Grazing alters the responses of GPP to environmental factors in an alpine meadow ecosystem on the Tibetan Plateau primarily by modifying surface microclimates - Wenbo Xiang; Yangjian Zhang; Renwei Chen; Lingxuan Zhao; Mingjie Xu; Shengtong Li; Guang Zhao; Zhoutao Zheng; Nan Cong; Juntao Zhu; Tao Zhang (Journal of Arid Environments, 2027)

Catechin-driven dual metabolic modulation enhances docosahexaenoic acid biosynthesis and oxidative stability in Schizochytrium sp - Chengxi Zhang; Zifan Zhang; Yuxuan Chen; Yingfeng Li; Guang Yang; Xiaoman Sun; Wang Ma (Bioresource Technology, 2027)

Low-temperature pyrolysis enhanced dissociation and waste oil assisted green flotation for the recovery of electrode materials from spent LiCoO2 batteries - Xin-long Li; Xiang-nan Zhu; Guang-liang Wei; Chun-liu Hu; Xiao-tian Zhao; Jing-tao Chen; Wen-hao Gao; Chun-chen Nie; Yong-qiang Zhao; Gu-yue Li (Minerals Engineering, 2026)

Shikonin alleviates high-fat diet-induced vascular aging and dysfunction by inhibiting oxidative stress and mitochondrial damage - Guang-qiu Ren; Hui-jun Liu; Ya-qi Guo; Mei-ling He; Jiao Li; Zhan-xia Li; Chen-hui Jia; Tong Liu; Jing Yang (Molecular Biology Reports, 2026)

ANGPTL4 in gestational diabetes: a diagnostic biomarker linked to placental senescence - Yu-Feng He; Hui Chen; Chuan-Meng Zhang; Su-Su Yang; Xiao-Long Yang; Li-Shuai Jiang; Fan Wang; Shu-Guang Zhou (Functional & Integrative Genomics, 2026)

Phosphate-induced surface roughening suppresses bacterial transport in coral sand - Guang Chen; Pengfei Gan; Yunyi Li; Jialiang Liang (Environmental Pollution, 2026)

DEM Investigation of Cyclic Lateral Loading of Granular Backfill for Integral Abutments: Earth Pressure Ratcheting and Settlement Mechanisms - Hao-Biao Chen; Nian-Wu Liu; Hong Wang; Ming-Guang Li; Guang-Zai Chen (Computers and Geotechnics, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Bioaugmentation in treatment wetlands: Opportunities, challenges, and safety considerations - Nianwen Chen; Huaqing Liu; Jizhen Li; Longlong Zhang; Dongle Cheng; Yanlong Wang; Guang Yang; Jian Zhang (Bioresource Technology, 2026)

Insights into the alleviating effects of exogenous α-ketoglutaric acid on free nitrous acid stress in Tribonema minus and ammonium removal in wastewater - Xinjuan Hu; Mingrui Wu; Teng Li; Xianhui Xue; Xu Yan; Baolong Wang; Lili Chen; Xiangru Xu; Lijuan Meng; Zhen Yu; Mostafa El-Sheekh; Guang Yang; et al. (Bioresource Technology, 2026)

Nitrogen and straw optimization boosts rice growth via arbuscular mycorrhizal fungal communities and soil ecological functions - Rui Chen; Ning Wang; Pei Chen; Yu Cheng; Jian-Guang Yu; Li-Hong Xue; Lin-Zhang Yang (Applied Soil Ecology, 2026)

Colorful microwave absorbers: Maya-inspired hybrid pigment with flaky carbonyl iron for enhanced absorption performance - Dandan Min; Meng Zhou; Guang Hu; Xiaoyan Gao; Yu Wang; Meiyan Chen; Xinyue Yang; Jiahui Zhi; Yaxin Zheng; Mengling Tang; Chenxi Li (Applied Clay Science, 2026)

Stochastic analysis of horizontal dynamic response of offshore pipe piles considering hydrodynamic pressure - Bo Yu; Libo Chen; Guang Han; Lichen Li; M. Hesham El Naggar; Wenbing Wu (Ocean Engineering, 2026)

Microbial community dynamics and functional gene shifts underpin enhanced nitrogen removal in a carrier-assisted transition from CANON to coupled CANON-denitrification - Neng-feng Qian; Shuai Zhang; Qi Luo; Qing-guo Chen; Ren-cun Jin; Li-juan Feng; Guang-feng Yang (Journal of Water Process Engineering, 2026)

Development of TM hypoallergenic enzymatic products with the potential to induce immune tolerance in Lateolabrax japonicus - Meng-Si Li; Qing-Mei Liu; Fei Xia; Su-Jie Huang; Shun-Xian Lin; Li-Qiang Zhong; Hao-Tian Zhang; Gui-Xia Chen; Guang-Ming Liu (Food Bioscience, 2026)

PFDA exposure promotes myocardial aging and fibrosis via hyperactivation of the MTORC1 signaling axis - Xiao Guang Chen; Ze Yu Liao; Yi Zhang; Ran Li (Food and Chemical Toxicology, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

CO2 sequestration via mixed hydrate formation in depleted Class I, II, and III hydrate reservoirs: A comparative study from laboratory to field scale - Hongyu Ye; Ling-ban Wang; Jie Li; Daoyi Chen; Xuezhen Wu; Dayong Li; Guang-jin Chen; Chang-yu Sun; Mucong Zi (Chemical Engineering Journal, 2026)

A photothermal-enhanced nanozyme hydrogel with stimuli-responsive biofactor delivery for diabetic bone regeneration - Renxin Chen; Zouwei Li; Guang Shi; Haoran Lu; Mengyue Zhu; Zhuowen Hao; Zijian Wu; Luhao Li; Jiayao Chen; Zheyuan Zhang; Lanhong Guo; Tian Luan; et al. (Chemical Engineering Journal, 2026)

Aeolian sediment provenance and supply mechanisms of the world's highest-elevation desert, Kumkol Desert: Insights from geochemical and geomorphological evidence - Guoxiang Chen; Junlin Yu; Zhibao Dong; Aimin Liang; Xiaokang Liu; Weikang Shi; Caixia Zhang; Peng Shang; Junquan Xu; Guang Li (CATENA, 2026)

Study on upper bound solution of anti-overturning bearing capacity of pile-bucket composite foundation in sand - Guang-si Chen; Rui Zhou; Le Wang; Run Liu; Tian-liang Li (Marine Georesources & Geotechnology, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

MOVLPSO-CNN-BiLSTM: Multi-objective variable-length particle swarm optimization-based CNN-BiLSTM for medium-term electric load forecasting - Guo-Qiang Zeng; De-Gui Yu; Li-Min Li; Yi-Peng Xu; Guang-Gang Geng; Chen Peng; Fei Chu (Swarm and Evolutionary Computation, 2026)

Process intensification of liquid-liquid extraction for zinc resource recovery via a submerged rotating packed bed - Zi-Qi Wang; Yi-Hang Xu; Xi-Fan Duan; Yan-Bin Li; Guang-Wen Chu; Jian-Feng Chen (Process Safety and Environmental Protection, 2026)

Effects of the hydration state of psyllium husk on the gel properties of pork meat batters under 50% phosphate reduction: Protein molecular interactions and lipid conformational alterations - Yu Wang; Hao Chen; Ning-ning Liu; Ke Li; Bo Chen; Jun-guang Li; Yan-hong Bai (Meat Science, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Comparison of food allergic immune responses in sensitized female and male Balb/c mouse induced by Lateolabrax japonicus tropomyosin - Meng-Si Li; Qing-Mei Liu; Fei Xia; Li-Qiang Zhong; Zhi-Qiang Chen; Ya-Ping Wu; Yu-Ni Liao; Gui-Xia Chen; Yi-Xiang Liu; Guang-Ming Liu (Food and Chemical Toxicology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

One-step fabrication of bioinspired dual-domain hierarchical wrinkled superhydrophobic strain sensors for intelligent perception - Xuemei Zhang; Guang Wang; Luyuan Chen; Guixian Li; Hongwei Li; Fengxing Niu; Jie Liu (Chemical Engineering Journal, 2026)

Redox-sensitive genetic circuits enhance microbial stress tolerance to complex inhibitors in lignocellulose biorefinery - Wen-Tao Wang; Qi Feng; Ting-Ting Li; Muhammad Aamer Mehmood; Hui Zhu; Ning Wang; Yi Ma; Chen-Guang Liu; Feng-Wu Bai (Chemical Engineering Journal, 2026)

Electrostatic-field-enhanced coordination anchoring of zirconium-oxo nanoclusters on amino-functionalized biochar for selective fluoride removal - Lian-Lian Liu; Zheng Tang; Mei-Qi Fan; Chen-Guang Yang; Yan Li; Qi-Di Liu; Xin-Li Wen; Shun-Li Wan (Chemical Engineering Journal, 2026)

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Calcium-mediated catalytic ozonation for water purification: Synergistic interplay among surface acid-base sites, alkaline interfacial microenvironment and dynamic oxygen supplementation - Hong-Guang Li; Cheng Chen; Zhi-Hang Wu; Ai-Yong Zhang; Rui-Gang Zhang; Shao-Wei Yuan; Ming Du; Jing-Yu Zhang (Water Research, 2026)

Effects of Alhagi sparsifolia root content and soil moisture content on soil deformation and strength under different freeze-thaw temperature conditions - Meixue Zhang; Qinglin Li; Xuanbing Luo; Wenjuan Chen; Rui Wang; Shuailong Yu; Guang Yang (Soil and Tillage Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Quorum sensing signals in reclaimed water enhance bacterial transport in carbonate porous media - Guang Chen; Yunyi Li; Pengfei Gan; Jialiang Liang; Shuai Wang; Yun Shen; Meiping Tong (Journal of Environmental Management, 2026)

Plastein reaction improves the ADH-stabilizing activity and digestive stability of chicken hydrolysate: The critical role of hydrophobic peptides - Chuqiao Xiao; Yongqi Xiao; Hujiaan Zeng; Zijie Chen; Xinqi Jiang; Xiaoyan Ning; Xiang-Guang Li (Food Chemistry, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

The abiotic drivers of soil system perturbation by metallic nanomaterials: a critical review bridging interfacial processes to environmental risks - Mengcheng Zhang; Xue Li; Yongchao Zhao; De'an Chen; Na Tian; Wenrui Zhang; Dongle Cheng; Guang Yang; Xiaoqiang Cao; Yanlong Wang; Huaqing Liu; Jian Zhang (Environmental Research, 2026)

Seismic behavior of novel multi-celled composite shear walls with energy-dissipating corrugated steel plates - Dai-Jiang Zhou; Xian Li; Chen-Ze Li; Zi-Lin Zhang; Xi-Guang Liu; Ming Chen (Engineering Structures, 2026)

Integrated 0D-1D-2D architecture in SiC/Si3N4 composites via TRM-exfoliated multilayer graphene and catalytic reactive sintering for synergistic mechanical-electromagnetic absorption properties - Cunhong Song; Zicui Lu; Juntong Huang; Ruo Huang; Zhiguo Ye; Ruiming Yin; Huiyong Yang; Qifa Wan; Vladimir Gennadievich Konakov; Deqing Chen; Guang Li; Ruiying Luo (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Numerical Investigation of Time-Dependent Deformation and Fracture Evolution in Flawed Sandstone - Teng-Fei Fu; Zhu-Guang Wang; Bi-Bi Qiao; Ya-Tao Li; Tao Ding; Chong-Feng Chen (Geotechnical and Geological Engineering, 2026)

Hair Follicle Stem Cells: Emerging Physiology and Therapeutic Applications - Shuyuan Yang; Qun Chen; Hanluo Li; Guang Yang (Stem Cell Reviews and Reports, 2026)

Study on the present-day crustal deformation characteristics and mechanism of the Yangyuan basin - Chen Gao; Jun Cao; Jian-Bao Sun; Jiang-Tao Qiu; Guang-Qing Ma; Fan Li (Applied Geophysics, 2026)

Numerical Investigation of Coupled Vortex-Induced Vibration and Scour of Subsea Pipelines under Ocean Currents - Yancheng Li; Xueliang Wen; Guang Yin; Lusheng Jia; Jun Huang; Naiquan Ye; Muk Chen Ong (Journal of Marine Science and Engineering, 2026)
Sediment transport beneath subsea pipelines is essentially a highly complex multiphase flow problem, involving strong coupling between hydrodynamics, structural response, and sediment transfer. Accurately capturing this process is of significant scientific and engineering importance for predicting seabed evolution and ensuring the structural safety and stability of subsea pipelines. In this study, the coupled vortex-induced vibration (VIV) and scour behaviour of subsea pipelines under steady current conditions is investigated using a computational fluid dynamics (CFD)-based numerical approach. The solver is developed within SedFoam by incorporating dynamic mesh motion to account for pipeline vibration. The pipeline is modelled as a single-degree-of-freedom system with a vertically mounted spring and a concentrated mass. The numerical results reveal a strong interaction between pipeline VIV and the evolving seabed morphology. Repeated pipeline motion toward the seabed significantly modifies the local scour profile and promotes the formation of a sand dune beneath the pipeline. The presence of the sand dune alters the near-bed flow field and suppresses vortex shedding beneath the pipeline. As the scour process develops and the fluid–structure–seabed interaction intensifies, the VIV response of the pipeline is progressively reduced. The present study highlights the important coupling mechanisms between pipeline vibration and seabed scour and provides insights into the dynamic evolution of pipeline–seabed interaction.

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

Estimating hydraulic conductivity based on a backbone curve model - Jia-Bin Li; Yun-Hua Li; Ming-Guang Li; Jin-Jian Chen; Yong-Mao Hou; Guan-Lin Ye (Transportation Geotechnics, 2026)

Janthinobacterium foliorum sp. nov., isolated from the decayed leaves of wild alpine rhododendron - Hui-Bin Lu; Ling-Yang Kong; Li Chen; Guang-Jie Chen (Systematic and Applied Microbiology, 2026)

3D analytical modeling of seismic ground motion and energy partitioning in the marine site subjected to obliquely P-SV waves - Guang-rui Feng; Li-quan Xie; Chen-wei Luo (Soil Dynamics and Earthquake Engineering, 2026)

Modeling and optimization of a hybrid PV/T-PRO-SOFC-WT multi-energy system using TTAO-GAO algorithm - Yingxue Chen; Haojun Deng; Changyu Ni; Guang Li (Process Safety and Environmental Protection, 2026)

Supplementing with vitamin B6 during the active phase can promote digestion, enhance intestinal barrier integrity, and accelerate the maturation of ileum flora in juvenile mice - Ya-Xin Liu; Jin-Hao Pang; Li-Ping Chen; Fei Huan; Qing-Mei Liu; Meng Liu; Yan-Ling Hao; Chen-Hong Zhang; Lian-Zhong Luo; Guang-Ming Liu (Food Bioscience, 2026)

Discrete element insights into passive failure mechanisms and Non-Limit earth pressure development - Hao-Biao Chen; Ming-Guang Li; Zhou-Jun Ma; Qing-Yun Yuan; Jin-Jian Chen (Computers and Geotechnics, 2026)

Punicalagin alleviates enterotoxigenic Escherichia coli-induced intestinal mucosal injury via Krüppel-like factor 4 - Xiang-Guang Li; Xiaowen Zhao; Peizhi Zhu; Jibin Fu; Jiaxin Zhang; Zhixin Yu; Runting Chen; Mingxia Chen; Chuqiao Xiao; Junxia Zheng (Chemico-Biological Interactions, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

Lithium isotopes as a new indicator for change in hydrology - Yadan Hu; Fei Zhang; Chen Chen; Ying Xie; Li Deng; Xiangying Li; Xiaolong Zhang; Guang Bao; Jinzhao Liu; Zhangdong Jin (Geochimica et Cosmochimica Acta, 2026)

Highly-selective extraction of lithium from low-quality brines through β-diketone-anchored porous microspheres - Feng Liu; Shimao Xue; Shijie Zhang; Xiaoling Zeng; Peng Zha; Shicong Chen; Sihui Li; Haotian Zhu; Feihu Bi; Liming Yang; Guang Yang; Xubiao Luo; et al. (Chemical Engineering Journal, 2026)

A mussel-inspired universal strategy for fabricating dual-bactericidal dressings to eradicate biofilms and accelerate infected wound healing - Guang Chen; Ruijie Xu; Shuang Li; Xiaoxue Chen; Yanjing Ji; Chunling Zhang; Ling Wang; Bingcheng Yi; Qihui Zhou; Yunbo Sun (Carbohydrate Polymers, 2026)

Exploratory behaviour shapes nutrient versus energy foraging priorities in Java sparrows - Ruiqiu Zhang; Yangkun Bi; Guang Chen; Deji Xue; Zhihui Jin; Donglai Li; Hui Li; Paul Racey; Dongmei Wan; Jiangxia Yin (Behavioural Processes, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

Strontium and cesium accumulation in soil-rice system: Influencing factors and predictive modeling - Hong-Ling Chen; Bao-Min Yao; Zi-Yang Pan; Dong-Li Sun; Guang Yang; Tian-Ran Sun; Guo-Xin Sun (Soil Ecology Letters, 2026)

Lignanamides, alkaloids, and other constituents from stems of Tinospora crispa - Yi-Yang Yuan; Xiang-Hong Chen; Tian Gao; Jun Li; Xian-Ju Huang; Hui Xiong; Zhi-Nan Mei; Yu Chen; Guang-Zhong Yang (Natural Product Research, 2026)

Two new quaternary ammonium zwitterions from the noni juice and their anti-gout activities - Dong-Hui Zhang; Yu-Qin Meng; Xu-hua Nong; Yan Ye; Zhang-Xin Yu; Xiao-Bao Li; Guang-Ying Chen (Natural Product Research, 2026)

Commentary: the TSP-1-CD47-integrin α4β1 axis—deciphering pathogenic mechanisms and therapeutic horizons in rheumatoid arthritis - Jie Guo; Feng-yi Mai; Xin-yu Li; Yu Liu; Jing-rong Liang; Xing-long Li; Chen-guang Li (Inflammation Research, 2026)

Assessment of commercial NF membranes for selective separation of Mg2+/Li+ in simulated brines - Tian-tian Xue; Jian-wei Jia; Fan-xin Kong; Li-ping Yue; Guang-dong Sun; Jin-fu Chen (Journal of Water Process Engineering, 2026)

The molybdenum isotope signature of cold seep sediments and its implication for marine molybdenum cycling - Niu Li; Guang-Yi Wei; Jörn Peckmann; Yu Chen; Jie Li; Pengfei Di; Shuhong Wang; Yi-Sheng Yin; Hong-Fei Ling; Duofu Chen (Geochimica et Cosmochimica Acta, 2026)

Plasma organophosphate ester exposure-associated microRNA expression profiles and their functional analysis in Chinese healthy adults - Xulin Zhang; Zirui Zhang; Yuxin Xu; Jiajia Zhu; Guang Chen; Rui Zeng; Wending Li; Xuedan Xu; Yu Yuan; Tao Jing; Tangchun Wu; Pinpin Long (Environmental Research, 2026)

From spent lithium-ion batteries to high-grade “urban mines”: A review of green recovery technologies for strategic metal resources of electrode material - Xiao-tian Zhao; Xiang-nan Zhu; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Chun-liu Hu; Chun-chen Nie; Gu-yue Li; Yong-qiang Zhao (Chemical Engineering Journal, 2026)

Chaotic effects in completely autotrophic nitrogen removal over nitrite process: how minor dissolved oxygen variations reshape microbial community and functional genes to drive divergent nitrogen removal - Yue Li; Wei-jian Wang; Shuai Zhang; Qi Luo; Neng-feng Qian; Dong-zhi Chen; Ren-cun Jin; Li-juan Feng; Guang-feng Yang (Bioresource Technology, 2026)

Synthesis and antihepatoma activity of dimeric 1-O-acetylbritannilactone derivatives - Guang-Xuan Du; Li-Qin He; Meng-Xiang Qin; Yun-Bao Ma; Xiao-Yan Huang; Yong-Cui Wang; Tian-Ze Li; Ji-Jun Chen (Medicinal Chemistry Research, 2026)

Model-based insights into temperature-driven declines in groundwater recharge under global warming in Michigan’s Lower Peninsula - Jing Zhang; Si-Chen Wu; Shu-Guang Li; Hua-Sheng Liao; Shi-Tao Peng; Jian-Min Zhang (Hydrological Sciences Journal, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

A new dameselloid trilobite from the Changhia Formation (Cambrian, Drumian) in central Shandong, North China - Guang-Ying Ren; Jin-Liang Yuan; Yi-Fan Wang; Bai-Zheng An; Kai Chen; Xiao-Hui Cui; Jian Gao; Nan Li (Palaeoworld, 2026)

Preparation of high quality CsPbI3 perovskite solar cells via CsF buried crystals - Pengyue Wang; Zhinan Hu; Gaoquan Li; Decheng Yang; Chao Li; Xushen Chen; Xiaopeng Wang; Shaopeng Yang; Tingwei He; Changjiu Sun; Guang Li; Kaixuan Zhou; et al. (Chemical Engineering Journal, 2026)

Environmental gradients mediate divergent patterns of microbial nutrient use efficiency and metabolic limitation in arid desert ecosystems - Xiaotong Li; Yudong Chen; Jinlong Wang; Yulin Shu; Guang Yang; Guanghui Lv (CATENA, 2026)

Java sparrows can modulate vocalizations in response to different light wavelengths - Deji Xue; Jinhong Chen; Yangkun Bi; Ruiqiu Zhang; Guang Chen; Donglai Li; Hui Li; Dongmei Wan; Paul Racey; Jiangxia Yin (Behavioural Processes, 2026)

The Influence of M1 and DLPFC iTBS on BCI Performance: A TMS and fNIRS Study - Jing Chen; Ya-wen Li; Shan-tong Yao; Yu-hong Huang; Wen-ming Ma; Zhi-hong Li; Yue Lan; Guang-qing Xu; Qian Ding (Translational Stroke Research, 2026)

Size-dependent performance and adaptive mechanisms of anammox granular sludge under fluctuating low-temperature conditions - Guang-feng Yang; Qi Luo; Neng-feng Qian; Ben-ze Chang; Ya-lei Liu; Dong-zhi Chen; Li-juan Feng (Biodegradation, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Soil microplastics at different depths before and after mechanical harvesting: case study in Anhui Province, China - Shi-hao Zhao; Di Dai; Yu-xin Tan; Si-yao Li; Bing-yu Chen; Qian Wang; Long Chen; Ji-yue Wang; Shu-guang Zhu; Fa-zhi Xie (Environmental Monitoring and Assessment, 2026)

Deciphering metallogenic linkage between deep K-bearing brine and salt lake brine in Mahai Playa: a perspective of dominance in boron in the northern Qaidam Basin - Min Li; Qishun Fan; Tianyuan Chen; Tong Pan; Guang Han (Journal of Oceanology and Limnology, 2026)

Development and analysis of the adverse outcome pathway network for neurotoxicity - Xinyue Hui; Xingying Li; Sisi Liu; Guang-Guo Ying; Chang-Er Chen (Toxicology, 2026)

Numerical simulation of dissolved oxygen transport under jet–roll coupled hydrodynamics in an aquaculture vessel tank - Zhiyong Sun; Hui Li; Guang Yin; Muk Chen Ong (Ocean Engineering, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Swelling of Compacted Bentonite into Technological Voids under Granite Boundary: Macro–micro Characterization and Hydro-mechanical Responses - Kun-peng Li; Yong-gui Chen; Wei-min Ye; Zhao Sun; Qiong Wang; Xing-guang Zhao (Rock Mechanics and Rock Engineering, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

The controllable generation of ·OH in NH2OH-enhanced Fe(III)/H2O2 system: the overlooked role of N-containing species - Hai-Teng Gu; Zhuo-Yu Li; Shi-Xuan Chen; Dong-Guang Yang; Chun-Mao Chen; Jun Ma (Water Research, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

A tripartite pollen killer–protector system confers temperature-sensitive inter-subspecific reproductive isolation in rice - Gousi Li; Yaling Zhang; Haixin Yu; Yongyao Xie; Hao Luo; Yuzhu Wang; Jintao Tang; Jia Zhang; Xianrong Xie; Wubei Zong; Kehong Liu; Xinhe Wang; et al. (Molecular Plant, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Retention time prediction of emerging contaminants via transfer learning with graph neural networks - Jiewen Deng; Junbin Chen; Jingyi Wang; Xingying Li; Sisi Liu; Linke Ge; Guang-Guo Ying; Chang-Er Chen (Journal of Hazardous Materials, 2026)

PE microplastics altered microbial resource limitation and C/N use efficiency in cotton rhizosphere soil - Yudong Chen; Xiaotong Li; Yulin Shu; Zhoukang Li; Guang Yang; Jinlong Wang; Qiong Wu; Wen Cao; Eryang Li; Yuehan Liu; Wusong Li; Guanghui Lv (Journal of Hazardous Materials, 2026)

Study on the influence mechanism of lead carbonate salt compounds on the combustion behaviors of 5AT/Sr(NO3)2 solid propellant - Yuan-Hui Liu; Jiu Chen; Zhan-Jun Yang; Guang-Ling Chen; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Li-Feng Xie; Dan Zhang (Fuel, 2026)

In-situ fabrication of magnetic prussian blue composites for highly selective rubidium recovery from high-salinity brine - Zheng Li; Zilong Chen; Chi Ma; Wei Qin; Jiantuan Jia; Guang Han; Yafei Guo; Tong Pan; Tianlong Deng (Desalination, 2026)

Synergistic octahedral distortion regulation to boost high-performance Fe-activated spinel phosphors for non-invasive lactate detection - Lu Chen; Chenxi Kang; Meng Sun; Shuai Tang; Tao Zhang; Ji-Guang Li; Qi Zhu (Chemical Engineering Journal, 2026)

Hierarchical Framework for Reservoir Co-management: A Cross-scale Reservoir Dispatch Paradigm Balancing Energy and Morphogenic Flow Needs - Hong Zeng; Tian-Yao Zhang; Yi-Ming Liao; Guang-Wen Ma; Ji-Dong Li; Wei-Bin Huang; Yan-Mei Zhu; Shi-Jun Chen (Water Resources Management, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Synergetic activation of both peroxydisulfate and bisulfite by Fe³⁺ for efficient singlet oxygen generation and organic pollutant degradation - Xin Zhang; Kangning Huangfu; Xiafei Meng; Jinghua Li; Junpei Ye; Yingxuan Deng; Zhihua Chen; Dapeng Wu; Kai Jiang; Guang-En Yuan; Fenglin Yang (Process Safety and Environmental Protection, 2026)

Mechanistic insights into gas capture and diffusion during the CO2 separation of mixed matrix membranes using ZIF materials as nanofillers - Han-chong Liu; Hong-li Chen; Li-guang Wu; Ting Wang; Hua-li Chen; Cheng Hu (Process Safety and Environmental Protection, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Nor-halimane and spiro-labdane diterpenoids with anti-inflammatory activity from Leucas ciliata Benth - Jia-Cai Kuang; Fu-Ling Cen; Xuan Zhang; Xu-Hua Nong; Xue-Ming Zhou; Xiao-Bao Li; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2026)

Numerical investigation of Jet–Roll coupled flow characteristics in an aquaculture vessel tank - Zhiyong Sun; Hui Li; Guang Yin; Muk Chen Ong (Ocean Engineering, 2026)

Mechanism of differential efficiency in expression of sericin 3 and silk fibroin heavy chain-like protein in the posterior silk gland of the domestic silkworm (Bombyx mori) - Yongfeng Wang; Yuguo Wang; Qiuying Li; Ruji Peng; Xinyin Liang; Xuedong Chen; Guang Wang; Yanghu Sima; Shiqing Xu (Journal of Insect Physiology, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Precision screening of Lactobacillus with potential anti-allergenic using dual cell model - Xiang-Ge Xin; Yue Meng; Zai-Chen Li; Jun Xi; Jun Meng; Chang-He Ding; Dong-Ge Zheng; Ling-Guang Du; Shu-Song Wang (Food Bioscience, 2026)

Corrigendum to “Hierarchical-structured bacterial cellulose/potato starch tubes as potential small-diameter vascular grafts” [Carbohydrate Polymers 281 (2022) 119034] - Li Liu; Xiongfa Ji; Lin Mao; Li Wang; Kun Chen; Zhijun Shi; Abeer Ahmed Qaed Ahmed; Sabu Thomas; Revin Victor Vasilievich; Lin Xiao; Xiaohong Li; Guang Yang (Carbohydrate Polymers, 2026)

FOXP2-Dependent Vulnerability of RGCs Under Acute Ocular Hypertension - Meifang Yan; Junjian Li; Zihao Zhang; Jieni Wang; Qi Tang; Jialu Wu; Huateng Cao; Xue Li; Jie-Guang Chen (Molecular Neurobiology, 2026)

Overlooked Roles of Pharmaceutical Metabolic Products in Stimulating Microbial Metabolism and Antibiotic Resistance Gene Dissemination of Anaerobic Sludge - Jing Wu; Dan Sun; Yuan Pan; Dong‐Feng Liu; Hui Zhang; Jun‐Hua Zhou; Tong Gao; Jie Wu; Ru‐Li He; Yin‐Guang Chen; Wen‐Wei Li (Environmental Microbiology, 2026)
The roles of non‐antibiotic pharmaceuticals in shaping the dissemination behaviours of antibiotic resistance genes (ARGs) in wastewater treatment systems remain poorly understood, and the influences of their transformation products have been overlooked. Here, we unveil more profound impacts of the metformin (MET) biotransformation product than the parent pollutant on the microbial community structure and ARG propagation of wastewater anaerobic sludge. The exposure to MET and its metabolic products guanylurea (GUA) at environmentally relevant concentrations both raised the methane production and resulted in up to 52.5% higher sludge ARGs abundance relative to the unexposed control. Especially, the GUA group showed up to 188‐fold upregulation in several ARGs including bcrA , PmrF , acrB and mexF , enabled 3218‐fold enrichment of plasmids from several bacteria. The underlying mechanisms were elucidated by integrated metagenomics, molecular dynamics simulations, and metabolic profiling analyses. MET and GUA were found to trigger coordinated cellular responses including disrupted glycerophospholipid metabolism, increased membrane permeability and broad metabolic reprogramming, which collectively boosted the ARGs dissemination. Overall, this work establishes a mechanistic link between micropollutant‐induced microbial stress and ARGs propagation in anaerobic sludge, and advocates for re‐evaluating the environmental risks of non‐antibiotic pharmaceuticals and integrating resistance control into wastewater management framework.

Lanostane-type triterpenoids from the fungus Inonotus obliquus - Tian-Hao Zhang; Wen-Li Zeng; Chuang Zhu; Di-Jun Chen; Hui Xiong; Guang-Zhong Yang; Yu Chen (Natural Product Research, 2025)

DiffKNet-TL: Maize phenology monitoring with confidence-aware constrained diffusion model based on UAV platform - Guang Yang; Chang Liu; Gaoliang Li; Hong Chen; Keying Chen; Yakun Wang; Xiaotao Hu (Computers and Electronics in Agriculture, 2025)

Chi-miR-146a promotes the propagation of Neospora caninum by targeting the TGF-β1/SMAD2 pathway - Jin-Ming Chen; Jing-Yu Li; Jia-Yi Jin; Xiao-Qi Bao; De-Liang Tao; Xiao-Yun Zhao; Jun-Ke Song; Xin Yang; Ying-Ying Fan; Guang-Hui Zhao (Veterinary Parasitology, 2025)

Synthesis of a Bi5O7Br/BiOBr photocatalyst to enhance norfloxacin degradation under simulated sunlight - Rongpeng Yang; Guang Lu; Zheng Li; Jingjing Zhao; Lei Yang; Fei Wang; Zhen Chen; Ghulam Mustafa; Wei Ma (Process Safety and Environmental Protection, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Fingerprinting sediment sources of the largest desert reservoir in Asia and its environmental implications - Guoxiang Chen; Zheng Chi; Zhibao Dong; Aimin Liang; Xiaokang Liu; Guang Li (Journal of Hydrology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Enhanced bacterial capture in hematite-modified biochar amended coral sand filters: Lab-scale validation and DFT mechanisms - Jialiang Liang; Guang Chen; Jingyao Luo; Pengfei Gan; Yunyi Li; Zhiwei Zhao; Meiping Tong (Journal of Hazardous Materials, 2025)

Nitrate modulates high CO2 effects on carbon partitioning in Gracilariopsis lemaneiformis: Trade-offs between particulate and dissolved organic carbon sequestration - Jichen Chen; Chi Song; Yicheng Ke; Mengmeng Wang; Jianing Qiu; Liujun Nie; Gang Li; Guang Gao (Environmental Research, 2025)

Integrated physical–chemical mechanisms drive carbon stabilization under conservation tillage in Karst agroecosystems - Guang Xu; Qishun Mo; Zhou Li; Wangfei Qin; Rui Dong; Xuechun Zhao; Chao Chen; Anna Gunina; Narasinha Shurpali; Tulasi Lakshmi Thentu; Gang Nie; Yuan Li (CATENA, 2025)

TurboID-based proximity labeling identifies novel germline proteins that maintain E granule integrity and small RNA homeostasis in C. elegans - Kun Li; Xuezhu Feng; Ke Wang; Xiaona Huang; Liang Liu; Chaoyue Yan; Xinya Huang; Chengming Zhu; Quan Wen; Shouhong Guang; Xiangyang Chen (Science China Life Sciences, 2025)

Commentary on “CircMAPK1 induces cell pyroptosis in sepsis-induced lung injury by mediating KDM2B mRNA decay to epigenetically regulate WNK1” - Wen-jing Bai; Chen-guang Li (Inflammation Research, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Peroxymonosulfate activation by iron-sulfur tailings doped with SiO2 for efficient degradation of tetracycline - Chen-Chen Yin; Chun Cheng; Peng-Yu Zhang; Zheng-Yuan Zhang; Ying Qin; Li-Pin Xue; Yu-Qi Feng; Bai Sun; Shu-guang Zhu (Environmental Science and Pollution Research, 2025)

Isolation of diverse Undibacterium-related strains from alpine lakes and re-examining the taxonomic status of this genus - Hui-Bin Lu; Ling-Yang Kong; Li Chen; Guang-Jie Chen; Jian-Jun Wang (Systematic and Applied Microbiology, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Microbial synergistic corrosion of Ti30ZrAlV alloy: Acid dissolution-electron transfer coupling mechanism - Zhihao Feng; Yu Zhao; Qian Feng; Kaimin Wei; Huicong Dong; Shan Liu; Jiangang Wang; Guang Chen; Jianhui Li (Process Safety and Environmental Protection, 2025)

Gestational joint exposure to air pollutants and intrauterine skeletal development: Mediating effect of placental metabolome in a Chinese birth cohort - Zhong-Hua Lu; Chong Liu; Chen Tang; Jun-Feng Tan; Hao Chang; Yu-Jie Chen; Guang-Ming Li; Wen-Qing Lu; Yi-Xin Wang; Jie Zhang (Journal of Hazardous Materials, 2025)

Optimizing CH4 recovery and CO2 sequestration in natural gas hydrate exploitation through dynamic adjustment of CO2/N2 injection composition: A simulation study - Jing-Yu Kan; Jian Kang; Jun-Rong Qin; Xing Huang; Nan Li; Zhi Li; Guang-Jin Chen (Fuel, 2025)

Impact-induced magnetite is widespread on the near and far sides of the moon - Ronghua Pang; Chen Li; Yang Li; Zhuang Guo; Dongsheng Song; Haifeng Du; Luyang Wang; Sizhe Zhao; Yuanyun Wen; Xiang Li; Junhu Wang; Xiongyao Li; et al. (Earth and Planetary Science Letters, 2025)

CO2 hydrate growth behavior and gas storage capacity in water-absorbing porous media - Le Zhao; Xiao-Hui Wang; Yi-Wei Wu; Zhen-Bin Xu; Li-Yong Bao; Peng Xiao; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

An innovative and clean strategy to recover copper resources from waste printed circuit boards: Malic acid leaching and micro-nano copper preparation - Xi-guang Li; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Xiao-tian Zhao; Chun-chen Nie; Lin Li; Shuai Yan; Xiang-nan Zhu (Chemical Engineering Journal, 2025)

Multifunctional hierarchical BN/MXene-Fe3O4 aerogel for efficient thermal management and ultra-broadband microwave absorption - Xin-Miao Liang; Qi-Fan Xuan; Hong-Hao Li; Peijia Ding; Yu Zhang; Martin C. Koo; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Dongfeng Zhang; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Bentazone stress resistance in Methylocystis-Tetradesmus symbiosis: Biochemical and communicative exchanges - Yong-Ze Lu; Chen Di; Ji Sun; Ling Wang; Xin Li; Guang-Can Zhu (Bioresource Technology, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Biotransformation of oleanonic acid by circinella muscae to produce novel 11,12-epoxy-13,28-lactonized derivatives and their anti-neuroinflammatory activity - Wei Liu; Li Yang; Liu-Tong Guan; Jia-Hui Wang; Yao-Yu Liu; Yan Song; Jian-Lin Li; Wen-Li Wang; Bo-Yi Fan; Guang-Tong Chen (Natural Product Research, 2025)

Synergistic enhancement of Pt electrocatalyst stability and activity in hydrogen oxidation reaction by polyoxometalate and carbon dot co-boosting - Fei-Yang Yu; Zhong-Ling Lang; Xian Wang; Jing Sun; Yu-Chen Liu; Hua-Qiao Tan; Jun-Jie Ge; Yang-Guang Li; Zhen-Hui Kang (Science Bulletin, 2025)

Thermal damage evolution of carbon fiber/epoxy composites for hydrogen storage tanks under fire conditions - Pan-Deng Liu; Bei Li; Xin Ma; Bing Han; Guang-Yin Li; Dong-Lei Sun; Chen Song (Process Safety and Environmental Protection, 2025)

Response of biofilm and granular sludge to low dissolved oxygen and organics in a single anammox reactor: Performance, bacterial community and function genes - Qi Luo; Yi-shu Li; Ben-ze Chang; Shuai Zhang; Dong-zhi Chen; Ren-cun Jin; Guang-feng Yang (Journal of Environmental Chemical Engineering, 2025)

Effect of cold plasma modification on bacterial cellulose and its dispersion behavior in chitosan-based matrix - Hui-mei Liu; Yao-yao Wang; Xiangzhen Ge; Yun Chen; Xi-guang Ye; Yong Hu; Mengfan Li; Chao Huang; Dong-mei Li (Food Bioscience, 2025)

Closing the oceanic lithium budget by continental shelf sediment removal - Qingquan Hong; Guang-Yi Wei; Gaojun Li; Yi-Bo Lin; Feifei Zhang; Shilei Li; Chenglong Wang; Zhimian Cao; Pinghe Cai; Tianyu Chen (Earth and Planetary Science Letters, 2025)

The dielectric permittivity modulation effect of phase engineering on SiC whiskers modified reduced graphene oxide composites - Yun-Tian Chen; Bo Cai; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Wen-Ping Li; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Catalyzing polysulfides redox reactions by p-d orbital hybridized ZnCoSe with built-in electric field - Zhengwei Yang; Peng Zhou; Tianyu Zhang; Jiali Liu; Ningxi Lu; Dengke Li; Min Liu; Guang Li; Jincang Su; Manfang Chen; Xiukang Yang; Hongbo Shu; et al. (Chemical Engineering Journal, 2025)

Unveiling Moxibustion's Impact on AD Mice Learning and Memory: Role of Mitochondrial Respiratory Chain Complex I Subunit in the Hippocampus - Yuan Shen; Hong-Ying Li; Qing-Qing Yang; Ke Zhang; Shu-Qing Liu; Ning Zhang; Chen-Yu Li; Shu-Guang Yu; Lu-Shuang Xie; Qiao-Feng Wu (Molecular Neurobiology, 2025)

Failure mechanism of ice and snow melting–induced rock avalanche: a case study of rock avalanche in Liangshui Village, Zhenxiong County, China - Guang Zheng; Xinwu Li; Jinning Yang; Zhongyi Yu; Mingyu Zhang; Qi Liu; Jun Chen; Zhendong Liu (Landslides, 2025)

Removal of emerging organic contaminants in a subsurface wastewater infiltration system: A preliminary study of microbial mechanism - Feng-Jiao Peng; Xing-Jun Feng; Sen Li; Xiao-Long Yu; Jun Chen; Shuang-Shuang Liu; Guang-Guo Ying; You-Sheng Liu (Water Research, 2025)

Closed-loop recycling of lead iodide precursor from waste organic solvents in the production of perovskite solar cells: Toward sustainable photovoltaics - Qingfang Zou; Zifan Lin; Zhaoyang Li; Guang Hu; Shifa Zhou; Ying Zheng; Liang Huang; Sha Liang; Huabo Duan; Shushan Yuan; Chao Chen; Ling Xu; et al. (Waste Management, 2025)

Conservation and divergence of OsGSTU9 and OsGSTU19 in cadmium detoxification and accumulation in rice - Xuan Chen; Wei Jiang; Di Chang; Qingfeng Zheng; Chunmeng Zhu; Li Hao; Fanrong Zeng; Zhong-Hua Chen; Guang Chen; Yuan Qin; Fenglin Deng (Journal of Hazardous Materials, 2025)

Selective complexation-stepwise precipitation-roasting process for separating and preparing ZnO nanoflakes from complex zinc-containing solutions - Yangfan Chen; Jiangling Li; Dabiao Tian; Ni Yang; Guang Hu; Qingcai Liu (Journal of Cleaner Production, 2025)

Cross-reactivity and conserved epitope analysis of tropomyosin from Lateolabrax japonicus and shellfish species - Meng-Si Li; Fei Xia; Qing-Mei Liu; Fa-Jie Li; Yu-Ni Liao; Li-Qiang Zhong; Gui-Xia Chen; Lian-Zhong Luo; Yi-Xiang Liu; Guang-Ming Liu (Food Chemistry, 2025)

Pre-carbonization facilitates closed pore formation in asphalt-derived hard carbon for high-plateau-capacity sodium storage - Chong Xu; Dongyuan Zhang; Guang Ma; Shuang Liu; Gong Cheng; Junjie Fu; Ye Wang; Runyi Xu; Chen Ling; Sai Che; Yongpeng Cui; Yongfeng Li (Chemical Engineering Journal, 2025)

3D printing of scaffolds for articular cartilage/osteochondral regeneration: Design, performance, and applications - Luhao Li; Guang Shi; Zijian Wu; Zhenxin Cai; Junwu Wang; Zhuowen Hao; Renxin Chen; Zhenzhou Piao; Chao Chen; Jingfeng Li (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Two-step cascade upgrading of Caragana korshinskii into bio-oil and biofuel by solvent-mediated selective hydroconversion over a MOF-based Ni@C - Han Wang; Guang-Hui Liu; Xiao-Xue Wang; Xiao-Qi Zhang; Yu-Hong Kang; Yun-Yan Gao; Lu-Yuan Chen; Xia-Long Li; Xian-Yong Wei (Biomass and Bioenergy, 2025)

Fire severity strongly shapes soil enzyme activities in terrestrial ecosystems: insights from a meta-analysis - Hua Chai; Michelle C. Mack; Jie Li; Guiyao Zhou; Jing Wang; Ruiqiang Liu; Zhenggang Du; Hongyang Chen; Yanghui He; Guang Yang; Long Sun; Xuhui Zhou (Plant and Soil, 2025)

TAT-T407 Mitigates Apoptosis and Cognitive Impairments Following Cerebral Ischemia Through Disruption of TRPV1-CDK5 Interaction - Qian Feng; Ying Li; Xiangru Wen; Hui Li; Chengyu Qi; Nan Wang; Guang Zhu; Yanyan Fu; Changdong Liu; Dan Liu; Zhen Zhang; Fan Yang; et al. (Molecular Neurobiology, 2025)

URSE-Net: a method of extraction winter wheat planting information based on multispectral remote sensing images - Yuguang Zhou; Mingxu Ma; Guang Yang; Zeyu Wang; Youchun Lai; Haifan Liu; Li Chen; Mo Wang (International Journal of Remote Sensing, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

Efficiencies, pathways and mechanism on simultaneous biodegradation of phthalates and polycyclic aromatic hydrocarbons by bacterial consortium - Yao-Si Chen; Jia-Lu Wei; Jie-Bin Zhou; Yu-Hong Huang; Guang-Xuan Tang; Yan-Wen Li; Hai-Ming Zhao; Lei Xiang; Nai-Xian Feng; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Two magmatic-hydrothermal events in Xinzhai Sn polymetallic deposit, Yunnan Province, China: Constraints from cassiterite U-Pb geochronology and elemental compositions of single fluid inclusions - Ying-Hua Chen; Wen-Chang Li; Ting-Guang Lan; Xiao-Yu Zhao; Ming-Guo Deng; Die Wang; Yan-Wen Tang; Ji-Huang Lai (Gondwana Research, 2025)

Corrigendum to “Surface segregation on Ag@MNi (M = Pd, Pt, Rh, and Ru) core–shell nanocrystals for enhancing the oxygen reduction performance” [Chem. Eng. J. 500 (2024) 156765] - Xinyuan Zhou; Qiyan Sun; Xinlin Wang; Ruixue Zhang; Bin Li; Zexing Wu; Dehong Chen; Lei Wang; Guang-Rui Xu (Chemical Engineering Journal, 2025)

Mechanistic insights into the combustion behaviors of 5AT/Sr(NO3)2 solid propellant induced by additives (Cu2(OH)2CO3 and Cu(OH)2)) - Jiu Chen; Guang-Ling Chen; Yuan-Hui Liu; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Guang-Cheng Yang; Li-Feng Xie; Dan Zhang (Chemical Engineering Journal, 2025)

Weakly solvated anion optimization for electrode/electrolyte interface construction in high-voltage supercapacitors - Zhenlei Chen; Peng Zhang; Pan Liu; Tong Huo; Guofu Sun; Ningkai Li; Dongfang Xu; Zhiqiang Shi; Guang Feng; Qingyin Zhang (Chemical Engineering Journal, 2025)

Assessing how the partial substitution of phosphate by modified chickpea protein affects the technofunctional, rheological, and structural characteristics of pork meat emulsions - Yu Wang; Ning-ning Liu; Ke Li; Bo Chen; Jia-le Wang; Jun-guang Li; Yan-hong Bai (Meat Science, 2025)

Key toxic pathways of hepatotoxicity induced by titanium dioxide nanoparticles through multi-omics analysis - Jiaqi Shi; Ying Ma; Nairui Yu; Yi Zhang; Zongfu Cao; Li Guan; Xiaodong Liu; Zhangjian Chen; Guang Jia (Food and Chemical Toxicology, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

Siderophores produced by marine microorganisms - Lei Chen; Zhuo-Yue Li; Guang-Yu Wang (Antonie van Leeuwenhoek, 2025)

Impact of the Yangtze River on Sediment source-to-sink processes in estuarine bays: a study of the Oujiang River Estuary, SE China - Xia Guang; Ping Yin; Ke Cao; Fei Gao; Yuan Tian; Xiangtong Huang; Bin Chen; Meina Li; Jinqing Liu (Frontiers in Marine Science, 2025)
Our study was designed to unravel the provenance signals of sediments from various sediment source-to-sink processes. To achieve this, we systematically collected samples from river basins, estuaries, and offshore waters of the Oujiang River estuary. Analyses of clay minerals and trace geochemical elements (Cr, Th, Sc) were then conducted. Our findings revealed a dynamic pattern of sediment distribution, with the predominant clay minerals in the surface sediment of the offshore area being illite, followed by kaolinite and chlorite, with a minor smectite content. Notably, we observed a gradual increase in the proportions of illite and smectite from the upstream to the estuary, while kaolinite decreased accordingly. The ratios of Cr/Th and Sc/Th in the small mountain rivers also showed a gradual increase, indicating a rising influence of fine-grained sediment from the Yangtze River. Furthermore, we utilized a robust nonlinear mathematical model to determine and quantify the sources and provenance contributions of the clay fraction sediment in the Oujiang River estuary. Our model results revealed that the majority (64%) of the clay fraction sediment in the offshore region of the estuary originates from the Yangtze River. In contrast, sediments from small mountain rivers, including the Oujiang River, contribute an average of 29%, but this can increase to 40% within the Oujiang River estuary and its southern areas. Coastal currents and tides influence the sediment distribution in coastal areas. The Zhe-Min Coastal Current plays a significant role in transporting sediments from the Yangtze River to the estuaries of Zhejiang Province, where they settle in the downstream areas of the current. Moreover, sediment from the Oujiang River is carried southward by the coastal current, most of which is deposited in the estuary and the nearby coastal waters to the south. In conclusion, our study underscores the significant influence of sediments from the Yangtze River on the surface sediments in small mountain rivers and offshore regions near the Zhejiang coastline.

A Novel Metric for Assessing Long-Term Outcomes in Adults with Chiari Malformation Type I: Occipitocervical Dura Angulation (ODA)—Applications and Value - Bo Wang; Shi-Chao Chen; Yao-Wu Zhang; Wei-Hao Liu; Chong Wang; Yi-Xiang Liu; Guang-Hao Zheng; Jia-Lin Li; Kai Ji; Jun Yang; Yong-Zhi Wang; Wen-Qing Jia (The Cerebellum, 2025)

A comprehensive reconnaissance and risk assessment of rubber additives and their transformation products (RATPs) in groundwater: 1,3-Diphenylguanidine (DPG) as a pressing ecological concern - Hai-Yan Zhang; Yu Han; Li-Xin Hu; Yingjie Chen; Guang-Guo Ying; Jian-Liang Zhao (Water Research, 2025)

The impact of dietary fat and fatty acid consumption on human health: A comprehensive review of meta-analyses and the Global Burden of Disease study 2021 - Jianglei Ma; Dingtao Hu; Duocai Li; Yuan Chen; Qingyang Chen; Zhiguo Fan; Guang Wang; Weidong Xu; Guanghui Zhu; Zhixiang Xin; Wanli Cao; Zongqin Zhang; et al. (Trends in Food Science & Technology, 2025)

Synergistic bimolecular erosion-healing interfacial passivation for wide-bandgap perovskite and tandem solar cells - Shiqiang Fu; Guang Li; Shun Zhou; Jiahao Wang; Dexin Pu; Lishuai Huang; Zhiqiu Yu; Wanping Chen; Guojia Fang; Weijun Ke (Science Bulletin, 2025)

Simultaneous and instrument-free detection of quinine and crystal violet based on a dual-emissive Eu3+-functionalized metal-organic framework - Hou-Qun Yuan; Yuan Yuan; Si-Yi Liu; Jia-Hao Fu; Yi-Fan Xia; Wei Li; Meng-Yuan Pan; Lirong Jiang; Peiyao Chen; Guang-Ming Bao (Journal of Hazardous Materials, 2025)

Evaluation of gas production from oceanic hydrate deposits by N2 sweep combined with depressurization - Jing-Yu Kan; Jian-Hao Yang; Zhi Li; Zhen Xu; Nan Li; Guang-Jin Chen (Fuel, 2025)

Borate as a multifunctional bridging agent enhances oxygen evolution activity of Co-Ci/BiVO4 photoanode - Xingsheng Hu; Bing-Hao Wang; Yue Tian; Xiong Wang; Biao Hu; Yang Li; Guang-Hui Chen; Yutong Dai; Chao Peng; Sheng Tian; Mingming Yin; Huijuan Wang; et al. (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Adaptive changes of biofilm and sludge in CANON process under various organics stresses: Performance, biomass characteristics and metabolic pathways - Ben-ze Chang; Yi-chun Zhao; Shuai Zhang; Qi Luo; Dong-zhi Chen; Ren-cun Jin; Li-juan Feng; Guang-feng Yang (Process Safety and Environmental Protection, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Functional crosstalk of sucrose and G protein signaling in maize thermotolerance by modulating osmoregulation system - Hong-Yan Chen; Zhong-Guang Li (Protoplasma, 2025)

Anthraquinone-benzisochromanquinone dimers from the stems and leaves of Berchemia polyphylla - Wen-Li Xie; Zheng-Yang Lu; Jing Xu; Yu Chen; Hong-Li Teng; Guang-Zhong Yang (Natural Product Research, 2025)

Greenspace and respiratory diseases and symptoms in Chinese children: A large-scale study exploring joint associations with ozone - Pei-Pei Dong; Gongbo Chen; Yue Wen; Joachim Heinrich; Elaine Fuertes; Tianyu Zhao; Nur Sabrina Idrose; Li-Zi Lin; Zhao-Huan Gui; Xiaodi Qin; Hongwei Tu; Guang-Hui Dong (Sustainable Cities and Society, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

SuperDecode: An integrated toolkit for analyzing mutations induced by genome editing - Fuquan Li; Xiyu Tan; Shengting Li; Shaotong Chen; Lin Liu; Jingjing Huang; Gufeng Li; Zijun Lu; Jinwen Wu; Dongchang Zeng; Yanqiu Luo; Xiaoou Dong; et al. (Molecular Plant, 2025)

Key role of the CSE/transsulfuration pathway in macrophage phenotypic change under iron overload - Zhaoji Yuan; Yuxuan Chen; Yijun Xin; Yong Zhang; Zihao Dong; Jianxu Wang; Xiangdong Wang; Guang Yang; Siying Li (Journal of Trace Elements in Medicine and Biology, 2025)

Immobilized microorganisms to remove petroleum hydrocarbon from wastewater and soil: Mechanisms of enhanced remediation and response of microbial communities - Hengyu Chen; Chuan Yin; Cong Li; Huan Yan; Zhanling Shi; Guang Li; Huanfang Gao (Journal of Environmental Chemical Engineering, 2025)

Synthesis optimization of a hydrophobic cationic flocculant and its mechanism study in clay suspension: Experiment and simulation - Na Li; Yuping Fan; Xianshu Dong; Xiaomin Ma; Ruxia Chen; Ming Chang; Guang Xu (Journal of Environmental Chemical Engineering, 2025)

Structural characterization of biohumic acid from Hongshaquan lignite degraded by Bacillus sp. XK1 and its application in the Brassica chinensis L. Growth - Chen Shi; Ya-Kun Wang; Long Yan; Yu-Hong Kang; Guang-Hui Liu; Yong Gao; Jin-Jun Bai; Yan-Jun Li; Ai-Min Wang; Ya-Nan Zhu; Xian-Yong Wei (Fuel, 2025)

Preparation and evaluation of ozone micro-nano bubbles ice for Litchi precooling - Hao Deng; Li Guo; Guang Wu; Zhe Chen; Farhat Abbas; Qingchun Yin (Food Chemistry, 2025)

Preparation of high-performance SiOx anode materials via dual interfacial reinforcement strategy - Ye Wang; Chong Xu; Junjie Fu; Sai Che; Guang Ma; Kaiyi Chen; Jiahao Yang; Shuang Liu; Gong Cheng; Dongyuan Zhang; Yunen Huang; Wenyue Gao; et al. (Chemical Engineering Journal, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Chemodivergent, enantio- and regioselective couplings of alkynes, aldehydes and silanes enabled by nickel/N-heterocyclic carbene catalysis - Jia-Ming Liu; Xuexiang Ma; Guang Chen; Wang Wan; Zhiyang Li; Youjun Xu; Dongju Zhang; Shi-Liang Shi (Science Bulletin, 2025)

A family of nitronate monooxygenase-domain proteins are essential for biocontrol potential of the insect mycopathogen Beauveria bassiana - Hao Zhang; Xin-Yi Wang; Ting-Fei Sun; Tian-Jing Chen; Jin-Li Ding; Ming-Guang Feng; Sheng-Hua Ying (Pesticide Biochemistry and Physiology, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Intensification of organic liquid dispersion in a rotating packed bed with oleophobic mesh packing - Yu-Gan Zhu; Zi-Qi Wang; Yan-Bin Li; Bao-Chang Sun; Guang-Wen Chu; Jian-Feng Chen (Chemical Engineering Journal, 2025)

Roles of straw return in shaping denitrifying bacteria in rice rhizosphere soils through effects on root exudates and soil metabolites - Pei Chen; Yu Cheng; Ning Wang; Jian-Guang Yu; Ying Zhao; Li-Hong Xue (Soil Ecology Letters, 2025)

Fully hydro-mechanical coupled analyses of the deep excavation above a multi-aquifer-aquitard system - Ming-Guang Li; Yue-Heng Yan; Zhong-Hua Xu; Hao-Biao Chen; Chen-Xin Peng; Jin-Jian Chen (Tunnelling and Underground Space Technology, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

Warming reduces bacterial diversity and stability in Lake Bosten - Zhen Shen; Bobing Yu; Xinyu Chen; Chen Wang; Xingchen Li; Guang Gao; Keqiang Shao; Xiangming Tang (Journal of Environmental Management, 2025)

Treatment of dye-containing wastewater using discarded animal blood-derived hemoglobin crystals - Xiao-Qian Jin; Jie Liu; Chen-Yuan Li; Liang-Liang Chen; Jia-Lei Li; Xue-Ting Wang; Guang-Ming Mi; Da-Chuan Yin (Journal of Environmental Management, 2025)

Optimized carbonylation treatment of Litopenaeus vannamei matrix decreased its immunoreactivity and improved edible quality, simultaneously - Meng Liu; Ming-Xuan Wu; Fei-Fei Gong; Zhao-Min Sun; Ying Li; Fei Huan; Gui-Xia Chen; Qing-Mei Liu; Hong Liu; Guang-Ming Liu (Food Chemistry, 2025)

Phylogenetic and functional diversity consistently increase engineered ecosystem functioning under nitrogen enrichment: The example of green roofs - Guang Hao; Xiaoqin Chen; Zhibo Du; Nan Yang; Meiyang Li; Yue Gao; Jiaan Liang; Lei Chen; Hongyuan Li (Ecological Engineering, 2025)

Enhanced glucose utilization and succinic acid production in Corynebacterium glutamicum by integration of metabolic engineering and electro-fermentation - Yu-Chen Liang; Kai Li; Xin-Qing Zhao; Feng-Wu Bai; Chen-Guang Liu (Chemical Engineering Journal, 2025)

The integrated strategy of W/MoC quantum dot heterointerface and defect engineering enhances the performance of solar cells - Wen Wang; Jixin Yao; Xiuying Wang; Song Ye; Haifeng Xu; Dongmeng Chen; Guang Li (Chemical Engineering Journal, 2025)

Design, synthesis and herbicidal activity of novel cyclohexanedione derivations containing pyrazole and pyridine groups as potential HPPD inhibitors - Shuai-Tao Hou; Ling Han; Wen-Rui Li; Guang-Yu Dai; Yu Liu; Ai-Min Lu; Chun-Long Yang; Min Chen (Molecular Diversity, 2025)

Inhibition of fish rhabdovirus demonstrates application prospect of two methylimidazole phenylpropanoid-based small molecules in aquaculture - Tian-Xiu Qiu; Huan Wang; Yang Hu; Li-Peng Shan; Guang-Lu Liu; Lei Liu; Jiong Chen (Aquaculture, 2025)

Influence of oxygen carrier on NOx and N2O emissions in biomass combustion within fluidized beds - Guang Sun; Lin Li; Dennis Lu; Ming Hu; Zhenkun Sun; Rongtao Wang; Yuqing Chen; Lunbo Duan (Process Safety and Environmental Protection, 2025)

Absolute quantitative lipidomics reveals the disturbance of lipid metabolism induced by oral exposure of titanium dioxide nanoparticles - Nairui Yu; Jiaqi Shi; Ying Ma; Yi Zhang; Li Guan; Zhangjian Chen; Guang Jia (NanoImpact, 2025)

Gastrointestinal dysfunction as the main performance of the oral toxicity of titanium dioxide nanoparticle on gastric ulcer rats - Yun Wang; Chen Li; Te Ba; Shengyuan Wang; Langzhi He; Zhangjian Chen; Ji Pu; Xiaoxing Cui; Guang Jia (NanoImpact, 2025)

Efficient As(III) removal from acidic wastewater by polymorphism control of FeS - Jing Chen; Qingfeng Dong; Jing Li; Chaobo Zhang; Guang Fu; Zhanqing Lu (Journal of Water Process Engineering, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Effect of chickpea protein modified with combined heating and high-pressure homogenization on enhancing the gelation of reduced phosphate myofibrillar protein - Yu Wang; Jia-le Wang; Ke Li; Jing-jing Yuan; Bo Chen; Yun-tao Wang; Jun-guang Li; Yan-hong Bai (Food Chemistry, 2025)

The influence of steep faults at various avoidance distances on the stability of hard rock caverns: Physical model experiments and DEM simulations - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Shi-jie Chen; Guang-liang Feng; Quan Jiang; Xin-hao Zhu; Shu-qian Duan (Tunnelling and Underground Space Technology, 2024)

How to evaluate the reduction effect of the park on PM2.5? Exploratory application of the maximum and cumulative perspective - Pengcheng Li; Yun Chen; Haifeng Niu; Lu Zhang; Yu Tang; Guang Zhu; Zhongyuan Zhang; Yizhe Ma; Wen Wu (Sustainable Cities and Society, 2024)

Potential impact of organophosphate esters on thyroid eye disease based on machine learning and molecular docking - Tianqi Jia; Wenbin Liu; Arturo A. Keller; Lirong Gao; Xiaotian Xu; Wenqi Wu; Xiaoxia Wang; Yang Yu; Guang Zhao; Baohui Li; Jinglin Deng; Tianao Mao; et al. (Science of The Total Environment, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

DEHP regulates ferritinophagy to promote testicular ferroptosis via suppressing SIRT1/PGC-1α pathway - Qi Zhu; Jianan Zhai; Zhengguo Chen; Zhifang Guo; Xiance Sun; Jing Li; Ningning Wang; Xiaofeng Yao; Cong Zhang; Haoyuan Deng; Shaopeng Wang; Guang Yang (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Inheritance recharge of subsurface brine constrains on formation of K-bearing sand-gravel brine in the alluvial fan zone of mountain-basin system on the Qinghai-Tibetan Plateau - Qishun Fan; Guang Han; Tianyuan Chen; Tong Pang; Hongkui Bai; Jiubo Liu; Qing Miao; Xiaodong Zhang; Haotian Yang; Qingkuan Li (Journal of Hydrology, 2024)

The associations between exposure to ambient air pollution and coagulation markers and the potential effects of DNA methylation - Yan Chen; Guang-Hui Dong; Shuai Li; Yuewei Liu; Shanshan Li; Yuming Guo; Chongjian Wang; Gongbo Chen (Journal of Hazardous Materials, 2024)

The source and dissemination of ARGs in pristine environments: Elucidating the role of migratory birds in the Arctic - Qin Shu; Hui Gao; Rui-jing Li; Hai-yang Chen; Guang-shui Na (Journal of Hazardous Materials, 2024)

Per- and poly-fluoroalkyl substances (PFAS) accelerate biological aging mediated by increased C-reactive protein - Zongxi Zhao; Jiayan Zhou; Anye Shi; Jingyi Wang; Hongzheng Li; Xiangjun Yin; Jialiang Gao; Ying Wu; Jinlin Li; Ya Xuan Sun; Hao Yan; Yige Li; et al. (Journal of Hazardous Materials, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Swine wastewater co-exposed with veterinary antibiotics enhanced the antibiotic resistance of endophytes in radish (Raphanus sativus L.) - Wei-Li Jia; Fang-Zhou Gao; Chao Song; Chang-Er Chen; Chuan-Xin Ma; Jason C. White; Guang-Guo Ying (Environmental Pollution, 2024)

Antibacterial bioadaptive scaffold promotes vascularized bone regeneration by synergistical action of intrinsic stimulation and immunomodulatory activity - Yuhan Qian; Chenglin Li; Qian Feng; Xiaojun Mao; Guang Yang; Shuo Chen; Tao Li; Xiaojun Zhou; Chuanglong He (Chemical Engineering Journal, 2024)

Chemical constituents from noni (Morinda citrifolia L.) fruit juice and their chemotaxonomic significance - Yu-Qin Meng; Bin Zhang; Dong-Hui Zhang; Zhang-Xin Yu; Chun-Hua Long; Si-Rong Li; Xue-Na Zhang; Xiao-Bao Li; Guang-Ying Chen (Biochemical Systematics and Ecology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Unveiling the overlooked small-sized microbiome in river ecosystems - Fang-Zhou Gao; Li-Xin Hu; You-Sheng Liu; Lu-Kai Qiao; Zi-Yin Chen; Jian-Qiang Su; Liang-Ying He; Hong Bai; Yong-Guan Zhu; Guang-Guo Ying (Water Research, 2024)

Cellulosic ethanol stillage for methane production by integrating single-chamber anaerobic digestion and microbial electrolysis cell system - Tian-Jie Ao; Jie Wu; Kai Li; Richard Chandra; Xin-Qing Zhao; Yue-Qin Tang; Chen-Guang Liu; Feng-Wu Bai (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Mesoproterozoic (∼1.4 Ga) magmatism in northern Alxa, China: Implications for tectonic affinity of microcontinents in the southern Central Asian Orogenic Belt - Xing-Jun Shi; Tao Wang; Heng Zhang; Chen-Guang Zhang; Jin-Li Pang; Lei Zhang; Jian-Jun Zhang (Precambrian Research, 2024)

De-noising magnetotelluric data based on machine learning - Tuanfu Gui; Juzhi Deng; Guang Li; Hui Chen; Hui Yu; Min Feng (Journal of Applied Geophysics, 2024)

Texture characterization of 3D printed fibrous whey protein-starch composite emulsion gels as dysphagia food: A comparative study on starch type - Zhiming Wang; Funi Chen; Yuanyuan Deng; Xiaojun Tang; Ping Li; Zhihao Zhao; Mingwei Zhang; Guang Liu (Food Chemistry, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Investigation on the responses of geotechnical materials to unloading and seepage based on the CFD-DEM coupling method - Jin-Hui He; Ming-Guang Li; Xiao Xiao; Jin-Jian Chen (Computers and Geotechnics, 2024)

Surface segregation on Ag@MNi (M = Pd, Pt, Rh, and Ru) core–shell nanocrystals for enhancing the oxygen reduction performance - Xinyuan Zhou; Qiyan Sun; Xinlin Wang; Ruixue Zhang; Bin Li; Zexing Wu; Dehong Chen; Lei Wang; Guang-Rui Xu (Chemical Engineering Journal, 2024)

Long-term changes of surface ozone and ozone sensitivity over the North China Plain based on 2015–2021 satellite retrievals - Chuanyong Zhu; Yichao Gai; Zhenguo Liu; Lei Sun; Siyuan Fu; Kun Liu; Leifeng Yang; Guang Pan; Baolin Wang; Chen Wang; Na Yang; Zhisheng Li; et al. (Air Quality, Atmosphere & Health, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

Eco-friendly and highly efficient PM0.3 air filter made from nonwoven basalt fiber and electrospun nanocellulose fiber - Desalegn Atalie; Ze-Xin Chen; Hui Li; Cun-Guang Liang; Ming-Cheng Gao; Xiao-Xi Cheng; Peng-Cheng Ma (Journal of Hazardous Materials, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Metabolic pathways altered by air pollutant exposure in association with coagulation function among the rural elderly - Haoyu Huang; Ru-Qing Liu; Yan Chen; Yuewei Liu; Guang-Hui Dong; Jian Hou; Shanshan Li; Yuming Guo; Chongjian Wang; Gongbo Chen (Journal of Hazardous Materials, 2024)

Highly efficient capture and conversion of CO2 into cyclic carbonates from actual flue gas under atmospheric pressure - Wen-Wang Yu; Xiang-Guang Meng; Wen Li; Li-Yu Chen; Zi-Yu Gan; Yu-Lian Zhang; Jie Zhou (Journal of Environmental Chemical Engineering, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Biomimetic solar evaporator for continuous clean water production with synergistic organic dye wastewater remediation - Peng Zhao; Jialu Xu; Jiakai Li; Meng Xia; Tao Yang; Guang Liu; Jiahui Yu; Qi Chen; Yijun Shen; Meng Li; Dong Wang; Juanxiu Xiao (Desalination, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

Synergistic effect of holey graphene and CoSe2-NiSe2 heterostructure to enhance fast Na-ion transport - Chong Xu; Kaiyi Chen; Jiahao Yang; Guang Ma; Ye Wang; Zizheng Zhou; Zhixuan Wu; Sai Che; Zechen Li; Yuxin Tu; Zhihua Xiao; Daqiang Jiang; et al. (Chemical Engineering Journal, 2024)

CoSe2-Modified multidimensional porous carbon frameworks as high-Performance anode for fast-Charging sodium-Ion batteries - Chong Xu; Jiahao Yang; Kaiyi Chen; Guang Ma; Ye Wang; Zechen Li; Zizheng Zhou; Zhixuan Wu; Sai Che; Changsheng Ding; Yongfeng Li (Chemical Engineering Journal, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

The receptor kinase OsANX limits precocious flowering and inflorescence over-branching and maintains pollen tube integrity in rice - Lan-Xin Zhang; Can-Can Shen; Ying-Xue Bai; Hao-Yue Li; Chen-Li Zhu; Chen-Guang Yang; Ammara Latif; Ying Sun; Cui-Xia Pu (Plant Science, 2024)

Influence of Chinese herbal plants on greenhouse gas emissions from pig manure composting and fermentation - Ya-jun Duan; Hong-sheng Wu; Guang-yao Chen; Feng-yi Hu; Yan-hui Li; Zhen-wei Li; Jin-he Chi; Dong-ming Lu; Xiao-ming Gu; Ming-chun Di (International Biodeterioration & Biodegradation, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Integrated analysis of the gonadal methylome and transcriptome provides new insights into the expression regulation of sex determination and differentiation genes in spotted scat (Scatophagus argus) - Kai-Zhi Jiao; Yu Li; Yuan-Qing Huang; Charles Brighton Ndandala; Gang Shi; Si-Ping Deng; Hong-Juan Shi; Hua-Pu Chen; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2024)

Curcumin inhibits PAT-induced renal ferroptosis via the p62/Keap1/Nrf2 signalling pathway - Jianan Zhai; Zhengguo Chen; Qi zhu; Zhifang Guo; Xiance Sun; Liping Jiang; Jing Li; Ningning Wang; Xiaofeng Yao; Cong Zhang; Haoyuan Deng; Shaopeng Wang; et al. (Toxicology, 2024)

Assessment of chlorine and hydrogen peroxide on airborne bacteria: Disinfection efficiency and induction of antibiotic resistance - Siyi Wang; Zhiwei Shao; Guang Chen; Bingjie Lin; Dan Li; Jianmin Chen (Journal of Hazardous Materials, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

Evolution of morphology, structure, and performance of the COF membranes with monomer concentrations: Enabling effective desalination and kinetics analysis - Li-ping Yue; Fan-xin Kong; Yi Wang; Guang-dong Sun; Ai-guo Zhou; Jin-fu Chen (Desalination, 2024)

Modeling and experimental verification for photodegradation in a spinning disk reactor - Zhi-Hao Li; Yan-Bin Li; Bao-Chang Sun; Guang-Wen Chu; Jian-Feng Chen (Chemical Engineering Journal, 2024)

Engineering Gluconbacter oxydans with efficient co-utilization of glucose and sorbitol for one-step biosynthesis of 2-keto-L-gulonic - Guang Li; Xuyang Wang; Weizhu Zeng; Zhijie Qin; Jianghua Li; Jian Chen; Jingwen Zhou (Bioresource Technology, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

Unveiling Turbulent Flow Dynamics in Blind-Tee Pipelines: Enhancing Fluid Mixing in Subsea Pipeline Systems - Fenghui Han; Qingyuan Lan; Yuxiang Liu; Guang Yin; Muk Chen Ong; Wenhua Li; Zhe Wang (Journal of Marine Science and Engineering, 2024)
Blind tees, as important junctions, are widely used in offshore oil and gas transportation systems to improve mixing flow conditions and measurement accuracies in curved pipes. Despite the significance of blind tees, their unsteady flow characteristics and mixing mechanisms in turbulent flow regimes are not clearly established. Therefore, in this study, Unsteady Reynolds-Averaged Navier–Stokes (URANS) simulations, coupled with Explicit Algebraic Reynolds Stress Model (EARSM), are employed to explore the complex turbulent flow characteristics within blind-tee pipes. Firstly, the statistical flow features are investigated based on the time-averaged results, and the swirl dissipation analysis reveals an intense dissipative process occurring within blind tees, surpassing conventional elbows in swirling intensity. Then, the instantaneous flow characteristics are investigated through time and frequency domain analysis, uncovering the oscillatory patterns and elucidating the mechanisms behind unsteady secondary flow motions. In a 2D-length blind tee, a nondimensional dominant frequency of oscillation (Stbt = 0.0361) is identified, highlighting the significant correlation between dominant frequencies inside and downstream of the plugged section, which emphasizes the critical role of the plugged structure in these unsteady motions. Finally, a power spectra analysis is conducted to explore the influence of blind-tee structures, indicating that the blind-tee length of lbt = 2D enhances the flow-mixing conditions by amplifying the oscillation intensities of secondary flow motions.

Catalytic hydroconversion of aryl ethers to polycyclic alkanes over Ni@MCM-41/β composite zeolite: Aromatic α-carbon activation and hydrogen transfer mechanisms - Guang-Hui Liu; Wen-Ao Shi; Jun Li; Han Wang; Ai-Min Wang; Yu-Hong Kang; Yong Gao; Ni Bai; Jie Kang; Chen Shi; Xian-Yong Wei (Fuel, 2024)

Comparative study of construction land development suitability assessment: Insights from multiple models and driving forces - Zhong Zhang; Jian Gong; Jingye Li; Jianxin Yang; Guang Chen; Yingjian Ren; Antonio Plaza (Environmental Impact Assessment Review, 2024)

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Biochar with enhanced performance prepared based on “graphite-structure regulation” conjecture designed to effectively control water pollution - Bolun Zhang; Yiping Jin; Jiacheng Lin; Ziyu Guo; Guang Chen; Yingjie Su; Xiaoxiao Yu; Shanshan Tang; Siji Chen; Jian Li (Science of The Total Environment, 2024)

Spatiotemporal carbon footprint and associated costs of wind power toward China's carbon neutrality - Ziwen Ruan; Xi Lu; Zihua Yin; Shawn C. Mobley; Chongyu Zhang; Jiaxing Wang; Yan Li; Zhaoyang Kong; Guang Shi; Dan Chen; Kebin He (Resources, Conservation and Recycling, 2024)

A novel spider venom peptide from the predatory mite Neoseiulus barkeri shows lethal effect on phytophagous pests - Li Chen; Michael J. Adang; Guang-Mao Shen (Pesticide Biochemistry and Physiology, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

Elucidating the interaction mechanism of rice glutelin and soybean 11S globulin using multi-spectroscopy and molecular dynamics simulation methods - Peng-yu Zhu; Chun-min Ma; Yang Yang; Xin Bian; Li-kun Ren; Bing Wang; Xiao-fei Liu; Feng-lian Chen; Guang Zhang; Na Zhang (Food Chemistry, 2024)

Microbial contribution to 14 biogenic amines accumulation in refrigerated raw and deep-fried hairtails (Trichiurus lepturus) - Hao Deng; Guang Wu; Lingyu Zhou; Xiaomei Chen; Li Guo; Senlin Luo; Qingchun Yin (Food Chemistry, 2024)

Evaluating combustion kinetics and quantifying fuel-N conversion tendency of shoe manufacturing waste - Guang Sun; Lin Li; Yuanqiang Duan; Yuqing Chen; Quanbin Gu; Yueming Wang; Zhenkun Sun; Junhua Mao; Xiaodong Qian; Lunbo Duan (Environmental Research, 2024)

Combined effects of binary mixtures of 17β-estradiol and testosterone in western mosquitofish (Gambusia affinis) after full life-cycle exposure - Chen-Si Wang; Gui-Zhen Fang; Xiao-Pei Li; Guo-Yong Huang; Lingtian Xie; Guang-Guo Ying (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Optimized dual-gas co-production from hydrate reservoirs with underlying gas through depressurization & well closure cycling: An experimental evaluation - Xian Sun; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Xing-Xun Li; Wei-Xin Pang; Qing-Ping Li; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Thermal conductivity of epoxy composites containing 3D honeycomb boron nitride filler - Guang Liu; Ao Ding; Pingfan Xu; Minmin Zhu; Haizhong Zhang; Yuying Zheng; Yaofa Luo; Li Zhang; Peikun Zhang; Aizheng Chen; Yuan Liu; Chao He (Chemical Engineering Journal, 2024)

Fingerprinting aeolian sediment sources in the Mu Us Sandy Land using the MixSIAR model - Guoxiang Chen; Guang Li; Aimin Liang; Zhibao Dong; Xiaokang Liu; Fang Ma; Min Cao; Junlin Yu; Mahran Sadiq (CATENA, 2024)

Systems metabolic engineering of Corynebacterium glutamicum to assimilate formic acid for biomass accumulation and succinic acid production - Kai Li; Xue Zhang; Cheng Li; Yu-Cheng Liang; Xin-Qing Zhao; Chen-Guang Liu; Anthony J. Sinskey; Feng-Wu Bai (Bioresource Technology, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

On the importance of angle-dependent hydrodynamic coefficients in the equilibrium configuration analysis of synthetic fiber towing ropes - Gen Li; Marek Jan Janocha; Guang Yin; Muk Chen Ong; Wenhua Li (Ocean Engineering, 2024)

Uncertainty quantification of vibro-acoustic coupling problems for robotic manta ray models based on deep learning - Yilin Qu; Zhongbin Zhou; Leilei Chen; Haojie Lian; Xudong Li; Zhongming Hu; Yonghui Cao; Guang Pan (Ocean Engineering, 2024)

Recent development of carrier materials in anthocyanins encapsulation applications: A comprehensive literature review - Ze Fu; Hao Ju; Guang-Sen Xu; Yan-Chao Wu; Xiao Chen; Hui-Jing Li (Food Chemistry, 2024)

Rapid and facile detection of largemouth bass ranavirus with CRISPR/Cas13a - Min Guang; Qian Zhang; Ruige Chen; Huaming Li; Mengran Xu; Xiaomin Wu; Rongrong Yang; HongBo Wei; Linzhu Ren; Liancheng Lei; Fuxian Zhang (Fish & Shellfish Immunology, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

Association of indoor solid fuel pollution with risk factors for cardiovascular disease among Chinese adults: A nationally multi-center study - Wenming Shi; Yongzhen Li; Yonggang Huang; Guang Huang; Changbo Jin; Jie Chen; Kun Gao (Building and Environment, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Microbial consortium degrading of organic pollutants: Source, degradation efficiency, pathway, mechanism and application - Huixiong Lü; Jia-Lu Wei; Guang-Xuan Tang; Yao-Si Chen; Yu-Hong Huang; Ruiwen Hu; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Cleaner Production, 2024)

TFN nanofiltration membrane incorporating ZIF-8@MXene for efficient removal ReO4- from simulated nuclear-contaminated wastewater - Ning-xiao Wei; Yu-xing Wang; Hua-li Chen; Li-guang Wu; Ting Wang (Journal of Environmental Chemical Engineering, 2024)

A review of combined fouling on high-pressure membranes in municipal wastewater reuse: Behaviors, mechanisms, and pretreatment mitigation strategies - Xiao-Yang Liu; Yu-Bo Chen; Jie Fu; Xianzheng Zhu; Long-Yi Lv; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemical Engineering Journal, 2024)

Vectorial integer bootstrapping of best integer equivariant estimation (VIB-BIE) for efficient and reliable GNSS ambiguity resolution - Weikai Miao; Bofeng Li; Yang Gao; Guang’e Chen (Journal of Geodesy, 2024)

Nitrogen enrichment decrease green roof multifunctionality - Guang Hao; Nan Yang; Xiaoqin Chen; Zhibo Du; Meiyang Li; Lei Chen; Hongyuan Li (Urban Forestry & Urban Greening, 2024)

Ca-high water recharge and mixing constrain on evolution and K enrichment of brine deposits in the evaporite basin: Case and analogue study in the Qaidam Basin, Qinghai-Tibet Plateau - Hualing Song; Qishun Fan; Qingkuan Li; Guang Han; Tianyuan Chen; Haotian Yang; Qi Wei (Journal of Hydrology, 2024)

Multifunctional Eu3+-MOF for simultaneous quantification of malachite green and leuco-malachite green and efficient adsorption of malachite green - Yi-Fan Xia; Hou-Qun Yuan; Chen Qiao; Wei Li; Ran Wang; Peiyao Chen; Yan-Xia Li; Guang-Ming Bao (Journal of Hazardous Materials, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

A novel unresolved/semi-resolved CFD-DEM coupling method for simulating undrained triaxial shear tests with flexible membranes - Jin-Hui He; Ming-Guang Li; Jin-Jian Chen (Computers and Geotechnics, 2024)

Enlightening thermoelectric mastery: Bio-inspired cellulose gel containing eco-friendly deep eutectic solvents - Yuxi Chen; Gonghua Hong; Lei Li; Qing Qu; Guang Li; Jiajie Wu; Lin Ge (Chemical Engineering Journal, 2024)

Co-immobilized multi-enzyme biocatalytic system on reversible and soluble carrier for saccharification of corn straw cellulose - Xiaoxiao Yu; Jianzhen Li; Yan Sun; Yubing Xie; Yingjie Su; Shanshan Tang; Sijia Bian; Liying Liu; Fei Huo; Qing Huang; Guang Chen (Bioresource Technology, 2024)

A mini broadband cavity enhanced absorption spectrometer for nitrogen dioxide measurement on the unmanned aerial vehicle platform - Zelong Zheng; Haichao Wang; Xiaorui Chen; Jie Wang; Xin Li; Keding Lu; Guang-He Yu; Xiaofeng Huang; Shaojia Fan (Atmospheric Environment, 2024)

Interaction of 17α-ethinylestradiol and methyltestosterone in western mosquitofish (Gambusia affinis) across two generations - Guo-Yong Huang; Gui-Zhen Fang; Wen-Jun Shi; Xiao-Pei Li; Chen-Si Wang; Hong-Xing Chen; Lingtian Xie; Guang-Guo Ying (Aquatic Toxicology, 2024)

CRL2APPBP2-mediated TSPYL2 degradation counteracts human mesenchymal stem cell senescence - Daoyuan Huang; Qian Zhao; Kuan Yang; Jinghui Lei; Ying Jing; Hongyu Li; Chen Zhang; Shuai Ma; Shuhui Sun; Yusheng Cai; Guibin Wang; Jing Qu; et al. (Science China Life Sciences, 2024)

Effect of SARS-CoV-2 infection in early pregnancy on placental development - Shanru Yi; Liping Wang; Mengting Wang; Wei Hong; Ben Xu; Xiaoying He; Mengtian Yang; Zhiping Wu; Beiying Wang; Guang Yang; Shijun Shen; Xinyu Cui; et al. (Science China Life Sciences, 2024)

Effects of landscape pattern on water quality at multi-spatial scales in Wuding River Basin, China - Chen’guang Zhao; Peng Li; Zixuan Yan; Chaoya Zhang; Yongxia Meng; Guojun Zhang (Environmental Science and Pollution Research, 2024)

Potential mechanisms of lung injury and repair after hexavalent chromium [Cr(VI)] aerosol whole-body dynamic exposure - Changmao Long; Zekang Su; Guiping Hu; Qiaojian Zhang; Yali Zhang; Tian Chen; Shiyi Hong; Li Su; Guang Jia (Chemosphere, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Associations of urinary zinc exposure with blood lipid profiles and dyslipidemia: Mediating effect of serum uric acid - Yunjiang Yu; Runan Chen; Zhenchi Li; Kai Luo; Mark Patrick Taylor; Chaojie Hao; Qian Chen; Yang Zhou; Hongxuan Kuang; Guocheng Hu; Xichao Chen; Hongyan Li; et al. (Science of The Total Environment, 2024)

The application of human-derived cell lines in neurotoxicity studies of environmental pollutants - Ming-Rui Li; Shu-Hui Men; Zi-Ye Wang; Chen Liu; Guo-Rui Zhou; Zhen-Guang Yan (Science of The Total Environment, 2024)

Reinitiation of modern-style plate tectonics in the Early Neoproterozoic: Evidence from a ∼930 Ma blueschist-facies terrane in South China - Li-Guang Wu; Yi Chen; Richard M. Palin; Qiu-Li Li; Lei Zhao; Yi-Bing Li; Chao-Feng Li; You-Lian Li; Xian-Hua Li (Precambrian Research, 2024)

Cationic ring-opening polymerization of natural thioctic acid to chemically recyclable and self-healable poly(thioctic acid) supramolecular material - Hang-Tian Zhang; Li-Ke Hou; Guang-Wen Chu; Jie-Xin Wang; Liang-Liang Zhang; Jian-Feng Chen (Chemical Engineering Journal, 2024)

Corrigendum to “Salecan confers anti-inflammatory effects in liver injury via regulating gut microbiota and its metabolites” [Carbohydrate Polymers. (2023) 120418] - Yanjun Liu; Panpan Li; Wenjie Pan; Juan Zhao; Chen Guang Olnood; Yuanfa Liu; Yong-Jiang Xu (Carbohydrate Polymers, 2024)

Diagenetic effects on strontium isotopes in shallow-water carbonate sediments from Middle Miocene to Recent - Xinran Chen; Mengchun Cao; Thomas J. Algeo; Na Li; Guang-yi Wei; Yi-bo Lin; Hua Zhang; Lei Xiang; Youhua Zhu; Changgui Xu; Caiwei Fan; Shuzhong Shen; et al. (Chemical Geology, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Prolonged Exposure to Plant Volatiles does not Significantly Affect Pban Expression and Mating Behavior in Diamondback Moth [Plutella Xylostella (Lepidoptera: Plutellidae)] - Houjun Tian; Ruibin Xu; Heng Li; Shuo Lin; Yixin Chen; Yong Chen; Guang Yang; Hui Wei (Journal of Chemical Ecology, 2024)

Dual-emissive Eu(III)-functionalized metal-organic frameworks for visual, rapid, and intelligent sensing of albendazole and albendazole sulfoxide in animal-origin food - Hou-Qun Yuan; Yi-Fan Xia; Yu-Fei Zhong; Wei Li; Hongda Zhu; Ran Wang; Peiyao Chen; Zhiming Gao; Xiangwei Zhu; Yan-Xia Li; Guang-Ming Bao (Analytica Chimica Acta, 2024)

Nitrogen (N) “supplementation, slow release, and retention” strategy improves N use efficiency via the synergistic effect of biochar, nitrogen-fixing bacteria, and dicyandiamide - Yingjie Su; Yanran Wang; Guoqing Liu; Zhongqing Zhang; Xiaoyu Li; Guang Chen; Zechang Gou; Qiang Gao (Science of The Total Environment, 2024)

Preparation of double-system imprinted polymer-coated multi-walled carbon nanotubes and their application in simultaneous determination of thyroid-disrupting chemicals in dust samples - Zhijia Zhuang; Danqi Cheng; Bin Han; Ruifang Li; Yang Shen; Mengyi Wang; Zhu Wang; Wenping Ding; Guang Chen; Yikai Zhou; Tao Jing (Science of The Total Environment, 2024)

Embryonic exposure of polystyrene nanoplastics affects cardiac development - Jingyan Li; Huimin Weng; Shuang Liu; Fan Li; Ke Xu; Shan Wen; Xi Chen; Chang Li; Yongmei Nie; Bin Liao; Jianming Wu; Fahsai Kantawong; et al. (Science of The Total Environment, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Influence of inner wall roughness of supersonic separator on non-equilibrium condensation of CO2 benefiting flue gas decarbonization - Jianan Chen; Tongsheng Wang; Anna Li; YuanYuan Gao; Zhu Huang; Wenming Jiang; Guang Xi (Journal of Cleaner Production, 2024)

Petrogenesis and implications for tin mineralization of the Beidashan granitic pluton, southern Great Xing'an Range, NE China: Constraints from whole-rock and accessory mineral geochemistry - Fei Yang; Guang Wu; Gongzheng Chen; Shihui Li; Yinglei Li; Tong Zhang; Yanjing Chen (Journal of Asian Earth Sciences, 2024)

Tandem mass spectrometry tag proteomic analysis of milk and colostrum of Guanzhong dairy goat - Chen Lu; Yu Mengqi; Yuan Yuxin; Qu Yingxin; Sha Riakang; Ren Xinyang; Li Guang (International Dairy Journal, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Arbuscular mycorrhizal symbiosis alleviates arsenic phytotoxicity in flooded Iris tectorum Maxim. dependent on arsenic exposure levels - Shuping Xing; Qihui Shen; Chuning Ji; Luhua You; Jinglong Li; Meng Wang; Guang Yang; Zhipeng Hao; Xin Zhang; Baodong Chen (Environmental Pollution, 2024)

Exposure to greenness during pregnancy and the first three years after birth and autism spectrum disorder: A matched case-control study in shanghai, China - Yan Chen; Gongbo Chen; Yuewei Liu; Guang-Hui Dong; Bo-Yi Yang; Shanshan Li; Hong Huang; Zhijuan Jin; Yuming Guo (Environmental Pollution, 2024)

Ochrobactrum chromiisoli sp. nov., Isolated from Chromium-Contaminated Soil - Yi Yang; Zhe Xu; Li Yang; Meng-yao Hu; Guang-yang Jiang; Jia Chen; Yi-chen Yang; Yongqiang Tian (Current Microbiology, 2024)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

Stress-induced collapse in horizontally layered rock and a yielding support strategy: A case study - Guang Huang; Jianbo Fei; Xiangsheng Chen; Fei Li (Tunnelling and Underground Space Technology, 2023)

Integrative application of biochar and arbuscular mycorrhizal fungi for enhanced chromium resistance in Medicago sativa - Jinglong Li; Gengxue Fu; Shuping Xing; Baodong Chen; Songlin Wu; Haiyan Feng; Guang Yang; Yaoyu Zhou; Xin Zhang (Science of The Total Environment, 2023)

Assembling the Proto-Yangtze Block in the late Paleoproterozoic: Constraints from a refined Magmatic-Metamorphic framework of the Cuoke Complex, SW China - Zhao Yang; Peter A. Cawood; Jian-Wei Zi; Gui-Chun Liu; Guang-Yan Chen; Tian-Yu Zhao; Jing Li (Precambrian Research, 2023)

Enhanced the formation kinetics of CO2 hydrate using graphene oxide and L-methionine - Shi-Dong Zhou; Yan-Yun Xiao; Chen-Qing Xia; Guang-Xin Liu; Xiao-Yan Li; Xing-Ya Ni; Yang Liu; Xiao-Fang Lv (Journal of Cleaner Production, 2023)

Review on the gentle hydrometallurgical treatment of WPCBs: Sustainable and selective gradient process for multiple valuable metals recovery - Xi-guang Li; Qiang Gao; Si-qi Jiang; Chun-chen Nie; Xiang-nan Zhu; Tian-tian Jiao (Journal of Environmental Management, 2023)

Deciphering the impacts of chromium contamination on soil bacterial communities: A comparative analysis across various soil types - Chuning Ji; Jiu Huang; Jinglong Li; Xuemeng Zhang; Guang Yang; Youran Ma; Zhipeng Hao; Xin Zhang; Baodong Chen (Journal of Environmental Management, 2023)

Numerical investigation of the effects of compressibility of gassy groundwater (CGG) on the performance of deep excavations in Shanghai soft deposits - Jia-Bin Li; Ming-Guang Li; Hao-Biao Chen; Jin-Jian Chen (Engineering Geology, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Transformation from Knudsen diffusion to facilitated diffusion for CO2 in confined mass transfer channels of polyimide mixed matrix membranes - Ting Wang; Ke Zhang; Shi-wen Du; Li-guang Wu; Chun-juan Li; Hua-li Chen; Hai-Chang Guo (Chemical Engineering Journal, 2023)

Hidden dangers of ice avalanches and glacier lake outburst floods on the Tibetan Plateau: identification, inventory, and distribution - Minggao Tang; Qiang Xu; Lina Wang; Huanle Zhao; Guangjian Wu; Jian Zhou; Guang Li; Wenjing Cai; Xu Chen (Landslides, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Production of all-male non-transgenic zebrafish by conditional primordial germ cell ablation - Fang Wang; Yong-Yong Feng; Xu-Guang Wang; Mi Ou; Xin-Cheng Zhang; Jian Zhao; Kun-Ci Chen; Kai-Bin Li (Fish Physiology and Biochemistry, 2023)

Reference Intervals for Thyroid Hormones and Thyroid Volume in Children Aged 7 ~ 13 Years from Iodine-Sufficient Areas in Tianjin, China - Yushan Cui; Yang Wang; Dandan Zhang; Yani Duan; Fang Li; Wenfeng Li; Lu Chen; Guang Jia (Biological Trace Element Research, 2023)

Influence of Air Pollution Exposures on Cardiometabolic Risk Factors: a Review - Li-Hao Guo; Mohammed Zeeshan; Guo-Feng Huang; Duo-Hong Chen; Min Xie; Jun Liu; Guang-Hui Dong (Current Environmental Health Reports, 2023)

Numerical investigation of blind-tee effect on flow mixing in double-bend combinations - Yuxiang Liu; Fenghui Han; Guang Yin; Muk Chen Ong; Wenhua Li; Zhe Wang (Ocean Engineering, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

Insecticidal effect of green walnut husks and its active basis digesting targeting to insect phenoloxidase using UPLC-Q-TOF-MS coupled with PLS analysis - Qiao Gao; Wen-Xian Du; Si-Tong Lv; Yi Li; Shi-An Meng; Guang Chen (Phytoparasitica, 2023)

Human activities further amplify the cooling effect of vegetation greening in Chinese drylands - Yixuan Zhu; Yangjian Zhang; Yan Li; Zhoutao Zheng; Guang Zhao; Yihan Sun; Jie Gao; Yao Chen; Jianshuang Zhang; Yu Zhang (Agricultural and Forest Meteorology, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Comparative analysis of different metabolites in semen of Guanzhong dairy goats with different motility rates - Yuxin Yuan; Mengqi Yu; Lu Chen; Xinyang Ren; Yingxin Qu; Akang Shari; Guang Li (Theriogenology, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Surface characteristic driven in waste printed circuit boards flotation: Floatability mechanism of resin and glass fiber in non-metallic component - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xian-jun Lyu; Ya-qing Zhang; Xiang-nan Zhu (Process Safety and Environmental Protection, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Culturable and inhalable airborne bacteria in a semiunderground municipal wastewater treatment plant: Distribution, transmission, and health risk assessment - Xiang Zhang; Bingjie Lu; Guang Chen; Lihua Wang; Bingjie Lin; Zhengliang Peng; Songliu Lu; Dan Li; Jianmin Chen (Journal of Hazardous Materials, 2023)

Outdoor environmental exposome and the burden of tuberculosis: Findings from nearly two million adults in northwestern China - Jia-Xin Li; Qiyun Luan; Beibei Li; Shyamali C. Dharmage; Joachim Heinrich; Michael S. Bloom; Luke D. Knibbs; Igor Popovic; Li Li; Xuemei Zhong; Aimin Xu; Chuanjiang He; et al. (Journal of Hazardous Materials, 2023)

Phosphoramidic acid functionalized silica microspheres for simultaneous removal of Cr(VI), As(V) and Se(VI) from aqueous solutions based on molecular geometry match - Shiqi Liang; Wenmei Jiao; Dingyi Zhang; Hu Zhang; Rongrong Qiao; Haozhe Liu; Meng Wang; Yu Chen; Meng Zou; Yan Huang; Wenhui Guo; Lei Li; et al. (Journal of Environmental Chemical Engineering, 2023)

Neoproterozoic crustal growth and reworking in South Qinling, central China: Evidence from zircon U-Pb age and Hf isotopic composition of paragneiss in the Foping dome - He Zhang; Jun He; Yan-Chen Li; Guang-Hui Wu; Hong Cheng; Fukun Chen (Journal of Asian Earth Sciences, 2023)

Fungal strain improvement for efficient cellulase production and lignocellulosic biorefinery: Current status and future prospects - Jie Yang; Hou-Ru Yue; Li-Ya Pan; Jia-Xun Feng; Shuai Zhao; Surisa Suwannarangsee; Verawat Champreda; Chen-Guang Liu; Xin-Qing Zhao (Bioresource Technology, 2023)

Developing high-dimensional machine learning models to improve generalization ability and overcome data insufficiency for mixed sugar fermentation simulation - Xiao-Yan Huang; Tian-Jie Ao; Xue Zhang; Kai Li; Xin-Qing Zhao; Verawat Champreda; Weerawat Runguphan; Chularat Sakdaronnarong; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2023)

Assessing the urban heat island effect of different local climate zones in Guangzhou, China - Guang Chen; Yiqi Chen; Xiao Tan; Lihua Zhao; Yunnan Cai; Li Li (Building and Environment, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Bufalin targeting BFAR inhibits the occurrence and metastasis of gastric cancer through PI3K/AKT/mTOR signal pathway - Guang Chen; Huhu Zhang; Hongxiao Sun; Xiaoyan Ding; Guoxiang Liu; Fanghao Yang; Guilin Feng; Xiaolei Dong; Yunfan Zhu; Xiaotong Wang; Yafei Wang; Bing Li; et al. (Apoptosis, 2023)

Chemical constituents of Aspergillus udagawae isolated from the soil of the Xingren coal areas and their antibacterial activities - Xing-Mei Long; Qin-Feng Zhu; Bing Wang; Guang-Gui Chen; Kai-Yu Li; Xun He; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2023)

A generalized land surface reflectance reconstruction method for aerosol retrieval: Application to the Particulate Observing Scanning Polarimeter (POSP) onboard GaoFen-5 (02) satellite - Zheng Shi; Yisong Xie; Zhengqiang Li; Ying Zhang; Cheng Chen; Linlu Mei; Hua Xu; Haofei Wang; Yang Zheng; Zhenhai Liu; Jin Hong; Mengyao Zhu; et al. (Remote Sensing of Environment, 2023)

Diverse diterpenoids from Callicarpa rubella Lindl. as natural inhibitors of macrophage foam cell formation - Xue-Wen Wu; Qian-Lang Feng; Yi-Fan Xie; Si-Chen Song; Bin Cheng; Yan Ma; Qing Li; Xu Ji; Xiao-Li Li; Guang Cao; Wei-Lie Xiao (Phytochemistry, 2023)

Geochemical characteristics of the Chang 7 Member in the southwestern Ordos Basin, China: the influence of sedimentary environment on the organic matter enrichment - Chen Li; Shi-Jia Chen; Jian-Bo Liao; Yu-Ting Hou; Jian Yu; Guang-Lin Liu; Kun Xu; Xue-Ting Wu (Palaeoworld, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

A novel machine learning-based model predictive control framework for improving the energy efficiency of air-conditioning systems - Sihao Chen; Puxian Ding; Guang Zhou; Xiaoqing Zhou; Jing Li; Liangzhu (Leon) Wang; Huijun Wu; Chengliang Fan; Jiangbo Li (Energy and Buildings, 2023)

An advanced SRR catalyst based on hollow polyhedral carbon skeleton modified by Tri-metal (Zn, Co, Fe) for Li-S batteries - Xi Zhou; Xuelin Huang; Guang Li; Peng Zeng; Xiaolin Liu; Hong Liu; Manfang Chen; Xianyou Wang (Chemical Engineering Journal, 2023)

Efficient production of 2-keto-L-gulonic acid from D-glucose in Gluconobacter oxydans ATCC9937 by mining key enzyme and transporter - Guang Li; Dong Li; Weizhu Zeng; Zhijie Qin; Jian Chen; Jingwen Zhou (Bioresource Technology, 2023)

Microbial metabolism and humic acid formation in response to enhanced copper and zinc passivation during composting of wine grape pomace and pig manure - Yingchao Zhang; Yang Xu; Xinlong Yu; Jinkang Li; Guang Chen; Shuaijie Wang; Yanping Xu; Rui Xu; Baohai Zhang; Hongqiong Zhang (Bioresource Technology, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Combining InSAR and infrared thermography with numerical simulation to identify the unstable slope of open-pit: Qidashan case study, China - Yu Lu; Changyu Jin; Qiang Wang; Tao Han; Guang Li; Xiaoyu Zhong; Guoqing Chen (Landslides, 2023)

Synthesis and anti‐parasites efficacy of coumarin derivatives against Dactylogyrus intermedius - Guang‐Lu Liu; Hui Zhang; Li‐Li Zhu; Xu‐Dong Liu; Yan‐Jie Liu; Ya‐hong Chen; Lei Liu; Yang Hu (Journal of Fish Diseases, 2023)
Dactylogyrus is one of the most common parasitic diseases in fish and causes huge losses to the aquaculture industry. With the advantages of safety, low toxicity and easy degradation, plant‐derived drugs are ideal for the creation of green aquatic ingredients. The use of plant‐derived drugs in aquaculture is limited by their low content and high processing costs, which is a challenge that can be solved by the chemical synthesis of plant‐derived drugs. Eleven new coumarin derivatives were synthesized and assessed for their anthelmintic activity in this study. Among them, the derivative 7‐((1‐tosyl‐1H‐1,2,3‐triazol‐4‐yl)methoxy)‐2H‐chromen‐2‐one (N11) has good anthelmintic activity and its mean anthelmintic efficacy against D. intermedius at a concentration of 10 μM reached 99.84%, which is even better than the anthelmintic activity of the positive control mebendazole. Further studies showed that N11 had concentration values of 3.31 and 1.94 μM for 50% maximal effect (EC 50 ) against D. intermedius at 24 and 48 h, respectively. Furthermore, scanning electron microscopy revealed that N11 caused damage to D. intermedius . What is more noteworthy is that a substantial reduction in the ATP content of the parasite was observed following in vitro and in vivo administration of N11. Moreover, it was also found that N11 was able to inhibit the horizontal transmission of D. intermedius . Furthermore, real‐time quantitative PCR analysis was utilized to determine the expression profile of genes associated with anti‐inflammatory cytokines (IL‐10 , TGF‐β and IL‐4 ) in goldfish. In all examined organs, it was observed that the expression of anti‐inflammatory cytokines increased subsequent to treatment with N11, according to the results. Thus, these results all suggest that N11 possesses good anthelmintic activity and is a potentially effective agent for the control of D. intermedius .

Spatiotemporal dynamics, traceability analysis, and exposure risks of antibiotic resistance genes in PM2.5 in Handan, China - Qing Wang; Shengjuan Yang; Shaojing Sun; Litao Wang; Guang Yang; Jinghui Luo; Yan Sun; Xuli Li; Na Wang; Bin Chen (Environmental Science and Pollution Research, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Understanding grain virtual water flux dynamics and drivers from a socio-ecohydrological perspective: A case study of landlocked developing countries of Africa - Hubert Hirwa; Fadong Li; Simon Measho; Gang Chen; Fabien Muhirwa; Qiuying Zhang; Alphonse Kayiranga; Yunfeng Qiao; Peifang Leng; Chao Tian; Guang Yang; Jean Baptiste Baranyika; et al. (Journal of Cleaner Production, 2023)

Synthesis of novel magnetic pitch-based hypercrosslinked polymers as adsorbents for effective recovery of Ag+ with high selectivity - Qi Peng; Hongwei Zhao; Guang Chen; Qilin Yang; Xinxiu Cao; Shaohui Xiong; Anguo Xiao; Gen Li; Bo Liu; Qingquan Liu (Journal of Environmental Management, 2023)

Dual-gas co-production behavior for hydrate-bearing coarse sediment with underlying gas via depressurization under constrained conditions - Xian Sun; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Xing-Xun Li; Wei-Xin Pang; Qing-Ping Li; Chang-Yu Sun; Guang-Jin Chen (Gas Science and Engineering, 2023)

Endocrine disruptor responses in the embryos of marine medaka (Oryzias melastigma) after exposure to aged plastic leachates - Shu-Qing Qiu; Guo-Yong Huang; Xiao-Pei Li; Dong-Qiao Lei; Chen-Si Wang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Characteristics of atmospheric carbonyls pollution in winter around petrochemical enterprises over North China - Jin-he Wang; Ou-yang Li; Xue Yang; Guang Pan; Guo-lan Fan; Hou-yong Zhang; Zhi-yong Xia; Xiao-yan Sun; Hong-yu Xu; Yan-jun Chen; Chao Zhu (Air Quality, Atmosphere & Health, 2023)

Insights into the release of triclosan from microplastics in aquatic environment assessed with diffusive gradient in thin-films - Si-Si Liu; Yu-Wei Jia; Xiao-Yuan Guo; Jian-Liang Zhao; Yue Gao; Andy J. Sweetman; Guang-Guo Ying; Li Xu; Chen Tu; Chang-Er Chen (Science of The Total Environment, 2023)

Unprecedented spirodioxynaphthalenes from the endophytic fungus Phyllosticta ligustricola HDF-L-2 derived from the endangered conifer Pseudotsuga gaussenii - Hao-Wei Chen; Chun-Xiao Jiang; Guang-Lei Ma; Xi-Ying Wu; Wei Jiang; Jiyang Li; Yi Zang; Jia Li; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2023)

Experimental and numerical investigation on the dynamic behavior of two partially overlapped identical plates submerged in water - Ming Zhang; David Valentín; Carme Valero; Qing-guang Chen; Xianchang Li (Ocean Engineering, 2023)

Effects of combined chickpea protein isolate and chitosan on the improvement of technological quality in phosphate-free pork meat emulsions: Its relation to modifications on protein thermal and structural properties - Yu Wang; Jing-jing Yuan; Ke Li; Jia-le Wang; Jun-guang Li; Bo Chen; Yan-hong Bai (Meat Science, 2023)

The association between long-term exposure to outdoor artificial light at night and poor sleep quality among Chinese veterans: A multi-city study - Xinyi Sun; Jiping Tan; Yan Chen; Yuewei Liu; Guang-Hui Dong; Bo-Yi Yang; Nan Li; Luning Wang; Shanshan Li; Gongbo Chen; Yuming Guo (International Journal of Hygiene and Environmental Health, 2023)

In-doping induced resonant level and thermoelectric performance enhancement in n-type GeBi2Te4 single crystals with intrinsically low lattice thermal conductivity - Peng Chen; Bin Zhang; Hanjun Zou; Xiangnan Gong; Yanci Yan; Jingwei Li; Daliang Zhang; Guang Han; Xu Lu; Hong Wu; Yun Zhou; Xiaoyuan Zhou; et al. (Chemical Engineering Journal, 2023)

Spatial distribution of planktonic ciliates in waters around the northeastern Antarctic Peninsula and the South Orkney Plateau - Haibo Li; Chen Liang; Guang Yang; Chaofeng Wang; Wuchang Zhang (Polar Biology, 2023)

Inhibition of Foxp4 Disrupts Cadherin-based Adhesion of Radial Glial Cells, Leading to Abnormal Differentiation and Migration of Cortical Neurons in Mice - Xue Li; Shimin Zou; Xiaomeng Tu; Shishuai Hao; Tian Jiang; Jie-Guang Chen (Neuroscience Bulletin, 2023)

An assessment of the simulation of East-Asia precipitation in the high-resolution community earth system model - Guang Yang; Mingkui Li; Shaoqing Zhang; Yishuai Jin; Chenyu Zhu; Zhaoying Wang; Xiaolin Yu; Hong Wang; Yuhu Chen (Climate Dynamics, 2023)

Genetic diversity and the population structure of Monochoria korsakowii in Japan revealed by nuclear simple sequence repeat (SSR) markers - Wei Jiang; Yuanyuan Chen; Shiping Liu; Hiroto Tamura; Wei Li; Guang-Xi Wang (Aquatic Botany, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Multistage metallogeny and tectonic evolution in eastern NE China and adjacent Russian Far East: geochronology, geochemistry, and Sr-Nd-Hf isotope perspectives - Qing-Fei Sun; Yi-Cun Wang; Ke-Yong Wang; Feng-Yue Sun; Chun-Kit Lai; Chen-Guang Zhao; Li-Xue Sun (International Geology Review, 2023)

Selective extraction of gold from strong acid E-waste leachate through H+-triggered cascade reaction of thiolated β-cyclodextrin - Difan Fang; Feihu Bi; Liming Yang; Wenbin Hu; Zan Hua; Hanchen Wei; Changli Chen; Yunyun Tu; Penghui Shao; Min Li; Xubiao Luo; Guang Yang (Resources, Conservation and Recycling, 2023)

Holocene warming trend based on peat brGDGTs records from southeastern humid to northwestern arid China - Shikai Wei; Zhiguo Rao; Jiantao Cao; Guodong Jia; Yunxia Li; Haichun Guo; Zixian Feng; Kaiyue Guang; Qianqian Qin; Yiping Tian; Jiayan Li; Siqi Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Mariculture affects antibiotic resistome and microbiome in the coastal environment - Lu-Xi He; Liang-Ying He; Fang-Zhou Gao; Min Zhang; Jun Chen; Wei-Li Jia; Pu Ye; Yu-Wei Jia; Bai Hong; Si-Si Liu; You-Sheng Liu; Jian-Liang Zhao; et al. (Journal of Hazardous Materials, 2023)

In-situ mechanochemically tailorable 2D gallium oxyselenide for enhanced optoelectronic NO2 gas sensing at room temperature - Tao Tang; Zhong Li; Yin Fen Cheng; Hua Guang Xie; Xuan Xing Wang; Yong Li Chen; Liang Cheng; Yi Liang; Xin Yi Hu; Chu Manh Hung; Nguyen Duc Hoa; Hao Yu; et al. (Journal of Hazardous Materials, 2023)

Chromium and iron recovery from hazardous extracted vanadium tailings via direct reduction magnetic separation - Jianfa Jing; Yufeng Guo; Shuai Wang; Guang Li; Feng Chen; Lingzhi Yang; Chao Wang (Journal of Environmental Chemical Engineering, 2023)

Effect of diffuser on condensing flow in nozzles for carbon capture - Jianan Chen; Anna Li; Zhu Huang; Guang Xi; Wenming Jiang (Fuel, 2023)

Experimental study on coal combustion by using the ilmenite ore as active bed material in a 0.3 MWth circulating fluidized bed - Lin Li; Junhua Mao; Wu Tang; Guang Sun; Quanbin Gu; Xiaoyan Lu; Ke Shao; Yuqing Chen; Lunbo Duan (Fuel, 2023)

Engineering Corynebacterium glutamicum for efficient production of succinic acid from corn stover pretreated by concentrated-alkali under steam-assistant conditions - Kai Li; Cheng Li; Xin-Qing Zhao; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2023)

Multiple Episodes of Zircon Growth during Anatectic Metamorphism of Metasedimentary Rocks in Collisional Orogens: Constraints from Felsic Granulites in the Bohemian Massif - Guang Yang; Ren-Xu Chen; Yong-Fei Zheng; Qiong-Xia Xia; Yong-Jie Yu; Kun Li; Zhaochu Hu; Bing Gong; Xiang-Ping Zha (Journal of Earth Science, 2023)

Geostatistical inversion method based on seismic waveform similarity - Xue-Bin Ni; Jia-Jia Zhang; Kang Chen; Guang-Zhi Zhang; Bao-Li Wang; Zhuo-Fan Liu; Ying Lin (Applied Geophysics, 2023)

Hashimoto’s encephalopathy with interesting neuroimaging performance: a case report - Cao Li; Guang-cai Tang; Guang-xiang Chen (Acta Neurologica Belgica, 2023)

The distribution and emission of CO2, CH4 and light hydrocarbons in an anticyclonic eddy of the Kuroshio extension - Xiao-Jun Li; Jian Wang; Hao Qiao; Rui-Chen Zhu; Hong-Hai Zhang; Zhao-Hui Chen; Andrew Montgomery; Shan Zheng; Guang-Chao Zhuang (Frontiers in Marine Science, 2023)
Mesoscale eddies are energetic and swirling circulations that frequently occur in the open ocean. The effects of mesoscale eddies on the biogeochemical cycling of climate-relevant gases remain poorly constrained. We investigated the distribution and air-sea fluxes of CO 2 , methane, and five non–methane hydrocarbons (NMHCs) in an anticyclone eddy of Kuroshio Extension during September 2019. Within eddy core, intense stratification hindered the replenishment of nutrients and favored the growth of small-size phytoplankton, such as Prochlorococcus . Seawater pCO 2 decreased from 406.1 μatm at the eddy outside to 377.5 μatm at the eddy core, accompanied by a decrease in surface seawater temperature from 26.7 °C to 25.2 °C. The vertical distribution of methane (0.3-9.9 nmol L -1 ) was influenced by the eddy process, with a maximum at 80 m in the eddy core, which might be attributed to the degradation of phosphonates sustained by Prochlorococcus . The concentrations of five NMHCs (ethane, ethylene, propane, propylene, and isoprene) ranged from 17.2-126.2, 36.7-168.1, 7.5-29.2, 22.6-64.1, 54.5-172.1, 3.5-27.9 pmol L -1 , respectively. Isoprene correlated well with Chl- a concentrations at the eddy core, while no significant correlation was observed at the eddy outside. Air-sea fluxes of CO 2 and isoprene associated with the eddy core were higher than those of the eddy outside, while the maximum ventilation of methane and other NMHCs (ethane, ethylene, propane, and propylene) was found at the eddy outside. Collectively, physical processes such as eddies impact the production and distribution of light hydrocarbons in seawater and further influence their regional emissions to the atmosphere.

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

An extended SW-TES algorithm for land surface temperature and emissivity retrieval from ECOSTRESS thermal infrared data over urban areas - Chen Ru; Si-Bo Duan; Xiao-Guang Jiang; Zhao-Liang Li; Cheng Huang; Meng Liu (Remote Sensing of Environment, 2023)

Capturing the hierarchically assorted modules of protein–protein interactions in the organized nucleome - Shuaijian Dai; Shichang Liu; Chen Zhou; Fengchao Yu; Guang Zhu; Wenhao Zhang; Haiteng Deng; Al Burlingame; Weichuan Yu; Tingliang Wang; Ning Li (Molecular Plant, 2023)

Effect of shock wave on nucleation and droplet growth of CO2 in flue gas in supersonic separators - Jianan Chen; Anna Li; Zhu Huang; Wenming Jiang; Guang Xi (Gas Science and Engineering, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Effect of residual guest concentration in aqueous solution on hydrate reformation kinetics - Xiao-Hui Wang; Xiao-Jie Xu; Jin Cai; Hua-Xing Zheng; Xing-Xun Li; Wei-Xin Pang; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2023)

Distinct tectono-magmatism on the margins of Rodinia and Gondwana - Guang-Hui Wu; Xu Chu; Ming Tang; Weiyong Li; Fukun Chen (Earth and Planetary Science Letters, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Degree of ontogenetic diet shift and trophic niche partitioning of Euphausia superba and Thysanoessa macrura are influenced by food availability - Zhipeng Pang; Xupeng Chi; Zhihui Song; Haibo Li; Yunyan Chen; Guang Yang (Journal of Oceanology and Limnology, 2023)

Resin glycosides from Merremia hederacea with multidrug-resistant reversal activities - Chen-Yue Li; Jie Fang; Guang-Yao Li; Wen-Qiong Wang; Li-Jiang Xuan (Phytochemistry Letters, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

White light and long persistent luminescence from metal cluster-based metal-organic frameworks - Zheng Wang; Jia-Jia Liu; Meng-Yang Li; Guang Chen (Chemical Engineering Journal, 2023)

Characteristics, chemical transformation and source apportionment of volatile organic compounds (VOCs) during wintertime at a suburban site in a provincial capital city, east China - BaoLin Wang; ZhenGuo Liu; ZiAng Li; YuChun Sun; Chen Wang; ChuanYong Zhu; Lei Sun; Na Yang; Ge Bai; GuoLan Fan; XiaoYan Sun; ZhiYong Xia; et al. (Atmospheric Environment, 2023)

Exposure to estrone disrupts the endocrine system of western mosquitofish (Gambusia affinis) - Dong-Qiao Lei; Guo-Yong Huang; Shu-Qing Qiu; Xiao-Pei Li; Chen-Si Wang; Gui-Zhen Fang; Lingtian Xie; Guang-Guo Ying (Aquatic Toxicology, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Investigation of insecticidal activity of two Rhododendron species on stored-product insects - Yu-Li Sang; Lu Dai; Pei Wang; Li-Jiang Chen; Mei-Ling Jiao; Jing-Yu Liu; Nai-Zhi Zhang; Guang-Wen Fan; Yan-Jun Hao; Xiu-Lan Wang (Journal of Plant Diseases and Protection, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Associations between trace level thallium and multiple health effects in rural areas: Chinese Exposure and Response Mapping Program (CERMP) - Yun-Jiang Yu; Zhen-Chi Li; Yang Zhou; Chen-Yin Dong; Hong-Xuan Kuang; Tong Zheng; Ming-Deng Xiang; Xi-Chao Chen; Hong-Yan Li; Xiao-Wen Zeng; Shu-Li Xu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

A comparative study on endocrine disrupting effects of leachates from virgin and aged plastics under simulated media in marine medaka larvae (Oryzias melastigma) - Shu-Qing Qiu; Guo-Yong Huang; Xiao-Pei Li; Dong-Qiao Lei; Chen-Si Wang; Guang-Guo Ying (Journal of Hazardous Materials, 2023)

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

Physiological and transcriptomic evidence of antioxidative system and ion transport in chromium detoxification in germinating seedlings of soybean - Guang Chen; Jian Wang; Guoxin He; Sujuan Li; Xuetong Li; Xiaoyuan Tao; Shuang Liang; Fenglin Deng; Fanrong Zeng; Zhong-Hua Chen; Shengchun Xu (Environmental Pollution, 2023)

Involvement of purinergic P2Y1R in antidepressant-like effects of electroacupuncture treatment on social isolation stress mice - Lingling Yu; Yao Wang; Hong Zhang; Man Li; Guang Chen; Jiahuan Hao; Minjie Xie (Purinergic Signalling, 2023)

Multiplex signal amplification strategy-based early-stage diagnosis of Parkinson's disease on a SERS-enabled LoC system - Shengjie Ge; Gaoyang Chen; Jialin Deng; Yuexing Gu; Yu Mao; Xinyu Zhou; Guang Li (Analytica Chimica Acta, 2023)

Cold Dome Affects Mesozooplankton Communities during the Southwest Monsoon Period in the Southeast East China Sea - Yan-Guo Wang; Li-Chun Tseng; Xiao-Yin Chen; Rou-Xin Sun; Peng Xiang; Bing-Peng Xing; Chun-Guang Wang; Jiang-Shiou Hwang (Journal of Marine Science and Engineering, 2023)
In order to better understand the cold dome influence on zooplankton community structure, zooplankton samples were collected during the southwest monsoon prevailing period from the southeast waters of the East China Sea. To reduce the bias caused by different sampling months, the samples were collected in June 2018 and in June 2019. An obvious cold dome activity was proven by images of remote sensing satellites during the June 2018 cruise. In contrast, the research area was much affected by open sea high temperature and water masses during the June 2019 cruise. Significant differences in water conditions were demonstrated by surface seawater temperature, salinity, and dissolved oxygen concentrations between the two cruises. Nevertheless, no significant differences were observed concerning mesozooplankton in general, copepods, large crustaceans, other crustaceans, and pelagic molluscs between the June 2018 and June 2019 cruises. However, the mean abundance of gelatinous plankton was significantly different with 1213.08 ± 850.46 (ind./m3) and 2955.93 ± 1904.42 (ind./m3) in June 2018 and June 2019, respectively. Noteworthy, a significantly lower mean abundance of meroplankton, with 60.78 ± 47.32 (ind./m3), was identified in June 2018 compared to 464.45 ± 292.80 (ind./m3) in June 2019. Pearson’s correlation analysis also showed a highly positive correlation of gelatinous plankton and meroplankton with sea surface temperature (p

High-resolution distribution and emission of dimethyl sulfide and its relationship with pCO2 in the Northwest Pacific Ocean - Shi-Bo Yan; Xiao-Jun Li; Feng Xu; Hong-Hai Zhang; Jian Wang; Yueqi Zhang; Gui-Peng Yang; Guang-Chao Zhuang; Zhaohui Chen (Frontiers in Marine Science, 2023)
Ocean-derived dimethyl sulfide (DMS) is widely concerning because of its hypothesized influence on global climate change. This study aims to explore the distribution characteristics and influencing factors of DMS and partial pressure of carbon dioxide ( p CO 2 ) in the Northwest Pacific Ocean, as well as the potential relationship between DMS and p CO 2 . A high-resolution, underway, shipboard measurement device was used to determine the DMS and p CO 2 of the surface seawater and atmosphere in the Northwest Pacific and its marginal seas during November 2019. The result show that atmospheric and surface seawater DMS concentrations ranged from 3 to 125 pptv and 0.63 to 2.28 nmol L -1 , respectively, with mean values of 46 ± 19 pptv and 1.08 ± 0.34 nmol L -1 . The average sea surface p CO 2 was 371 ± 16 μatm (range from 332 to 401 μatm). The trends in the surface seawater DMS in different current systems were primarily associated with phytoplankton abundance and composition. Biological activity and physical processes such as cooling jointly influenced the sea surface p CO 2 . A cold eddy along the transect in the Northwest Pacific Ocean increased DMS at the sea surface by 10% and CO 2 uptake by 3%. We found a significant negative correlation between DMS and p CO 2 in the Northwest Pacific Ocean at the 0.1° resolution [DMS] seawater = -0.0161[ p CO 2 ] seawater + 7.046 (R 2 = 0.569, P < 0.01). The DMS and p CO 2 sea-air fluxes were estimated to range from 0.04 to 25.3 μmol m -2 ·d -1 and from -27.0 to 4.22 mmol m -2 ·d -1 throughout the survey area. The Northwest Pacific Ocean, especially the Oyashio Current, is an important sink of CO 2 and a source of DMS.

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

Study on comparative analysis of differential metabolites in Guanzhong dairy goat semen before and after freezing - Yuxin Yuan; Guang Wang; Jiahao Zou; Yongtao Zhang; Dexian Li; Mengqi Yu; Lu Chen; Guang Li (Theriogenology, 2023)

Enhancements of dissociation of electrode materials in spent lithium-ion batteries by low-temperature heating pretreatment - Si-qi Jiang; Chun-chen Nie; Shun-xiang Shi; Yong-qiang Zhao; Xiang-guang Li; Chao-zhu Deng; Lu Yang; Ling Zhang; Xiang-nan Zhu (Process Safety and Environmental Protection, 2023)

Numerical simulation of carbon separation with shock waves and phase change in supersonic separators - Jianan Chen; Zhu Huang; Anna Li; Ran Gao; Wenming Jiang; Guang Xi (Process Safety and Environmental Protection, 2023)

Eudesmane−type sesquiterpenes from the rhizomes of Atractylodes macrocephala and their bioactivities - Hai-Xin Zhang; Jin-Guang Si; Jing-Rong Li; Meng Yu; Ling-Ling Qin; Chen-Xu Zhao; Tao Zhang; Zhong-Mei Zou (Phytochemistry, 2023)

Enhanced biodegradation of thiamethoxam with a novel polyvinyl alcohol (PVA)/sodium alginate (SA)/biochar immobilized Chryseobacterium sp H5 - Xuezhu Xiang; Xiaohui Yi; Wanbing Zheng; Yingqiang Li; Chao Zhang; Xinzhi Wang; Zhenguo Chen; Mingzhi Huang; Guang-Guo Ying (Journal of Hazardous Materials, 2023)

Mass transfer modeling for viscous fluids in a disk-distributor rotating packed bed - Yan-Bin Li; Zhang-Nan Wen; Han-Zhuo Xu; Guang-Wen Chu; Liang-Liang Zhang; Jian-Feng Chen (Chemical Engineering Journal, 2023)

Salecan confers anti-inflammatory effects in liver injury via regulating gut microbiota and its metabolites - Yanjun Liu; Panpan Li; Wenjie Pan; Juan Zhao; Chen Guang Olnood; Yuanfa Liu; Yong-Jiang Xu (Carbohydrate Polymers, 2023)

Overexpression of maize GOLDEN2 in rice and maize calli improves regeneration by activating chloroplast development - Wanni Luo; Jiantao Tan; Tie Li; Ziting Feng; Zhi Ding; Xianrong Xie; Yuanling Chen; Letian Chen; Yao-Guang Liu; Qinlong Zhu; Jinxing Guo (Science China Life Sciences, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Molecular mechanism study on the effect of nonionic surfactants with different degrees of ethoxylation on the wettability of anthracite - Xuanlai Chen; Guochao Yan; You Zhou; Guang Xu; Xuyang Bai; Jiajun Li (Chemosphere, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Effect of multi-type oxides on the catalytic pyrolysis behaviors of 5-amino-1H-tetrazole - Jiu Chen; Quan Liu; Xian-Zhao Song; Si-Yuan Zhou; Bin Li; Li-Feng Xie; Guang-Cheng Yang; Cheng-Yan Cao; Song Lu; Dan Zhang (Fuel, 2023)

Associations between greenspace surrounding schools and lipid levels in Chinese children and teenagers - Li-Xin Hu; Shujun Fan; Yinghua Ma; Xiao-Xuan Liu; Wen-Wen Bao; Yuming Guo; Li-Wen Hu; Gongbo Chen; Xiao-Wen Zeng; Zhiyong Zou; Bo-Yi Yang; Jun Ma; et al. (Environmental Pollution, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Dual electrical-behavior regulation of α-MoC quantum dots and Mo-N-C sites for high photoelectric conversion performance of solar cells - Jixin Yao; Wen Wang; Jie Wang; Shiwei Wu; Ying Meng; Shibin Lu; Haibo Wang; Feng Du; Bo Yang; Dongmeng Chen; Huaibao Tang; Haifeng Xu; et al. (Chemical Engineering Journal, 2023)

Nitrogen and phosphorus co-doped porous carbons (NPCs) for peroxydisulfate (PDS) activation towards tetracycline degradation: Defects enhanced adsorption and non-radical mechanism dominated by electron transfer - Minxian Cheng; Yichu Zhang; Bo Lai; Lingzhen Wang; Shengjiong Yang; Kailong Li; Dongqi Wang; Yaoguo Wu; Guang-Hao Chen; Jin Qian (Chemical Engineering Journal, 2023)

Facile synthesis of Fe3C-dominated Fe/Fe3C/FeN0.0324 multiphase nanocrystals embedded in nitrogen-modified graphitized carbon as efficient pH-universal catalyst for oxygen reduction reaction and zinc-air battery - Guang Li; Kuang Sheng; Yu Lei; Juan Yang; Yulian Chen; Xiaowei Guo; Gairong Chen; Baobao Chang; Tianjing Wu; Xianyou Wang (Chemical Engineering Journal, 2023)

Poly(ionic liquid) boosts overall performance of electrocatalytic reduction of low concentration of CO gas - Guo-Yi Duan; Xiao-Qiang Li; Jun-Wu Chen; Guang-Rong Ding; Peng-Xin Guan; Bao-Hua Xu (Chemical Engineering Journal, 2023)

An inhibitory effect of schisandrone on α-hemolysin expression to combat methicillin-resistant staphylococcus aureus infections - Yingxin Qi; Juan Hou; Yicheng Zhao; Wu Song; Li Wang; Huan Chen; Guang Chen (World Journal of Microbiology and Biotechnology, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Three novel antioxidant peptides isolated from C-phycocyanin against H2O2-induced oxidative stress in zebrafish via Nrf2 signaling pathway - Fenghua Xu; Yun Zhang; Yuezi Qiu; Fanghao Yang; Guoxiang Liu; Xiaolei Dong; Guang Chen; Can Cao; Qian Zhang; Shanshan Zhang; Bing Li (Frontiers in Marine Science, 2022)
Background C-phycocyanin (C-PC), a phycobiliprotein from Spirulina platensis, has been confirmed to be an effective antioxidant. Duing to the large molecular weight protein, C-PC is hardly absorbed in the human gut and easy coagulates into lumps. In light of this, highly pure, easy absorption, and small molecular weight polypeptides has won the attention in the recent past. However, there are few studies on the C-PC bioactive peptides. Thus, the objective of this study was find natural multifunctional antioxidant peptides from C-PC and demonstrate their mechanisms. Method In this study, novel antioxidant peptides from pancreatin hydrolysate of C-PC were isolated and purified by using a multi-bioassay-guided method. The DPPH and ABTS radical scavenging in vitro and antioxidant zebrafish model in vivo were used to evaluate the antioxidant activities. Furthermore, the underlying molecular mechanisms of these peptides were investigated by measuring the level of ROS, MDA, SOD, CAT and gene expression in Nrf2 signaling pathway. Results Total three novel active peptides, MHLWAAK (Met-His-Leu-Trp-Ala-Ala-Lys), MAQAAEYYR (Met-Ala-Gln-Ala-Ala-Glu-Tyr-Tyr-Arg), and MDYYFEER (Met-ASP-Tyr-Tyr-Phe-Glu-Glu-Arg) were isolated and purified from pancreatin hydrolysate of C-PC. These synthesized peptides displayed high DPPH and ABTS radical scavenging ability. In addition, in a zebrafish model, the three peptides significantly protected zebrafish embryos from H2O2-induced oxidative injury without toxicity by inhibiting ROS generation, preventing MDA formation, and upregulating the activities of SOD and CAT. Further experiments showed that these peptides could significantly regulated oxidative stress via activating the Nrf2 signaling pathway. Conclusion This study indicates that the antioxidant peptides from C-PC could serve as powerful antioxidants for preventing and treating various diseases associated with oxidative stress.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Failure criteria of unreinforced masonry walls of rural buildings under the impact of flash floods in mountainous regions - Guang-wu Si; Xiao-qing Chen; Jian-gang Chen; Wan-yu Zhao; Shuai Li; Xiang-ning Li (Journal of Mountain Science, 2022)

Anatexis of late Neoarchean-Early Paleoproterozoic and late Paleoproterozoic garnet-bearing leucogranite from the Khondalite Belt in the North China Craton - Qiang Shi; Zhong-Yuan Xu; Guo-Chun Zhao; Ding Ding; Guang-Wei Liu; Zhong-Hai Zhao; Jing-Yu Yu; Chen Li; Li-Qiang Bai; Yao Wang; Bing Guo; Kai Zhang; et al. (International Geology Review, 2022)

Amino acid transporter gene TaATLa1 from Triticum aestivum L. improves growth under nitrogen sufficiency and is down regulated under nitrogen deficiency - Heng Chen; Yingchun Liu; Jiazhen Zhang; Yifei Chen; Cuican Dai; Renmei Tian; Tianxiang Liu; Mingxun Chen; Guang Yang; Zhonghua Wang; Hongxia Li; Xinyou Cao; et al. (Planta, 2022)

Improving the combined GNSS/INS positioning by using tightly integrated RTK - Bofeng Li; Guang’e Chen (GPS Solutions, 2022)

Experimental Investigation and Numerical Modeling of Two-Phase Flow Development and Flow-Induced Vibration of a Multi-Plane Subsea Jumper - Wenhua Li; Qing Zhou; Guang Yin; Muk Chen Ong; Gen Li; Fenghui Han (Journal of Marine Science and Engineering, 2022)
As an essential component in the offshore oil and gas industry, subsea jumpers are likely to encounter the cyclic-induced stresses caused by the alternating movement of gas plugs and liquid slugs while transporting a multiphase mixture. The present study investigates the gas-liquid flow and the induced vibration in a multi-plane jumper by adopting experimental and numerical techniques. The flow patterns at every characteristic section of a Z-shaped jumper with an inner diameter of 48 mm are experimentally investigated, including dispersed bubbly, slug, churn, wavy, stratified and annular flows. Displacement and pressure sensors are installed near each elbow to record the vibration and pressure response of the jumper. It is found that both pressure characteristics and vibration amplitudes are highly related to the gas content rate, mixing velocity, and gas and liquid superficial velocity. The one-way fluid–solid coupling numerical simulations are performed and validated against the experimental data in terms of the flow patterns and the induced vibrations at different gas–liquid velocities. The results reveal that both simulated flow patterns and vibration responses agree well with the experiments.

Antibacterial activities of the chemical constituents of Schizophyllum commune MST7-3 collected from coal area - Guang-Gui Chen; Qin-Feng Zhu; Xing-Mei Long; Qian Lu; Kai-Yu Li; Qian Chen; Meng Zhou; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2022)

Ambiguity resolution for smartphone GNSS precise positioning: effect factors and performance - Bofeng Li; Weikai Miao; Guang’e Chen; Zhong Li (Journal of Geodesy, 2022)

Ovary transcriptomic analysis reveals regulation effects of dietary fish oil on hormone, lipid, and glucose metabolism in female adult spotted scat (Scatophagus argus) - Tuo Wang; Zhi-Long Liu; Guang-Li Li; Umar Farouk Mustapha; Charles Brighton Ndandala; Hong-Juan Shi; Chun-Hua Zhu; Hua-Pu Chen; Yang Huang; Dong-Neng Jiang (Frontiers in Marine Science, 2022)
In the aquaculture industry, fish oil is widely used as a nutritional supplement to promote the gonadal maturation of broodstocks, while the mechanism of fish oil on ovary development remain unclear. Herein, female adult spotted scat ( Scatophagus argus ) with most ovaries at phase II were fed with diets containing 8% soybean oil (SO) or 8% fish oil (FO) for 60 days. The final average fish body weight was similar between FO and SO groups. The average gonadosomatic index (GSI) of FO group was higher (non-significant) than that of SO group. Finally, the phase IV ovary of the FO and SO groups were 7 and 5 out of 10, respectively. The serum estradiol (E2) level of the FO group was significantly higher than that of the SO group. The proportions of n-3 long-chain polyunsaturated fatty acids (LC-PUFA, such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA)) in the ovaries were much higher in the FO group than in the SO group. These results suggest that the maturity level of the FO group is relatively higher than that of the SO group. Transcriptome sequencing was used to detect the ovary gene expression. Comparatively, the ovary transcriptome analysis showed 68 up-regulated and 193 down-regulated genes in the FO group. The expression levels of Jund and Jun necessary for the ovary maturation were up-regulated in the FO group, while Pparγ and Cxcl12 , which could inhibit the ovary development, were down-regulated in the FO group. Cyp3a27 coding the enzyme for degrading the estrogen was significantly down-regulated in the FO group and coincided with the increase of its serum E2. Kif5b which could regulate the glucose metabolism was up-regulated in the FO group. Serum insulin level was also increased in the FO group. Additionally, Aldh3a2 and Plin2 related to lipid metabolism were significantly down-regulated in the FO group. Briefly, dietary fish oil can influence the expression of genes related to steroid hormone, glucose and lipid metabolism. This study will clarify the mechanism of dietary fish oil in promoting ovary development in teleost fish.

Intestinal Models for Personalized Medicine: from Conventional Models to Microfluidic Primary Intestine-on-a-chip - Xiang-Guang Li; Ming-xia Chen; Su-qing Zhao; Xiu-qi Wang (Stem Cell Reviews and Reports, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

Halomonas faecis sp. nov., a halophilic bacterium isolated from human faeces - Zhu-Xiang Liu; Jin-Hua Chen; Ling-Ling Yang; Yu-Zhou Feng; Li-Ying Deng; Jian-Wu He; Shu-Kun Tang; Yi-Guang Chen (Extremophiles, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Identification of Key Pathways and Genes in SARS-CoV-2 Infecting Human Intestines by Bioinformatics Analysis - Ji-Chun Chen; Tian-Ao Xie; Zhen-Zong Lin; Yi-Qing Li; Yu-Fei Xie; Zhong-Wei Li; Xu-Guang Guo (Biochemical Genetics, 2022)
COVID-19 is a serious infectious disease that has recently swept the world, and research on its causative virus, SARS-CoV-2, remains insufficient. Therefore, this study uses bioinformatics analysis techniques to explore the human digestive tract diseases that may be caused by SARS-CoV-2 infection. The gene expression profile data set, numbered GSE149312, is from the Gene Expression Omnibus (GEO) database and is divided into a 24-h group and a 60-h group. R software is used to analyze and screen out differentially expressed genes (DEGs) and then gene ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses are performed. In KEGG, the pathway of non-alcoholic fatty liver disease exists in both the 24-h group and 60-h group. STRING is used to establish a protein–protein interaction (PPI) network, and Cytoscape is then used to visualize the PPI and define the top 12 genes of the node as the hub genes. Through verification, nine statistically significant hub genes are identified: AKT1, TIMP1, NOTCH, CCNA2, RRM2, TTK, BUB1B, KIF20A, and PLK1. In conclusion, the results of this study can provide a certain direction and basis for follow-up studies of SARS-CoV-2 infection of the human digestive tract and provide new insights for the prevention and treatment of diseases caused by SARS-CoV-2.

Expanding the clinical spectrum of adult-onset neuronal intranuclear inclusion disease - Yuwen Cao; Jingying Wu; Yunhua Yue; Chao Zhang; Shihua Liu; Ping Zhong; Shige Wang; Xiaojun Huang; Weiping Deng; Jing Pan; Lan Zheng; Qing Liu; et al. (Acta Neurologica Belgica, 2022)

Geographic distance, sedimentation, and substrate shape cryptic crustose coralline algal assemblages in the world’s largest subtropical intertidal algal reef - Shing Hei Zhan; Ling Chen; Chen‐Pan Liao; Wun‐Ruei Chang; Cheng‐Chin Li; Guang‐You Tang; Ching‐Yu Liou; Wei‐Lung Wang; Shih‐Wei Wang; Shao‐Lun Liu (Molecular Ecology, 2022)
Algal reefs, concreted by crustose coralline algae (CCA), are the main biotic reefs in temperate waters but rare in the subtropics and tropics. The world's largest known intertidal algal reef in the subtropics is the Taoyuan Algal Reef (TAR) located in the northwestern coast of Taiwan. The biodiversity and ecology of the TAR are scarcely explored, and now the reef is imperiled by industrialization. Here, we document cryptic species of CCA in Taiwan, particularly the TAR, by sequencing the psb A genes of over 1800 specimens collected across Taiwan. We also examine the ecological background of the TAR by surveying its benthic composition and measuring its environmental parameters. Our data reveal that the TAR harbours a high diversity of cryptic CCA species (27 molecular operational taxonomic units, or mOTUs), many of which are potentially new to science (18 mOTUs) and/or endemic to the TAR (9 mOTUs). Comparing the CCA species inventory of the TAR with the rest of Taiwan shows that the TAR represents a unique hotspot of CCA taxa in the waters of Taiwan. Our analyses show that variation in the CCA assemblages in the TAR is associated with geographic distance, sedimentation, and substrate type (for example, reef vs. hermit crab shell), suggesting that dispersal limitation and contemporary environmental selection shape the CCA assemblages in the TAR. The data from this study can inform the monitoring of human impacts on the health of the TAR and contribute to our understanding of the ecological processes underlying algal reef development.

How the Skate Embryo Develops: A Fine Developmental Timeline of Kong Skate Okamejei kenojei (Müller & Henle, 1841) - Gao Guang; Xiao Zhizhong; Ma Yuting; Chen Xiao; Xiao Yongshuang; Li Jun (Frontiers in Marine Science, 2022)
Cartilaginous fishes, as an important group of jawed vertebrates, hold great promise for improving our understanding of vertebrate evolution. Previous studies have established a good staging scheme for shark embryos. However, to date, little attention has been paid to the development of skate embryos. In this study, we established a fine developmental timeline for the Kong skate. We hatched eggs of the Kong skate ( Okamejei kenojei ) at fixed temperatures (16.5°C ± 0.5°C) while observing three samples every day and recorded the complete embryonic development. The embryo weight and development time were found to have a quadratic relationship. The weight-at-day curve was fitted by y = 0.0005x 2 - 0.0109x + 0.0882 (R² = 0.9406). In addition, complete embryonic development from gastrula to skate larvae took 92 ± 5 days. Here, we divided the entire development process into 39 stages. This shows that the jaw of O. kenojei is developed from the first pair of pharyngeal arches, and its body disc is formed by the fusion of the pectoral fin and head. The eyespots began to form from stage 36 and then became thicker and bigger until the young skate broke out of the egg. Notably, we found that males and females develop differently from stage 31; the end of the male pelvic fins expands inward, which develop into copulatory organ-claspers, whereas in the females, they do not expand. To the best of our knowledge, this is the first study to record the embryonic development of eyes, body discs, eyespots, and other organs of O. kenojei in detail. We hope that our work will provide valuable information for researchers to identify specific time points for developing skate embryos.

Neuropeptide Y in Spotted Scat (Scatophagus Argus), Characterization and Functional Analysis towards Feed Intake Regulation - Daniel Assan; Yaorong Wang; Umar Farouk Mustapha; Charles Brighton Ndandala; Zhiyuan Li; Guang-Li Li; Huapu Chen (Fishes, 2022)
Neuropeptide Y (Npy) is an intricate neuropeptide regulating numerous physiological processes. It is a highly conserved peptide known to improve feed intake in many vertebrates, including fishes. To enlighten the mechanism of Npy in spotted scat feed intake control, we cloned and identified the Npy cDNA sequence. We further examined its expression in some tissues and explored its expression effects at different time frames (hours and days). Here, we discovered that spotted scat Npy comprised a 300 bp open reading frame (ORF) and a 99 amino acid sequence. Npy was identified to be expressed in all tissues examined. Using in situ hybridization examination, we proved that npy has a wide expression in the brain of the spotted scat. Furthermore, the expression of npy in the hypothalamus significantly increased one hour after feeding (p

Correction to: Arthrobacter wenxiniae sp. nov., a novel plant growth-promoting rhizobacteria species harbouring a carotenoids biosynthetic gene cluster - Yu-chen Sun; Pengbo Sun; Jing Xue; Yunpeng Du; Hui Yan; Li-wei Wang; Xin-xin Yi; Jian-guang Sun; Xiuhai Zhang; Jun-lian Gao (Antonie van Leeuwenhoek, 2022)

Reproductive Dynamics of the Large Yellow Croaker Larimichthys crocea (Sciaenidae), A Commercially Important Fishery Species in China - Li-ting Yan; Yan Jiang; Qing Xu; Guang-mao Ding; Xin-yi Chen; Min Liu (Frontiers in Marine Science, 2022)
The large yellow croaker Larimichthys crocea (Richardson, 1846) (Sciaenidae) is distributed in southern Yellow Sea, East China Sea, and northern South China Sea of China and is a commercially important nearshore fishery species. L. crocea was listed on the IUCN Red List as “Critically Endangered” in 2020 mainly due to the over-exploration of its spawning and over-wintering aggregations in the 1950s–1980s throughout its distribution region. However, detailed studies on reproductive dynamics of L. crocea were limited in the past three decades. In this study, the reproductive dynamics of L. crocea was examined in the traditional Guanjingyang (GJY) spawning ground, one of the 15 well-known ones in its distribution region. Samples were collected using set nets from April 2019 to November 2021 to ensure at least 20 samples for all 12 months. A total of 1,006 individuals were caught, ranging from 46 to 391 mm standard length (SL) and 1.45 to 1,110.05 g body weight (BW). A growth dimorphism was found between sexes with females heavier than males when body sizes exceeded 61 mm SL (non-parametric ANCOVA, p < 0.01). Gonad histology of all 1,006 individuals revealed, for the first time, that L. crocea was able to spawn almost year-round for both females and males. Two spawning peaks, spring and autumn, were identified in March and May and in November for females and in April to June and in October to November for males. The minimum sizes at sexual maturity were 160 mm SL for females and 112 mm SL for male. The sizes at 50% sexual maturity were 187.2 mm SL for females and 150.2 mm SL for males. Results showed that the minimum SL for female maturity decreased about 20% in the past six decades. The spawning peaks were 2 months earlier in spring and 1 month extension in autumn in GJY. Clearly, the national fishing moratorium regulation in May to August, an important fishery management measure in China, can only protect the spring spawning peak partly. Further evaluation on the influence of climate change on reproductive strategies and stock recruitment of L. crocea is highly recommended.

Effective connectivity decreases in specific brain networks with postparalysis facial synkinesis: a dynamic causal modeling study - Zhen-Zhen Ma; Ye-Chen Lu; Jia-Jia Wu; Xu-Yun Hua; Si-Si Li; Wei Ding; Jian-Guang Xu (Brain Imaging and Behavior, 2022)

Identification of the soybean small auxin upregulated RNA (SAUR) gene family and specific haplotype for drought tolerance - Guang Li; Quan Wang; Lei Lu; Shoudong Wang; Xiao Chen; Muhammad Hafeez U. Khan; Yaohua Zhang; Suxin Yang (Biologia, 2022)

A new isoflavone from the fruits of Ficus auriculata and its antibacterial activity - Tai-Ming Shao; Hai-Xia Liao; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Arthrobacter wenxiniae sp. nov., a novel plant growth-promoting rhizobacteria species harbouring a carotenoids biosynthetic gene cluster - Yu-chen Sun; Pengbo Sun; Jing Xue; Yunpeng Du; Hui Yan; Li-wei Wang; Xin-xin Yi; Jian-guang Sun; Xiuhai Zhang; Jun-lian Gao (Antonie van Leeuwenhoek, 2022)

Neoflavonoids from the heartwood of Dalbergia melanoxylon - Meng-fei Wang; Guang-qiang Ma; Feng Shao; Rong-hua Liu; Lan-ying Chen; Yang Liu; Li Yang; Xiao-wei Meng (Natural Product Research, 2022)

Geochronology and geochemistry of Early Cretaceous bimodal volcanic rocks from Erguna Massif, NE China: evidence for the back-arc extension of the Mongol–Okhotsk orogenic belt - Fei Yang; Gong-Zheng Chen; Guang Wu; Ying-Lei Li; Yong-Xu Shao; Tie-Gang Li; Guang-Chao Song; Bing Han (International Journal of Earth Sciences, 2022)

Analysis of Pipeline Deformation Caused by Shield Tunnel Excavation that Obliquely Crosses Existing Pipelines - Sheng-Wu Zhao; Xiao-Li Li; Xin Li; Li-Guang Chen; Tong Li; Suo-Hui Li; Yu Bai (Arabian Journal of Geosciences, 2022)

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

Integer ambiguity resolution and precise positioning for tight integration of BDS-3, GPS, GALILEO, and QZSS overlapping frequencies signals - Guang’e Chen; Bofeng Li; Zhiteng Zhang; Tianxia Liu (GPS Solutions, 2022)

Complete genome sequence of a novel mitovirus from binucleate Rhizoctonia AG-K strain FAS2909W - Yanqiong Li; Yang Sun; Lei Yu; Wurong Chen; He Liu; Lifang Yin; Yingxia Guang; Genhua Yang; Xiaohan Mo (Archives of Virology, 2022)

Mitogenomes provide new insights into the evolutionary history of Prodiamesinae (Diptera: Chironomidae) - Xiao‐Long Lin; Yan‐Min Zhao; Li‐Ping Yan; Wen‐Bin Liu; Wen‐Jun Bu; Xin‐Hua Wang; Chen‐Guang Zheng (Zoologica Scripta, 2022)
Evolutionary analysis of Prodiamesinae has long been impeded by lack of information, and its phylogenetic relationship with Orthocladiinae remains questionable. Here, ten complete mitochondrial genomes (mitogenomes) of Orthocladiinae sensu lato were newly sequenced, including three Prodiamesinae species and seven Orthocladiinae species. Coupled with published mitogenomes, a total of 12 mitogenomes of Orthocladiinae sensu lato were selected for a comparative mitogenomic analysis and phylogenetic reconstruction. Mitogenomes of Orthocladiinae sensu lato are conserved in structure, and all genes arrange the same gene order as the ancestral insect mitogenome. Nucleotide composition is highly biased, and the control region displayed the highest A + T content. All protein‐coding genes are under purifying selection, and the ATP8 evolves at the fastest rate. In addition, the mitogenomes of Orthocladiinae sensu lato are highly conserved, and they are practically useful for phylogenetic inference, suggesting a re‐classification of Orthocladiinae by sinking Prodiamesinae as a subgroup of Orthocladiinae.

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Antibiotic resistance genes and bacterial community on the surfaces of five cultivars of fresh tomatoes - Yanmei Sun; Guang Guo; Fang Tian; Huihai Chen; Weijie Liu; Meng Li; Shiwei Wang (Ecotoxicology, 2021)

Glycomyces salinus sp. nov., an actinomycete isolated from a hypersaline habitat - Rui Li; Gang-Qiang Jiang; Yun Wang; Yi-Guang Chen; En-Min Zhou; Shu-Kun Tang (Archives of Microbiology, 2021)

Correction to: A failure case study of tunnel water inrush source identified by statistical analysis model - Li-Gang Yuan; Xiao-Li Li; Xin Li; Yi-Lin Yu; Li-Guang Chen; Xian-Pan Xu; Xiang Wang (Arabian Journal of Geosciences, 2021)

Sesquiterpenoids from Artemisia argyi and their NO production inhibitory activity in RAW264.7 cells - Gui-Min Xue; Jin-Feng Xue; Chen-Guang Zhao; Zhen-Zhu Zhao; Yan-Jun Sun; Kun Du; Han-Wei Li; Wei-Sheng Feng (Natural Product Research, 2021)

Baicalin attenuates adriamycin-induced nephrotic syndrome by regulating fibrosis procession and inflammatory reaction - Ning Tan; Chen-Xia Sun; Hui-Jun Zhu; De-Yu Li; Sheng-Guang Huang; Shou-Di He (Genes & Genomics, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Corticosterone Can Be an Essential Stress Index in Channel Catfish (Ictalurus punctatus) - Kang Xiao; Xi Wang; Wen-Bin Liu; Ding-Dong Zhang; Xiang-Fei Li; Chun-Nuan Zhang; Wei-Hua Chen; Kenneth Prudence Abasubong; Guang-Zhen Jiang (Frontiers in Marine Science, 2021)
Although cortisol is considered the main glucocorticoid involved in regulating stress in fish by elevating the serum glucose, the presence of serum corticosterone and whether its level can be used as an indicator for fish stress activation and reflect the degree of fish stress remains to be determined. To comprehensively and accurately evaluate the performance of two glucocorticoids after stress, in this study, seven of the most common stressors (ammonia nitrogen, high-temperature, acid, alkali, Aeromonas hydrophila, and salinity) in aquaculture were selected. The levels of serum corticosterone, cortisol, and glucose were detected within 48 h, and then the dynamic changes were analyzed. In addition, the kidneys were collected to detect the expression of corresponding proteins involved in corticosterone and cortisol synthesis (3 β-HSD and CYP17A1) for further exploration. From the results obtained, the content of serum corticosterone was about 100 times higher than that of cortisol, and it was found that corticosterone and cortisol showed different dynamic changes within 48 h among the seven kinds of stress. In the subsequent detection of glucose, it was found that the dynamic shift in glucose was not consistent with the dynamic changes of corticosterone or cortisol entirely but seemed to be caused by the combination of the two. In the follow-up protein expression detection, we found that corticosterone seemed to respond to stress earlier. Therefore, it is concluded that the responses of corticosterone and cortisol to stress are independent, corticosterone may be more sensitive in the current seven acute stresses, and then they regulate glucose together to resist stress. The study aimed to fill the vacancy of corticosterone in fish research and provide a reference for the complete evaluation of fish stress degree.

Application of Plant Print Identification Technology in Salt-resistant Soybean Breeding - Yan Li; Xia Li; Zi-qi Chen; Ying Ma; Guang-yu Yang; Ying Zhang; Ming-chun Sun; Li-hong Zhang; Jin-meng Chu; Jing-mei Lu; Jun Zhu; Ji-hong You (Journal of Plant Growth Regulation, 2021)

Caulobacter endophyticus sp. nov., an endophytic bacterium harboring three lasso peptide biosynthetic gene clusters and producing indoleacetic acid isolated from maize root - Jun-lian Gao; Pengbo Sun; Yu-chen Sun; Jing Xue; Guoliang Wang; Li-wei Wang; Yunpeng Du; Xiuhai Zhang; Jian-guang Sun (Antonie van Leeuwenhoek, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Marinobacter orientalis sp. nov., a thiosulfate-oxidizing bacterium isolated from a marine solar saltern - Feng-Bai Lian; Xu-Yang Chen; Shan Jiang; Guang-Yu Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Dynamic Elimination of Enrofloxacin Under Varying Temperature and pH in Aquaculture Water: An Orthogonal Study - Longxiang Fang; Yiwen Zhou; Zhuyu Huang; Guang Yang; Tian Li; Chao Song; Jiazhang Chen (Bulletin of Environmental Contamination and Toxicology, 2021)

Large-scale Late Triassic to Early Jurassic high εHf(t)–εNd(t) felsic rocks in the Ergun Massif (NE China): implications for southward subduction of the Mongol–Okhotsk oceanic slab and lateral crustal growth - Yinglei Li; Guang Wu; Shengjin Zhao; Gongzheng Chen; Fei Yang; Tiegang Li (International Journal of Earth Sciences, 2021)

Effects of fenvalerate concentrations and its chiral isomers on bacterial community structure in the sediment environment of aquaculture ponds - Chao Song; Jingwei Zhang; Xi Chen; Gengdong Hu; Limin Fan; Guang Yang; Tian Li; Liping Qiu; Jiazhang Chen; Longxiang Fang (Environmental Science and Pollution Research, 2021)

Prestack seismic stochastic inversion based on statistical characteristic parameters - Wang Bao-Li; Lin Ying; Zhang Guang-Zhi; Yin Xing-Yao; Zhao Chen (Applied Geophysics, 2021)

Multiple‐scale negative impacts of warming on ecosystem carbon use efficiency across the Tibetan Plateau grasslands - Ning Chen; Yangjian Zhang; Juntao Zhu; Nan Cong; Guang Zhao; Jiaxing Zu; Zhipeng Wang; Ke Huang; Li Wang; Yaojie Liu; Zhoutao Zheng; Ze Tang; et al. (Global Ecology and Biogeography, 2021)
Aim Ecosystem carbon use efficiency (CUEe) is a core parameter of ecosystem process models, but its relationships with climate are still uncertain, especially for ecosystems with harsh environments. Large inconsistencies in climate impacts on the CUEe have been reported among various spatial scales. The goal of this study was to examine whether warming promotes or restricts the CUEe and whether the CUEe responds to a warming gradient in a linear or nonlinear manner. Location Tibetan Plateau. Time period 2000–2018. Major taxa studied Alpine grassland ecosystem. Methods We integrated multiple‐source data of carbon fluxes and CUEe, including warming experiments at a site scale, eddy covariance observations at a landscape scale and synthesized warming experiments and ecosystem process models at a regional scale. Next, we deployed a statistical model to examine the warming impacts on the CUEe across scales; the effects of biotic and abiotic factors on the CUEe and its components were summarized based on the results of standardized major axis tests and routines, structural equation modelling and nonlinear models. Results This study reported a suppressive warming impact on the CUEe, which followed a nonlinear curve with severe inhibition in the high‐level warming treatment. With a warming threshold of 1.5–2.0°C, CUEe response patterns transitioned from no change to a significant decrease. The restriction effects can be ascribed to the joint adverse and asymmetric effects of warming on CUEe components under multiple‐level warming. Warming‐modified relationships among CUEe components and the nonlinear effects of biotic and abiotic factors led to the nonlinear responses of CUEe to warming. Main conclusions This study revealed suppressive and nonlinear effects of warming on the CUEe, including especially dramatic CUEe decreases with high‐level warming. These findings are critical for optimizing model parameters and improving predictions of the carbon sequestration capacity of alpine grasslands.

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Fasting Increases Iron Export by Modulating Ferroportin 1 Expression Through the Ghrelin/GHSR1α/MAPK Pathway in the Liver - Qianqian Luo; Jianan Hu; Guang Yang; Xiaoyu Yuan; Zhongping Chen; Dan Wang; Yapeng Lu; Li Zhu; Guohua Wang (Biological Trace Element Research, 2021)

The Arabidopsis KH-domain protein FLOWERING LOCUS Y delays flowering by upregulating FLOWERING LOCUS C family members - Guang-Yi Dai; Ding-Kang Chen; Yun-Peng Sun; Wei-Yi Liang; Yu Liu; Li-Qun Huang; Yong-Kang Li; Jia-Fan He; Nan Yao (Plant Cell Reports, 2020)

Intramuscular injection of tetracycline decreased gut microbial diversity in mouse - Jia Liu; Xi-chuan Deng; Xiao-yu Li; Zhi-bang Yang; Guang-yuan Zhang; Ting-ting Chen (Mammalian Genome, 2020)

2-Hydroxypropyl-β-cyclodextrin Ototoxicity in Adult Rats: Rapid Onset and Massive Destruction of Both Inner and Outer Hair Cells Above a Critical Dose - Xiaopeng Liu; Dalian Ding; Guang-Di Chen; Li Li; Haiyan Jiang; Richard Salvi (Neurotoxicity Research, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Postchemotherapy hippocampal functional connectivity patterns in patients with breast cancer: a longitudinal resting state functional MR imaging study - Yun Feng; Dilihumaer Tuluhong; Zhao Shi; Li Juan Zheng; Tao Chen; Guang Ming Lu; Shaohua Wang; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Well hydraulics of temporally varying artificial recharge with well clogging in confined aquifers - Jiong Li; Jin-Jian Chen; Ming-Guang Li; Xiao-He Xia (Arabian Journal of Geosciences, 2020)

Bayesian prediction of potential depressions in the Erlian Basin based on integrated geophysical parameters - Feng-Jiao Xu; Chuan-Zhang Tang; Liang-Jun Yan; Qing-Li Chen; Guang-Ye Feng (Applied Geophysics, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Mesorhizobium rhizophilum sp. nov., a 1-aminocyclopropane-1-carboxylate deaminase producing bacterium isolated from rhizosphere of maize in Northeast China - Jun-lian Gao; Jing Xue; Yu-chen Sun; Han Xue; En Tao Wang; Hui Yan; Shuai Tong; Li-wei Wang; Xiuhai Zhang; Jian-guang Sun (Antonie van Leeuwenhoek, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

A new triterpenoid glucoside from Leucas zeylanica - Guang-Ying Chen; Bin Zhang; Ting Zhao; Najat Nidhal; Wang Jia-Li; Xue-Ming Zhou; Dai Chun-Yan (Natural Product Research, 2020)

Shortened snRNA promoters for efficient CRISPR/Cas-based multiplex genome editing in monocot plants - Yu Hao; Wubei Zong; Dongchang Zeng; Jingluan Han; Shuifu Chen; Jianian Tang; Zhe Zhao; Xiaojuan Li; Kun Ma; Xianrong Xie; Qinlong Zhu; Yuanling Chen; et al. (Science China Life Sciences, 2020)

Development of a specific AFLP-based SCAR marker for Chinese Race 34MKG of Puccinia graminis f. sp. tritici - Si Chen; Xue Yang; Wen-gong Huang; Yan Liu; Ying Yu; Guang-wen Wu; Shu-quan Zhang; Tian-ya Li; Yuan-yin Cao (Molecular Biology Reports, 2020)

Study on Transient Unloading Response Characteristics of Brittle Coal Samples Under Different Stress Paths - Chen Qiao; Chang-hong Li; Guang-nan Ma (Geotechnical and Geological Engineering, 2020)

Efficacy of internet-based integrated intervention on depression and anxiety symptoms in patients with COVID-19 - Ning Wei; Bo-chao Huang; Shao-jia Lu; Jian-bo Hu; Xiao-yi Zhou; Chan-chan Hu; Jing-kai Chen; Jin-wen Huang; Shu-guang Li; Zheng Wang; Dan-dan Wang; Yi Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Heat stress induces apoptosis through disruption of dynamic mitochondrial networks in dairy cow mammary epithelial cells - Kun-Lin Chen; Hui-Li Wang; Lin-Zheng Jiang; Yong Qian; Cai-Xia Yang; Wei-Wei Chang; Ji-Feng Zhong; Guang-Dong Xing (In Vitro Cellular & Developmental Biology - Animal, 2020)

Comparative genomics analysis of Nitriliruptoria reveals the genomic differences and salt adaptation strategies - Dai-Di Chen; Ye Tian; Jian-Yu Jiao; Xiao-Tong Zhang; Yong-Guang Zhang; Zhou-Yan Dong; Meng-Jie Xiong; Min Xiao; Wen-Sheng Shu; Wen-Jun Li (Extremophiles, 2020)

Zircon U-Pb Ages and Magmatic History of the Kashan Plutons in the Central Urumieh-Dokhtar Magmatic Arc, Iran: Evidence for Neotethyan Subduction during Paleogene-Neogene - Tayebeh Khaksar; Nematollah Rashidnejad-Omran; Fukun Chen; Shu-Guang Song; Shuang-Qing Li; Majid Ghaderi (Journal of Earth Science, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Short hairpin RNAs targeting M and N genes reduce replication of porcine deltacoronavirus in ST cells - Wen-yuan Gu; Yan Li; Bao-jing Liu; Jing Wang; Guang-fu Yuan; Shao-jie Chen; Yu-Zhu Zuo; Jing-Hui Fan (Virus Genes, 2019)

Carbamazepine promotes specific stimuli-induced NLRP3 inflammasome activation and causes idiosyncratic liver injury in mice - Zhilei Wang; Guang Xu; Xiaoyan Zhan; Youping Liu; Yuan Gao; Nian Chen; Yuming Guo; Ruisheng Li; Tingting He; Xueai Song; Ming Niu; Jiabo Wang; et al. (Archives of Toxicology, 2019)

Genome-editing technologies: the gap between application and policy - Gousi Li; Yao-Guang Liu; Yuanling Chen (Science China Life Sciences, 2019)

Accumulation and Depuration of Nonylphenol and Its Effect on the Expressions of Vitellogenin and Vitellogenin Receptor in Freshwater Prawn Macrobrachium rosenbergii - Hui Guo; Luan-luan Chen; Guang-li Li; Si-ping Deng; Chun-hua Zhu (Bulletin of Environmental Contamination and Toxicology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

ATP induces caspase-3/gasdermin E-mediated pyroptosis in NLRP3 pathway-blocked murine macrophages - Chen-Ying Zeng; Chen-Guang Li; Jun-Xiang Shu; Li-Hui Xu; Dong-Yun Ouyang; Feng-Yi Mai; Qiong-Zhen Zeng; Cheng-Cheng Zhang; Rui-Man Li; Xian-Hui He (Apoptosis, 2019)

Chemical constituents from Ginkgo biloba L. male flowers and their biological activities - Min Li; Zi-ming Xia; Bin Li; Ying Tian; Guang-jie Zhang; Chen Xu; Jun-xing Dong (Medicinal Chemistry Research, 2019)

Dysregulation of Fibroblast Growth Factor 10 in the Peripheral Blood of Patients with Schizophrenia - Yun Yu; Guo-Jun Xie; Yang Hu; Xue-Song Li; Guang-Yang Chen; Guang-En Zheng; Xi Chen; Yong Cheng (Journal of Molecular Neuroscience, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

A new cadinane sesquiterpenoid glucoside with cytotoxicity from Abelmoschus sagittifolius - De-Li Chen; Guang Li; Yang-Yang Liu; Guo-Xu Ma; Wei Zheng; Xiao-Bo Sun; Xu-Dong Xu (Natural Product Research, 2019)

Identification, evolution and alternative splicing profile analysis of the splicing factor 30 (SPF30) in plant species - Di Zhang; Jing-Fang Yang; Bei Gao; Tie-Yuan Liu; Ge-Fei Hao; Guang-Fu Yang; Li-Jun Fu; Mo-Xian Chen; Jianhua Zhang (Planta, 2019)

Antiproliferative activity of ursolic acid/glycyrrhetinic acid-uracil/thymine hybrids - Li Sun; Xiang-Wu Chu; Chun-mei Liu; Li-Xin Sheng; Zhuan-Xin Chen; Ke-Guang Cheng (Medicinal Chemistry Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

The LRP6 functional mutation rs2302685 contributes to individual susceptibility to alcoholic liver injury related to the Wnt/β-catenin-TCF1-CYP2E1 signaling pathway - Ying Xu; Dan Chen; Xiu-Xian Lin; Qing Zhao; Jing Guo; Li-jie Chen; Wei Zhang; Jian Xiao; Guang-Hui Lian; Shi-Fang Peng; Dong Guo; Hong Yang; et al. (Archives of Toxicology, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Chemotherapeutic paclitaxel and cisplatin differentially induce pyroptosis in A549 lung cancer cells via caspase-3/GSDME activation - Cheng-cheng Zhang; Chen-guang Li; Yao-feng Wang; Li-hui Xu; Xian-hui He; Qiong-zhen Zeng; Chen-ying Zeng; Feng-yi Mai; Bo Hu; Dong-yun Ouyang (Apoptosis, 2019)

Relationships between body weight and other morphological traits in young sea cucumbers Apostichopus japonicas - Yaoyao Zhan; Weijie Zhang; Chen Ge; Kai Lin; Guang Li; Jian Song; Yaqing Chang (Journal of Oceanology and Limnology, 2019)

Experimental Study and Estimation of Groundwater Fluctuation and Ground Settlement due to Dewatering in a Coastal Shallow Confined Aquifer - Jiong Li; Ming-Guang Li; Lu-Lu Zhang; Hui Chen; Xiao-He Xia; Jin-Jian Chen (Journal of Marine Science and Engineering, 2019)
The coastal micro-confined aquifer (MCA) in Shanghai is characterized by shallow burial depth, high artesian head, and discontinuous distribution. It has a significant influence on underground space development, especially where the MCA is directly connected with deep confined aquifers. In this paper, a series of pumping well tests were conducted in the MCA located in such area to investigate the dewatering-induced groundwater fluctuations and stratum deformation. In addition, a numerical method is proposed for the estimation of hydraulic parameter, and an empirical prediction method is developed for dewatering-induced ground settlement. Test results show that groundwater drawdowns and soil settlement can be observed not only in MCA but also in the aquifers underneath it. This indicates that there is a close hydraulic connection among each aquifer. Moreover, the distributions and development of soil settlement at various depths are parallel to those of groundwater drawdowns in most areas of the test site except the vicinity of pumping wells, where collapse-induced subsidence due to high-speed flow may occur. Furthermore, the largest deformation usually occurs at the top of the pumping aquifer instead of the ground surface, because the top layer is expanded due to the stress arch formed in it. Finally, the proposed methods are validated to be feasible according to the pumping well test results and can be employed to investigate the responses of groundwater fluctuations and stratum deformations due to dewatering in MCA.

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Theoretical study of the mechanism of the manganese catalase KatB - Xi-Xi Yang; Qiu-Yun Mao; Xiao-Ting An; Xi-Chen Li; Per E. M. Siegbahn; Guang-Ju Chen; Hong-Wei Tan (JBIC Journal of Biological Inorganic Chemistry, 2019)

Spatial distribution and environmental implications of heavy metals in typical lead (Pb)-zinc (Zn) mine tailings impoundments in Guangdong Province, South China - Tao Chen; Chang Lei; Bo Yan; Li-li Li; Da-mao Xu; Guang-Guo Ying (Environmental Science and Pollution Research, 2018)

Association mapping and favourable QTL alleles for fibre quality traits in Upland cotton (Gossypium hirsutum L.) - Cheng-Guang Dong; Juan Wang; Yu Yu; Bao-Cheng Li; Quan-Jia Chen (Journal of Genetics, 2018)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

Serum Oxidative Stress Marker Levels in Unmedicated and Medicated Patients with Schizophrenia - Zhi-Le Bai; Xue-Song Li; Guang-Yang Chen; Yang Du; Ze-Xu Wei; Xi Chen; Guang-En Zheng; Wen Deng; Yong Cheng (Journal of Molecular Neuroscience, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

A new12-membered lactone from the stems of Ficus auriculata - Tai-Ming Shao; Cai-Juan Zheng; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Survival rate and population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) in Xiamen Bay, China - Bingyao Chen; Huili Gao; Thomas A. Jefferson; Yi Lu; Lin Wang; Shanshan Li; Hui Wang; Xinrong Xu; Guang Yang (Marine Mammal Science, 2018)
The survival rate and population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) in Xiamen, China, were estimated from vessel‐based surveys during 2007–2010. Over the course of 202 d (881.1 observation hours), 76 groups were observed, and 52 dolphins were successfully identified. The Cormack‐Jolly‐Seber model estimated a constant apparent survival of 0.948 (95% CI: 0.922–0.966). Based on the open/POPAN model, the population size was estimated at 70 individuals (95% CI: 63–88). To explore the effect of uneven yearly survey effort, we pooled the data with seven sampling occasions with similar effort. This data set generated similar results of a constant survival of 0.957 (95% CI: 0.918–0.978) and population size of 72 (95% CI: 65–88). The small population size of the Xiamen humpback dolphins satisfies the Critically Endangered criterion of IUCN (D), and emphasizes urgency of the need for protection of the population. Improved monitoring efforts should be focused on enhancing our understanding of current status and evaluating impacts of all anthropogenic activities. A conservation plan for the population should also be drawn up.

Expression of ASIC3 in the Trigeminal Nucleus Caudalis Plays a Role in a Rat Model of Recurrent Migraine - Sha Wang; Bai-Xue Wu; Chao-Yang Liu; Guang-Cheng Qin; Wen-Hui Yan; Ji-Ying Zhou; Li-Xue Chen (Journal of Molecular Neuroscience, 2018)

Thimet oligopeptidase and prolyl endopeptidase of spotted scat Scatophagus argus: characterization, tissue distribution, expression at different ovarian stages and down-regulation by estradiol - Si-ping Deng; Dong-neng Jiang; Jian-ye Liu; Zhi-qi Liang; Hua-pu Chen; Tian-li Wu; Chun-hua Zhu; Guang-li Li (Fisheries Science, 2018)

(−)-Epigallocatechin-3-gallate, the major green tea catechin, regulates the desensitization of β1 adrenoceptor via GRK2 in experimental heart failure - Qi Zhang; Liqun Hu; Li Chen; Hongqi Li; Jun Wu; Wenting Liu; Mengyuan Zhang; Guang Yan (Inflammopharmacology, 2018)

Six indicator genes for zinc (Zn) homeostasis in freshwater teleost yellow catfish Pelteobagrus fulvidraco: molecular characterization, mRNA tissue expression and transcriptional changes to Zn exposure - Guang-Hui Chen; Zhi Luo; Chuan-Chuan Wei; Dan-Dan Li; Ya-Xiong Pan (BioMetals, 2018)

Outcomes of EC-MPS combined with low-dose tacrolimus in DCD kidney transplantation for high-risk DGF recipients - Li-zi Jiao; Chen-guang Ding; Pu-xun Tian; Xiao-ming Ding; Xiao-ming Pan; He-li Xiang; Xiao-hui Tian; Yang Li; Jin Zheng; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2018)

Geochronological and sedimentological evidences of Panyangshan foreland basin for tectonic control on the Late Paleozoic plate marginal orogenic belt along the northern margin of the North China Craton - Jialiang Li; Zhiguang Zhou; Yingfu He; Guosheng Wang; Chen Wu; Changfeng Liu; Guang Yao; Wentao Xu; Xiaoqi Zhao; Pengfei Dai (International Journal of Earth Sciences, 2018)

Ecological risk assessment of the Gannan Plateau, northeastern Tibetan Plateau - Dong-xia Yue; Jian-jun Zeng; Chao Yang; Ming-liang Zou; Kai Li; Guan-guang Chen; Jian-jun Guo; Xiao-feng Xu; Xing-min Meng (Journal of Mountain Science, 2018)

A new DDA model for kinematic analyses of rockslides on complex 3-D terrain - Hong Zhang; Shu-guang Liu; Wei Wang; Lu Zheng; Ying-bin Zhang; Yan-qiang Wu; Zheng Han; Yan-ge Li; Guang-qi Chen (Bulletin of Engineering Geology and the Environment, 2018)

PPARβ in yellow catfish Pelteobagrus fulvidraco: molecular characterization, tissue expression and transcriptional regulation by dietary Cu and Zn - Wen-Jing You; Xiao-Ying Tan; Guang-Hui Chen; Chuan-Chuan Wei; Dan-Dan Li (Fish Physiology and Biochemistry, 2018)

An efficient and reusable quaternary ammonium fabric adsorbent prepared by radiation grafting for removal of Cr(VI) from wastewater - Li-juan Pang; Jiang-tao Hu; Mao-jiang Zhang; Chen-guang Yang; Guo-zhong Wu (Environmental Science and Pollution Research, 2018)

Epigenetic modification of TLE1 induce abnormal differentiation in diabetic mice intestinal epithelium - Ji-hao Xu; Guang-cheng Chen; Can-ze Huang; Di Cheng; Ting-feng Wu; Si-yi Wang; Jie-yao Li; Tao Yu; Qi-kui Chen (Molecular and Cellular Biochemistry, 2018)

Phytotoxic, antibacterial, and antioxidant activities of mycotoxins and other metabolites from Trichoderma sp. - Ju-cheng Zhang; Guang-Yi Chen; Xiao-Zhan Li; Ming Hu; Bang-Yan Wang; Bao-Hui Ruan; Hao Zhou; Li-Xing Zhao; Jun Zhou; Zhong-Tao Ding; Ya-Bin Yang (Natural Product Research, 2017)

Retraction Note to: MiR-154 Functions as a Tumor Suppressor in Glioblastoma by Targeting Wnt5a - Dongsheng Zhao; Rencong Wang; Junkang Fang; Xituan Ji; Juan Li; Xiaoyan Chen; Gangfeng Sun; Zhengjun Wang; Weiping Liu; Yangang Wang; Guang Cheng; Haining Zhen; et al. (Molecular Neurobiology, 2017)

Changes in Histopathology, Enzyme Activities, and the Expression of Relevant Genes in Zebrafish (Danio rerio) Following Long-Term Exposure to Environmental Levels of Thallium - Li-Ping Hou; Yang Yang; Hu Shu; Guang-Guo Ying; Jian-Liang Zhao; Yi-Bing Chen; Yong-Heng Chen; Gui-Zhen Fang; Xin Li; Ji-Sheng Liu (Bulletin of Environmental Contamination and Toxicology, 2017)

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

A study of the damage of the intestinal mucosa barrier structure and function of Ctenopharyngodon idella with Aeromonas hydrophila - Wei-Guang Kong; Si-Si Li; Xiao-Xuan Chen; Yu-Qing Huang; Ying Tang; Zhi-Xin Wu (Fish Physiology and Biochemistry, 2017)

Effects of potassium deficiency on root morphology, ultrastructure and antioxidant enzyme system in sweet potato (Ipomoea batatas [L.] Lam.) during early growth - Ming Liu; Ai-Jun Zhang; Xiao-Guang Chen; Rong Jin; Hong-Min Li; Zhong-Hou Tang (Acta Physiologiae Plantarum, 2017)

Demographic history and population genetic structure of Hagenia abyssinica (Rosaceae), a tropical tree endemic to the Ethiopian highlands and eastern African mountains - Andrew W. Gichira; Zhi-Zhong Li; Josphat K. Saina; Guang-Wan Hu; Robert W. Gituru; Qing-Feng Wang; Jin-Ming Chen (Tree Genetics & Genomes, 2017)

A new norsesquiterpene from the roots of Polyalthia laui - Zhang-Xin Yu; Ming-Ye Zhuo; Xiao-Bao Li; Yan-Hui Fu; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han; Xin-Ming Song; Qi-Jing Fan (Natural Product Research, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Erratum to: A metagenomics study for the identification of respiratory viruses in mixed clinical specimens: an application of the iterative mapping approach - Yu-Nong Gong; Shu-Li Yang; Guang-Wu Chen; Yu-Wen Chen; Yhu-Chering Huang; Hsiao-Chen Ning; Kuo-Chien Tsao (Archives of Virology, 2017)

A metagenomics study for the identification of respiratory viruses in mixed clinical specimens: an application of the iterative mapping approach - Yu-Nong Gong; Shu-Li Yang; Guang-Wu Chen; Yu-Wen Chen; Yhu-Chering Huang; Hsiao-Chen Ning; Kuo-Chien Tsao (Archives of Virology, 2017)

A population association study of vitamin D receptor gene polymorphisms and haplotypes with the risk of systemic lupus erythematosus in a Chinese population - Xu-E Chen; Pu Chen; Shan-Shan Chen; Jin Lu; Ting Ma; Guang Shi; Ya Zhou; Ji Li; Liang Sheng (Immunologic Research, 2017)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

RETRACTED ARTICLE: MiR-154 Functions as a Tumor Suppressor in Glioblastoma by Targeting Wnt5a - Dongsheng Zhao; Rencong Wang; Junkang Fang; Xituan Ji; Juan Li; Xiaoyan Chen; Gangfeng Sun; Zhengjun Wang; Weiping Liu; Yangang Wang; Guang Cheng; Haining Zhen; et al. (Molecular Neurobiology, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Effects of melanocortin-4 receptor agonists and antagonists on expression of genes related to reproduction in spotted scat, Scatophagus argus - Dong-Neng Jiang; Jian-Tao Li; Ya-Xiong Tao; Hua-Pu Chen; Si-Ping Deng; Chun-Hua Zhu; Guang-Li Li (Journal of Comparative Physiology B, 2017)

An UDP-Glucosyltransferase Gene from Barley Confers Disease Resistance to Fusarium Head Blight - Li-Ping Xing; Li-Qiang He; Jin Xiao; Qi-Guang Chen; Ming-Hao Li; Yi Shang; Yan-Fei Zhu; Pei-Du Chen; Ai-Zhong Cao; Xiu-E Wang (Plant Molecular Biology Reporter, 2017)

Altered Amygdala Resting-State Functional Connectivity in Maintenance Hemodialysis End-Stage Renal Disease Patients with Depressive Mood - Hui Juan Chen; Yun Fei Wang; Rongfeng Qi; U. Joseph Schoepf; Akos Varga-Szemes; B. Devon Ball; Zhe Zhang; Xiang Kong; Jiqiu Wen; Xue Li; Guang Ming Lu; Long Jiang Zhang (Molecular Neurobiology, 2017)

Evaluation of the antioxidant property and effects in Caenorhabditis elegans of Xiangxi flavor vinegar, a Hunan local traditional vinegar - Run-ting Huang; Qing Huang; Gen-liang Wu; Chun-guang Chen; Zong-jun Li (Journal of Zhejiang University-SCIENCE B, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Cryopreservation of Jerusalem artichoke cultivars using an improved droplet-vitrification method - Jin-Mei Zhang; Li Han; Xin-Xiong Lu; Gayle M. Volk; Xia Xin; Guang-Kun Yin; Juan-Juan He; Ling Wang; Xiao-Ling Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Dating of the topmost terrace in the Jingxian Basin, Anhui Province: an indication of the establishment of the Qingyijiang River - Chun-sheng Hu; Chen-qi Hu; Shao-chen Liu; Guang-lai Xu; Li Wu; Li-hui Yang (Journal of Mountain Science, 2017)

Genomewide association study for seeding emergence and tiller number using SNP markers in an elite winter wheat population - GUANG FENG CHEN; RU GANG WU; DONG MEI LI; HAI XIA YU; ZHIYING DENG; JI CHUN TIAN (Journal of Genetics, 2017)

Spatio-temporal assessments of rockburst hazard combining b values and seismic tomography - Jing Li; Si-Yuan Gong; Jiang He; Wu Cai; Guang-An Zhu; Chang-Bin Wang; Tian Chen (Acta Geophysica, 2017)

Lipid Nanoparticles Loaded with an Antisense Oligonucleotide Gapmer Against Bcl-2 for Treatment of Lung Cancer - Xinwei Cheng; Qibing Liu; Hong Li; Chen Kang; Yang Liu; Tianqi Guo; Ke Shang; Chengyun Yan; Guang Cheng; Robert J. Lee (Pharmaceutical Research, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Leptin receptor overlapping transcript: characterization, tissue distribution and changes in gene expression in response to eyestalk ablation in the Pacific white shrimp Litopenaeus vannamei - Si-Ping Deng; Hua-Pu Chen; Chun-Hua Zhu; Man Ye; Guang-Li Li (Fisheries Science, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Evaluation of estrogenic activity in the Pearl River by using effect-directed analysis - Xiao -Wen Chen; Jian-Liang Zhao; You-Sheng Liu; Li-Xin Hu; Shuang-Shuang Liu; Guang-Guo Ying (Environmental Science and Pollution Research, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Influence of the exclusion distance among trees on gap fraction and foliage clumping index of forest plantations - Jun Geng; Jing-Ming Chen; Li-Li Tu; Qing-Jiu Tian; Lei Wang; Ran-Ran Yang; Yan-Jun Yang; Yan Huang; Wei-Liang Fan; Chun-Guang Lv; Guang Zheng (Trees, 2016)

Identification of FECH gene multiple variations in two Chinese patients with erythropoietic protoporphyria and a review - Zhang-biao Long; Yong-wei Wang; Chen Yang; Gang Liu; Ya-li Du; Guang-jun Nie; Yan-zhong Chang; Bing Han (Journal of Zhejiang University-SCIENCE B, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Inhibition of Adhesion of Enteropathogenic Escherichia coli to HEp-2 Cells by Binding of a Novel Peptide to EspB Protein - Duoyun Li; Zhong Chen; Hang Cheng; Jin-xin Zheng; Wei-guang Pan; Wei-zhi Yang; Zhi-jian Yu; Qi-wen Deng (Current Microbiology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Generation of regulatory dendritic cells after treatment with paeoniflorin - Dan Chen; Yingxi Li; Xiaodong Wang; Keqiu Li; Yaqing Jing; Jinghua He; Zhaoyan Qiang; Jingzhi Tong; Ke Sun; Wen Ding; Yi Kang; Guang Li (Immunologic Research, 2016)

Research on the surface movement rules and prediction method of underground coal gasification - Huai-zhan Li; Guang-li Guo; Jian-feng Zha; Ya-fei Yuan; Bin-chen Zhao (Bulletin of Engineering Geology and the Environment, 2016)

Organic two-photon nanoparticles modulate reactive oxygen species, intracellular calcium concentration, and mitochondrial membrane potential during apoptosis of human gastric carcinoma SGC-7901 cells - Geng Chen; Shou-Ying Li; Hamid Tayyab Malik; Yu-Guang Ma; Hong Xu; Lian-Kun Sun (Biotechnology Letters, 2016)

One-year clinical study of NeuroRegen scaffold implantation following scar resection in complete chronic spinal cord injury patients - Zhifeng Xiao; Fengwu Tang; Jiaguang Tang; Huilin Yang; Yannan Zhao; Bing Chen; Sufang Han; Nuo Wang; Xing Li; Shixiang Cheng; Guang Han; Changyu Zhao; et al. (Science China Life Sciences, 2016)

Phosphorylation of Connexin 43 by Cdk5 Modulates Neuronal Migration During Embryonic Brain Development - Guang-Jian Qi; Qiang Chen; Li-Jun Chen; Yang Shu; Lu-Lu Bu; Xiao-Yun Shao; Pei Zhang; Feng-Juan Jiao; Jin Shi; Bo Tian (Molecular Neurobiology, 2016)

The adipokine Chemerin induces lipolysis and adipogenesis in bovine intramuscular adipocytes - Yuan-Yuan Fu; Kun-Lin Chen; Hui-Xia Li; Guang-Hong Zhou (Molecular and Cellular Biochemistry, 2016)

Two generalized algorithms measuring phase–amplitude cross-frequency coupling in neuronal oscillations network - Qun Li; Chen-guang Zheng; Ning Cheng; Yi-yi Wang; Tao Yin; Tao Zhang (Cognitive Neurodynamics, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

Analysis the role of arabidopsis CKRC6/ASA1 in auxin and cytokinin biosynthesis - Dong-Wei Di; Lei Wu; Pan Luo; Li Zhang; Tian-Zi Zhang; Xue Sun; Shao-Dong Wei; Chen-Wei An; Guang-Qin Guo (Journal of Plant Biology, 2016)

Glutathione homeostasis and Cd tolerance in the Arabidopsis sultr1;1-sultr1;2 double mutant with limiting sulfate supply - Xiang Liu; Fei-Hua Wu; Jing-Xi Li; Juan Chen; Guang-Hui Wang; Wen-Hua Wang; Wen-Jun Hu; Li-Jie Gao; Zong-Ling Wang; Jun-Hui Chen; Martin Simon; Hai-Lei Zheng (Plant Cell Reports, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Photodegradation of Mefenamic Acid in Aqueous Media: Kinetics, Toxicity and Photolysis Products - Ping Chen; Feng Liang Wang; Kun Yao; Jing Shuai Ma; Fu Hua Li; Wen Ying Lv; Guo Guang Liu (Bulletin of Environmental Contamination and Toxicology, 2016)

Carbon stock of larch plantations and its comparison with an old-growth forest in northeast China - Guang Qi; Hua Chen; Li Zhou; Xinchuang Wang; Wangming Zhou; Lin Qi; Yuhua Yang; Fengling Yang; Qingli Wang; Limin Dai (Chinese Geographical Science, 2016)

Investigation of the ASR family in foxtail millet and the role of ASR1 in drought/oxidative stress tolerance - Zhi-Juan Feng; Zhao-Shi Xu; Jiutong Sun; Lian-Cheng Li; Ming Chen; Guang-Xiao Yang; Guang-Yuan He; You-Zhi Ma (Plant Cell Reports, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)

Effects of foraging leaf litter of Aegiceras corniculatum (Ericales, Myrsinaceae) by Parasesarma plicatum (Brachyura, Sesarmidae) crabs on properties of mangrove sediment: a laboratory experiment - Guang C. Chen; Changyi Lu; Rong Li; Bin Chen; Qianfang Hu; Yong Ye (Hydrobiologia, 2016)

Synthesis and Application of Modified Zero-Valent Iron Nanoparticles for Removal of Hexavalent Chromium from Wastewater - Dan-Lian Huang; Guo-Min Chen; Guang-Ming Zeng; Piao Xu; Ming Yan; Cui Lai; Chen Zhang; Ning-Jie Li; Min Cheng; Xiao-Xiao He; Yan He (Water, Air, & Soil Pollution, 2015)

Potential candidate cells for constructing tissue-engineered lacrimal duct epithelium: a histological and cytological study in rabbits - Chen Xie; Xiu-yi Li; Hong-guang Cui (Journal of Zhejiang University-SCIENCE B, 2015)

Repair of articular cartilage defects in rabbits through tissue-engineered cartilage constructed with chitosan hydrogel and chondrocytes - Ming Zhao; Zhu Chen; Kang Liu; Yu-qing Wan; Xu-dong Li; Xu-wei Luo; Yi-guang Bai; Ze-long Yang; Gang Feng (Journal of Zhejiang University-SCIENCE B, 2015)

The impact of hemodialysis on cognitive dysfunction in patients with end-stage renal disease: a resting-state functional MRI study - Hui Juan Chen; Rongfeng Qi; Xiang Kong; Jiqiu Wen; Xue Liang; Zhe Zhang; Xue Li; Guang Ming Lu; Long Jiang Zhang (Metabolic Brain Disease, 2015)

Disruption of thalamic connectivity in Alzheimer’s disease: a diffusion tensor imaging study - Qing-Yong Zhu; Si-Wei Bi; Xiu-Ting Yao; Zhi-Yan Ni; Ying Li; Bo-Yu Chen; Guo-Guang Fan; Xiu-Li Shang (Metabolic Brain Disease, 2015)

cDNA cloning, expression, and immunolocalization of gonad-inhibiting hormone (GIH) in Litopenaeus vannamei - Guang-li Li; Si-ping Deng; Shu-na Jiang; Man Ye; Hua-pu Chen; Siuming F. Chan; Chun-hua Zhu (Genes & Genomics, 2015)

miR21 is Associated with the Cognitive Improvement Following Voluntary Running Wheel Exercise in TBI Mice - Tao Hu; Feng-Jie Zhou; Ye-Fei Chang; Ya-Shan Li; Guang-Cai Liu; Ying Hong; Hong-Lan Chen; Yan-Bin Xiyang; Tian-hao Bao (Journal of Molecular Neuroscience, 2015)

Intravenous Thrombolytic Therapy for Acute Ischemic Stroke with Subclavian Arterial Steal Syndrome: A Case Report - Xiao-Guang Tong; Yuxin Wang; Yan Chen; Chenhao Zhang; Chen-Hua Li; Zhong Dong; Xiao-Wei Zhang; Fang-Fang Zhang; Hang Yin; Jin-Huan Wang; Pei-Lan Zhang (Cell Biochemistry and Biophysics, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Involvement of sulfhydryl compounds and antioxidant enzymes in H2S-induced heat tolerance in tobacco (Nicotiana tabacum L.) suspension-cultured cells - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang; Tao Chen (In Vitro Cellular & Developmental Biology - Plant, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Physiological response to potassium deficiency in three sweet potato (Ipomoea batatas [L.] Lam.) genotypes differing in potassium utilization efficiency - Zhong-Hou Tang; Ai-Jun Zhang; Meng Wei; Xiao-Guang Chen; Zheng-Hui Liu; Hong-Min Li; Yan-Feng Ding (Acta Physiologiae Plantarum, 2015)

Late Cenozoic transtensional fault belt discovered on the boundary of the Awati Sag in the northwestern Tarim Basin - Yue-Jun Li; Qiang Zhang; Guang-Ya Zhang; Hai-Jun Yang; Xian-Zhang Yang; Jun Shi; Yuan Neng; Yan-Gui Chen; Lei Wen (International Journal of Earth Sciences, 2015)

Growth of embryo and gene expression of nutrient transporters in the small intestine of the domestic pigeon (Columba livia) - Ming-xia Chen; Xiang-guang Li; Jun-xian Yang; Chun-qi Gao; Bin Wang; Xiu-qi Wang; Hui-chao Yan (Journal of Zhejiang University-SCIENCE B, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

The effects of land use and landscape position on labile organic carbon and carbon management index in red soil hilly region, southern China - Zhong-wu Li; Xiao-dong Nie; Xiao-lin Chen; Yin-mei Lu; Wei-guo Jiang; Guang-ming Zeng (Journal of Mountain Science, 2015)

Enhancement of post-anoxic denitrification for biological nutrient removal: effect of different carbon sources - Hong-bo Chen; Dong-bo Wang; Xiao-ming Li; Qi Yang; Guang-ming Zeng (Environmental Science and Pollution Research, 2015)

Photodegradation of Ibuprofen Under UV–Vis Irradiation: Mechanism and Toxicity of Photolysis Products - Fu Hua Li; Kun Yao; Wen Ying Lv; Guo Guang Liu; Ping Chen; Hao Ping Huang; Ya Pu Kang (Bulletin of Environmental Contamination and Toxicology, 2015)

Enhanced Phytoextraction of Heavy Metals from Contaminated Soil by Plant Co-cropping Associated with PGPR - Zhi-feng Liu; Hong-guang Ge; Chen Li; Zuo-ping Zhao; Feng-min Song; Shi-bin Hu (Water, Air, & Soil Pollution, 2015)

Okibacterium endophyticum sp. nov., a novel endophytic actinobacterium isolated from roots of Salsola affinis C. A. Mey - Hong-Fei Wang; Yong-Guang Zhang; Li Li; Wei-Hong Liu; Wael N. Hozzein; Ji-Yue Chen; Jian-Wei Guo; Yuan-Ming Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Optimization of the expression conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by response surface methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

The decreased frequency of SIGIRR-positive CD4+ T cells in peripheral blood of patients with SLE and its correlation with disease activity - Dao-Yang Wang; Chao Su; Gui-Mei Chen; Hai-Feng Pan; Feng-Mei Wang; Gui-Ling Liu; Li Hao; De-Guang Wang; Dong-Qing Ye (Molecular Biology Reports, 2015)

BpGH3.5, an early auxin-response gene, regulates root elongation in Betula platyphylla × Betula pendula - Guang Yang; Su Chen; Shuo Wang; Guifeng Liu; Huiyu Li; Haijiao Huang; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

Molecular characterization of a novel reovirus isolated from Pekin ducklings in China - Ying-Qi Zhu; Chuan-Feng Li; Zhuang-Li Bi; Zong-Yan Chen; Chun-Chun Meng; Gui-Jun Wang; Chan Ding; Guang-Qing Liu (Archives of Virology, 2015)

Variovorax guangxiensis sp. nov., an aerobic, 1-aminocyclopropane-1-carboxylate deaminase producing bacterium isolated from banana rhizosphere - Jun-lian Gao; Mei Yuan; Xu-ming Wang; Tian-lei Qiu; Ji-wei Li; Hong-can Liu; Xiu-ai Li; Jian Chen; Jian-guang Sun (Antonie van Leeuwenhoek, 2015)

Labedella endophytica sp. nov., a novel endophytic actinobacterium isolated from stem of Anabasis elatior (C. A. Mey.) Schischk - Hong-Fei Wang; Yong-Guang Zhang; Juan Cheng; Wael N. Hozzein; Wei-Hong Liu; Li Li; Ji-Yue Chen; Jian-Wei Guo; Yuan-Ming Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Effect of Trash Addition to the Soil on Microbial Communities and Physico-Chemical Properties of Soils and Growth of Sugarcane Plants - Qing Liao; Guang-Po Wei; Gui-Fen Chen; Bin Liu; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2014)

Genome-Wide Analysis of the C3H Zinc Finger Transcription Factor Family and Drought Responses of Members in Aegilops tauschii - An-Long Jiang; Zhao-Shi Xu; Guang-Yao Zhao; Xiao-Yu Cui; Ming Chen; Lian-Cheng Li; You-Zhi Ma (Plant Molecular Biology Reporter, 2014)

Identification of a potential novel type of influenza virus in Bovine in China - Wen-Ming Jiang; Su-Chun Wang; Cheng Peng; Jian-Min Yu; Qing-Ye Zhuang; Guang-Yu Hou; Shuo Liu; Jin-Ping Li; Ji-Ming Chen (Virus Genes, 2014)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

Multiple correlations of mRNA expression and protein abundance in human cytokine profile - Hong-wu Du; Guang-yu Chen; Chun-he Yang; Chuan-bao Li; Yi-ping Xun; Jia Liu; Peng Chen; Li-li Shi (Molecular Biology Reports, 2014)

Microseismic monitoring of columnar jointed basalt fracture activity: a trial at the Baihetan Hydropower Station, China - Bing-Rui Chen; Qing-Peng Li; Xia-Ting Feng; Ya-Xun Xiao; Guang-Liang Feng; Lian-Xing Hu (Journal of Seismology, 2014)

A more sensitive and rapid multiplex RT-PCR assay combining with magnetic nanobeads for simultaneous detection of viruses in sweet potato - Xing-Guang Deng; Feng Zhu; Ying-Juan Chen; Jian Liu; Tong Zhu; Jing-Yi Li; De-Hui Xi; Hong-Hui Lin (European Journal of Plant Pathology, 2014)

The Role of the QseC Quorum-Sensing Sensor Kinase in Epinephrine-Enhanced Motility and Biofilm Formation by Escherichia coli - Kun Yang; Jun Meng; Yun-chao Huang; Lian-hua Ye; Guang-jian Li; Jie Huang; Hua-mei Chen (Cell Biochemistry and Biophysics, 2014)

Clinical Factors Associated With the Diagnosis and Progression of Diabetic Nephropathy - Shuang Liang; Qian Li; Han-Yu Zhu; Jian-Hui Zhou; Rui Ding; Xiang-Mei Chen; Guang-Yan Cai (Cell Biochemistry and Biophysics, 2014)

Steady-state and dynamic photosynthetic performance and nitrogen partitioning in the shade-demanding plant Panax notoginseng under different levels of growth irradiance - Jun-Wen Chen; Shuang-Bian Kuang; Guang-Qiang Long; Zeng-Gui Meng; Long-Gen Li; Zhong-Jian Chen; Guang-Hui Zhang; Sheng-Chao Yang (Acta Physiologiae Plantarum, 2014)

The protective effect of rosmarinic acid on hyperthermia-induced C2C12 muscle cells damage - Kun-Lin Chen; Hui-Xia Li; Xing-Lian Xu; Guang-Hong Zhou (Molecular Biology Reports, 2014)

mir-300 Promotes Self-Renewal and Inhibits the Differentiation of Glioma Stem-Like Cells - Daming Zhang; Guang Yang; Xin Chen; Chunmei Li; Lu Wang; Yaohua Liu; Dayong Han; Huailei Liu; Xu Hou; Weiguang Zhang; Chenguang Li; Zhanqiang Han; et al. (Journal of Molecular Neuroscience, 2014)

Catechin ameliorates cardiac dysfunction in rats with chronic heart failure by regulating the balance between Th17 and Treg cells - Qi Zhang; Li-qun Hu; Chang-sen Yin; Ping Chen; Hong-qi Li; Xin Sun; Guang Yan (Inflammation Research, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Sequence and phylogenetic analysis of surface protein genes of emerging H9N2 influenza viruses isolated from poultry in two geographical regions of China - Yu Xue; Jing-Lan Wang; Zhuan-Qiang Yan; Guang-Wei Li; Shun-Yan Chen; Xiang-Bin Zhang; Jian-Ping Qin; Hai-Yan Li; Shuang Chang; Feng Chen; Ying-Zuo Bee; Qing-Mei Xie (Virus Genes, 2014)

Temperature influence on biological phosphorus removal induced by aerobic/extended-idle regime - Hong-bo Chen; Dong-bo Wang; Xiao-ming Li; Qi Yang; Kun Luo; Guang-ming Zeng (Environmental Science and Pollution Research, 2014)

Differences in Gene Expression and Regulation during Ontogenetic Phase Change in Apple Seedlings - Yan Gao; Feng Qiu Yang; Xin Cao; Chun Min Li; Yi Wang; Yong Bo Zhao; Guang Juan Zeng; Dong Mei Chen; Zhen Hai Han; Xin Zhong Zhang (Plant Molecular Biology Reporter, 2014)

CATS derived SNPs discovery in the golden snub-nosed monkey (Rhinopithecus roxellanae) - Chen Cheng; Shuzhen Li; Boshi Wang; Maofang Luo; Yunxia Yang; Guang Yang; Ming Li (Conservation Genetics Resources, 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

Research on global change scientific satellites - HuaDong Guo; WenXue Fu; XinWu Li; Pei Chen; Guang Liu; Zhen Li; Cheng Wang; Qing Dong; LiPing Lei; LinYan Bai; QingJie Liu (Science China Earth Sciences, 2014)

Characterization and genetic mapping of a Photoperiod-sensitive dwarf 1 locus in rice (Oryza sativa L.) - Riqing Li; Jixing Xia; Yiwei Xu; Xiucai Zhao; Yao-Guang Liu; Yuanling Chen (Theoretical and Applied Genetics, 2014)

Absorptive constituents and their metabolites in drug-containing urine samples from Wuzhishan miniature pigs orally administered with Buyang Huanwu decoction - Dong-Hui Yang; Xiang-Liang Ren; Feng Xu; Xiao-Qing Ma; Guang-Xue Liu; Cang-Hai Li; Chen Li; Shao-Qing Cai (Journal of Natural Medicines, 2014)

Streptomyces fukangensis sp. nov., a novel alkaliphilic actinomycete isolated from a saline-alkaline soil - Yong-Guang Zhang; Hong-Fei Wang; Qing Liu; Wael N. Hozzein; Mohammed A. M. Wadaan; Juan Cheng; Yue-Ji Chen; Yuan-Ming Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Effects of ecological factors on secondary metabolites and inorganic elements of Scutellaria baicalensis and analysis of geoherblism - LanPing Guo; Sheng Wang; Ji Zhang; Guang Yang; ManXi Zhao; WeiFeng Ma; XiaoBo Zhang; Xuan Li; BangXing Han; NaiFu Chen; LuQi Huang (Science China Life Sciences, 2013)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Correlation of Nr4a2 Expression with the Neuron Progenitors in Adult Zebrafish Brain - Sheng Chen; Guang Rui Luo; Ting Li; Ting Xi Liu; Weidong Le (Journal of Molecular Neuroscience, 2013)

A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Saccharopolyspora cavernae sp. nov., a novel actinomycete isolated from the Swallow Cave in Yunnan, south-west China - Juan Cheng; Yong-Guang Zhang; Wei Chen; Li Li; Dao-Feng Zhang; Hong-Fei Wang; Xin-Hua Lu; Yan-Qing Duan; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Quantitative changes of nitrergic neurons during postnatal development of chicken myenteric plexus - Ping Yang; Jameel Ahmed Gandahi; Qian Zhang; Lin-li Zhang; Xun-guang Bian; Li Wu; Yi Liu; Qiu-sheng Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Cytochrome P450 oxidoreductase genetic polymorphisms A503V and rs2868177 do not significantly affect warfarin stable dosage in Han-Chinese patients with mechanical heart valve replacement - Sheng-Lan Tan; Zhi Li; Wei Zhang; Guo-Bao Song; Li-Ming Liu; Juan Peng; Zhao-Qian Liu; Lan Fan; Xiang-Guang Meng; Lian-Sheng Wang; Yao Chen; Xin-Min Zhou; et al. (European Journal of Clinical Pharmacology, 2013)

Analogical model test and theoretical analysis on zonal disintegration based on filed monitoring in deep tunnel - Xu-Guang Chen; Yuan Wang; Qiang-Yong Zhang; Shu-Cai Li; Erling Nordlund (European Journal of Environmental and Civil Engineering, 2013)

An Application of Remote Sensing Data in Mapping Landscape-Level Forest Biomass for Monitoring the Effectiveness of Forest Policies in Northeastern China - Xinchuang Wang; Guofan Shao; Hua Chen; Bernard J. Lewis; Guang Qi; Dapao Yu; Li Zhou; Limin Dai (Environmental Management, 2013)

Rothia marina sp. nov., isolated from an intertidal sediment of the South China Sea - Zhu-Xiang Liu; Ling-Ling Yang; Ying Huang; Hu Zhao; He Liu; Shu-Kun Tang; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2013)

Screening and test of CD40 related signal transduction pathway in AGS cells and construction of gene silencing vector - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Partial or complete substitution of fish meal with soybean meal and cottonseed meal in Chinese mitten crab Eriocheir sinensis diets - Hai-Bo Jiang; Li-Qiao Chen; Jian-Guang Qin; Lu-Jiao Gao; Er-Chao Li; Na Yu; Sheng-Ming Sun; Xue-Qin Jiang (Aquaculture International, 2013)

Strategy for pH control and pH feedback-controlled substrate feeding for high-level production of l-tryptophan by Escherichia coli - Li-Kun Cheng; Jian Wang; Qing-Yang Xu; Chun-Guang Zhao; Zhi-Qiang Shen; Xi-Xian Xie; Ning Chen (World Journal of Microbiology and Biotechnology, 2013)

Mitochondrial Dysfunction Induced by Honokiol - Jia-Xin Dong; Guang-Yuan Zhao; Qiu-Li-Yang Yu; Ran Li; Lian Yuan; Jing Chen; Yi Liu (The Journal of Membrane Biology, 2013)

Extracellular Signal-Regulated Kinase 5 in the Cerebrospinal Fluid-Contacting Nucleus Contributes to Morphine Physical Dependence in Rats - Chun-Guang Wang; Yan-Ling Ding; Tian-Fang Zheng; Jing-Qiu Wei; He Liu; Yu-Feng Chen; Jia-You Wang; Li-Cai Zhang (Journal of Molecular Neuroscience, 2013)

Geochronology and geochemistry of leucosomes in the North Dabie Terrane, East China: implication for post-UHPM crustal melting during exhumation - Shui-Jiong Wang; Shu-Guang Li; Li-Juan Chen; Yong-Sheng He; Shi-Chao An; Ji Shen (Contributions to Mineralogy and Petrology, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Effect of PI3K gene silencing on growth, migration and related proteins expression of CD40 signal-mediated gastric cancer cells - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2013)

Variations in soil culturable bacteria communities and biochemical characteristics in the Dongkemadi glacier forefield along a chronosequence - Guang-Xiu Liu; Ping Hu; Wei Zhang; Xiukun Wu; Xuan Yang; Tuo Chen; Manxiao Zhang; Shi-Weng Li (Folia Microbiologica, 2012)

Paenibacillus taohuashanense sp. nov., a nitrogen-fixing species isolated from rhizosphere soil of the root of Caragana kansuensis Pojark - Jian-Bo Xie; Li-Hong Zhang; Yu-Guang Zhou; Hong-Can Liu; San-Feng Chen (Antonie van Leeuwenhoek, 2012)

Correlation between serum CA724 and gastric cancer: multiple analyses based on Chinese population - Xin-Zu Chen; Wei-Ke Zhang; Kun Yang; Lan-Lan Wang; Jin Liu; Li Wang; Jian-Kun Hu; Bo Zhang; Zhi-Xin Chen; Jia-Ping Chen; Zong-Guang Zhou; Xian-Ming Mo (Molecular Biology Reports, 2012)

Combined effect of sCD40L and PI3K siRNA on transplanted tumours growth and microenvironment in nude mice with gastric cancer - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2012)

CD40 signal expression in gastric cancer tissue and its correlation with prognosis of gastric cancer patients - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

The evolution and utility of ribosomal ITS sequences in Bambusinae and related species: divergence, pseudogenes, and implications for phylogeny - HUI-XING SONG; SU-PING GAO; MING-YAN JIANG; GUANG-LI LIU; XIAO-FANG YU; QI-BING CHEN (Journal of Genetics, 2012)

Effect of hepcidin on intracellular calcium in human osteoblasts - Guang-Fei Li; You-Jia Xu; Yin-Feng He; Ben-Cai Du; Peng Zhang; Dong-Yang Zhao; Chen Yu; Chen-Hao Qin; Kai Li (Molecular and Cellular Biochemistry, 2012)

High prevalence of Eimeria infection in dairy goats in Shaanxi province, northwestern China - Guang Hui Zhao; Li-Hui Lei; Chuan-Chuan Shang; Man Gao; Yan Qing Zhao; Chao-Xi Chen; De-Kun Chen (Tropical Animal Health and Production, 2012)

Gastric cancer cell lines AGS before and after CD40 signal activating - Rui Li; Xue-Qin Pang; Wei-Chang Chen; Ling Li; Wen-Yan Tian; Xue-Guang Zhang (Molecular Biology Reports, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Cohnella plantaginis sp. nov., a novel nitrogen-fixing species isolated from plantain rhizosphere soil - Li-Ying Wang; San-Feng Chen; Lei Wang; Yu-Guang Zhou; Hong-Can Liu (Antonie van Leeuwenhoek, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Characterization of HbEREBP1, a wound-responsive transcription factor gene in laticifers of Hevea brasiliensis Muell. Arg. - Yue-Yi Chen; Li-Feng Wang; Long-Jun Dai; Shu-Guang Yang; Wei-Min Tian (Molecular Biology Reports, 2012)

Optimisation of preparation conditions and properties of phytosterol liposome-encapsulating nattokinase - Xu-Yan Dong; Fan-Pi Kong; Gang-You Yuan; Fang Wei; Mu-Lan Jiang; Guang-Ming Li; Zhan Wang; Yuan-Di Zhao; Hong Chen (Natural Product Research, 2012)

The distribution of IGF2 and IMP3 in osteosarcoma and its relationship with angiogenesis - Peng Chen; Shao-jin Wang; Hong-bo Wang; Peng Ren; Xi-qian Wang; Wen-guang Liu; Wan-li Gu; Dong-qing Li; Ting-guo Zhang; Cheng-jun Zhou (Journal of Molecular Histology, 2012)

Influence of sCD40L on gastric cancer cell lines - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Xue-Guang Zhang (Molecular Biology Reports, 2011)

MiR-106a inhibits glioma cell growth by targeting E2F1 independent of p53 status - Guang Yang; Ruyou Zhang; Xiaofeng Chen; Yulong Mu; Jing Ai; Chen Shi; Yaohua Liu; Changbin Shi; Lihua Sun; Nikolai G. Rainov; Hulun Li; Baofeng Yang; et al. (Journal of Molecular Medicine, 2011)

A high-throughput method for screening of Aspergillus niger mutants with high transglycosylation activity by detecting non-fermentable reducing sugar - Gui-guang Chen; Wei Li; Yun-kai Zhang; Yong-ling Qin; Kong-yang Wu; Zhi-qun Liang (World Journal of Microbiology and Biotechnology, 2011)

Sphingomonas hunanensis sp. nov., isolated from forest soil - Qi-Hui Chen; Jin-Hua Chen; Ying Ruan; Yu-Qin Zhang; Shu-Kun Tang; Zhu-Xiang Liu; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2011)

Moisture sorption characteristics of freeze-dried human platelets - Meng-jie Xu; Guang-ming Chen; Ju-li Fan; Jin-hui Liu; Xian-guo Xu; Shao-zhi Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Chemical-protein interactome and its application in off-target identification - Lun Yang; Ke-Jian Wang; Li-Shan Wang; Anil G. Jegga; Sheng-Ying Qin; Guang He; Jian Chen; Yue Xiao; Lin He (Interdisciplinary Sciences: Computational Life Sciences, 2011)

Bacillus hunanensis sp. nov., a slightly halophilic bacterium isolated from non-saline forest soil - Yi-Guang Chen; Di-Fei Hao; Qi-Hui Chen; Yu-Qin Zhang; Jian-Ben Liu; Jian-Wu He; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Bacillus zhanjiangensis sp. nov., isolated from an oyster in South China Sea - Yi-Guang Chen; Song-Ping Hu; Shu-Kun Tang; Jian-Wu He; Jian-Qing Xiao; Hong-Yi Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

Extraction of essential oils from garlic (Allium sativum) using ligarine as solvent and its immunity activity in gastric cancer rat - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Analysis of the essential oil of magnolia and its effect on antioxidant enzyme activity, sCD40L and phosphorylate-activate Akt protein levels in gastric cancer mice - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Oxygen consumption and ammonia excretion of black carp (Mylopharyngdon piceus Richardson) and allogynogenetic crucian carp (Carassius auratus gibelio ♀ × Cyprinus carpio ♂) fed different carbohydrate diets - Chun Fang Cai; Yuan Tu Ye; Li Qiao Chen; Jian Guang Qin; Yong Ling Wang (Fish Physiology and Biochemistry, 2010)

MicroRNA-200b regulates cyclin D1 expression and promotes S-phase entry by targeting RND3 in HeLa cells - Wei Xia; Jie Li; Liucun Chen; Baochun Huang; Shaohua Li; Guang Yang; Hongmei Ding; Fang Wang; Nongle Liu; Qiang Zhao; Tao Fang; Tao Song; et al. (Molecular and Cellular Biochemistry, 2010)

Preliminary study on the freeze-drying of human bone marrow-derived mesenchymal stem cells - Shao-zhi Zhang; Huan Qian; Zhen Wang; Ju-li Fan; Qian Zhou; Guang-ming Chen; Rui Li; Shan Fu; Jie Sun (Journal of Zhejiang University-SCIENCE B, 2010)

Development of a large-scale isolation chamber system for the safe and humane care of medium-sized laboratory animals harboring infectious diseases - Xin Pan; Jian-cheng Qi; Ming Long; Hao Liang; Xiao Chen; Han Li; Guang-bo Li; Hao Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Jeotgalibacillus soli sp. nov., isolated from non-saline forest soil, and emended description of the genus Jeotgalibacillus - Yi-Guang Chen; De-Jiao Peng; Qi-Hui Chen; Yu-Qin Zhang; Shu-Kun Tang; Da-Chun Zhang; Qing-Zhong Peng; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Yaniella soli sp. nov., a new actinobacterium isolated from non-saline forest soil in China - Yi-Guang Chen; Jun Chen; Qi-Hui Chen; Shu-Kun Tang; Yu-Qin Zhang; Jian-Wu He; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2010)

Identification of p27/KIP1 expression level as a candidate biomarker of response to rapalogs therapy in human cancer - Guang Chen; Na Yang; Xiang Wang; Si-Yuan Zheng; Yi Chen; Lin-Jiang Tong; Yi-Xue Li; Ling-Hua Meng; Jian Ding (Journal of Molecular Medicine, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Nocardiopsis terrae sp. nov., a halophilic actinomycete isolated from saline soil - Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Zhu-Xiang Liu; Li-Hua Xu; Li-Xin Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Detection of Bifidobacterium Species-specific 16S rDNA Based on QD FRET Bioprobe - JunFeng Jiang; ZhiHui Peng; Le Deng; Guang Li; LinLi Chen (Journal of Fluorescence, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Effects of upregulated expression of microRNA-16 on biological properties of culture-activated hepatic stellate cells - Can-Jie Guo; Qin Pan; Bo Jiang; Guang-Yu Chen; Ding-Guo Li (Apoptosis, 2009)

Virgibacillus zhanjiangensis sp. nov., a marine bacterium isolated from sea water - Qing-Zhong Peng; Jun Chen; Yu-Qin Zhang; Qi-Hui Chen; De-Jiao Peng; Xiao-Long Cui; Wen-Jun Li; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

Halobacillus hunanensis sp. nov., a moderately halophilic bacterium isolated from a subterranean brine - Qing-Zhong Peng; Qing-Jing Peng; Yu-Qin Zhang; Zhu-Xiang Liu; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui; Yi-Guang Chen (Antonie van Leeuwenhoek, 2009)

Enhancement of mucosal immune response against the M2eHBc+ antigen in mice with the fusion expression products of LTB and M2eHBc+ through mucosal immunization route - Guo-guang Zhang; Dong-xiao Li; Hui-huang Zhang; Ya-ming Zeng; Liang Chen (Veterinary Research Communications, 2009)

Antitumor effect of the seashell protein Haishengsu on Ehrlich ascites tumor: an experimental study - Ji-Zhu Liu; Shou-Guo Chen; Zhang Bin; Chun-Bo Wang; Guang-Yao Li; Le-Xin Wang (Journal of Natural Medicines, 2009)

Cloning and expression analysis of hsp70 gene from freshwater planarian Dugesia japonica - Ke-Xue Ma; Guang-Wen Chen; Hao Lou; Li-Na Fei (Biologia, 2009)

Virgibacillus litoralis sp. nov., a moderately halophilic bacterium isolated from saline soil - Yi-Guang Chen; Zhu-Xiang Liu; De-Jiao Peng; Yu-Qin Zhang; Yong-Xia Wang; Shu-Kun Tang; Wen-Jun Li; Xiao-Long Cui; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Alteromonas halophila sp. nov., a new moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Huai-Dong Xiao; Shu-Kun Tang; Yu-Qin Zhang; Entomack Borrathybay; Xiao-Long Cui; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

ATG16L1 T300A polymorphism and Crohn’s disease susceptibility: evidence from 13,022 cases and 17,532 controls - Hai-Feng Zhang; Li-Xin Qiu; Yu Chen; Wa-Li Zhu; Chen Mao; Li-Guang Zhu; Ming-Hua Zheng; Yan Wang; Lei Lei; Jian Shi (Human Genetics, 2009)

Halobacillus naozhouensis sp. nov., a moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Zhi-Xiong Liu; Yu-Qin Zhang; You-Xiang Zhang; Shu-Kun Tang; Entomack Borrathybay; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Arthrobacter halodurans sp. nov., a new halotolerant bacterium isolated from sea water - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhao-Yang Li; Lang-Bo Yi; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

β-Amino-butyric acid protects Arabidopsis against low potassium stress - Shuqing Cao; Li Jiang; Huaibo Yuan; Hongyong Jian; Guang Ren; Xiaohui Bian; Jizhi Zou; Zhengyi Chen (Acta Physiologiae Plantarum, 2008)

Occurrence of entomopathogenic fungi in migratory alate aphids in Yunnan Province of China - Bin Chen; Zheng Yue Li; Ming Guang Feng (BioControl, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

Protolith natures and U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) zircon ages of the metabasites in Hainan Island, South China: Implications for geodynamic evolution since the late Precambrian - De‐Ru Xu; Bin Xia; Peng‐Chun Li; Guang‐Hao Chen; Ci Ma; Yu‐Quan Zhang (Island Arc, 2007)
Metabasites within the Paleozoic volcanic‐clastic sedimentary sequences in Hainan Island, South China, show large differences not only in the nature of protoliths, but also in zircon U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) ages. The protoliths for the Tunchang area metabasites have intraoceanic arc geochemical affinities. In the east‐central island gabbroic to diabasic rocks and pillow lavas are also present, while the Bangxi area metabasites with back‐arc geochemical affinities in the northwest island consist of basaltic, gabbroic and/or picritic rocks. Three types of zircon domains/crystals in the Tunchang area metabasites are defined. Type 1 is comagmatic and yields concordant to approximately concordant 206 Pb/238 U ages ranging from 442.1 ± 13.7 Ma to 514.3 ± 30.2 Ma with a weighted U‐Pb mean age of 445 ± 10 Ma. Type 2 is inherited and yields a weighted 207 Pb/206 Pb mean age of 2488.1 ± 8.3 Ma. Type 3 is magmatic with a 207 Pb/206 Pb age of ca 1450 Ma. Magmatic zircons in the Bangxi area metabasites yield a weighted U‐Pb mean age of 269 ± 4 Ma. We suggest 450 Ma is the minimum age for crystallization of protoliths of the Tunchang area metabasites, because the age range of ca 440–514 Ma probably corresponds to both the time of igneous crystallization and the high‐temperature overprint. The presence of abundant inherited zircons strongly favors derivation of these rocks from a NMORB‐like mantle proximal to continental crust. A protolith age of ca 270 Ma for the Bangxi area metabasites probably records expansion of an epircontinental back‐arc basin and subsequent generation of a small oceanic basin. The presence of ophiolitic rocks with an age of ca 450 Ma, not only in Hainan Island, but also in the Yangtze block, highlights the fact that the South China Caledonian Orogeny was not intracontinental in nature, but characterized by an ocean‐related event.

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Expression of a truncated ripening inhibitor (RIN) protein from tomato and production of an anti-RIN antibody - Hong-Liang Zhu; Ben-Zhong Zhu; Ya-Li Zhang; Yi Shao; Xiao-Guang Wang; Yuan-Hong Xie; An-Jun Chen; Ying-Cong Li; Hui-Qin Tian; Yun-Bo Luo (Biotechnology Letters, 2007)

Studies on optimization of nitrogen sources for astaxanthin production by Phaffia rhodozyma - Hui Ni; Qi-he Chen; Hui Ruan; Yuan-fan Yang; Li-jun Li; Guang-bin Wu; Yang Hu; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2007)

Improved production of ethanol by deleting FPS1 and over-expressing GLT1 in Saccharomyces cerevisiae - Qing-Xue Kong; Ji-Guang Gu; Li-Min Cao; Ai-Li Zhang; Xun Chen; Xue-Ming Zhao (Biotechnology Letters, 2006)

Remediation of pentachlorophenol-contaminated soil by composting with immobilized Phanerochaete chrysosporium - Xiao-yun Jiang; Guang-ming Zeng; Dan-lian Huang; Yang Chen; Fang Liu; Guo-he Huang; Jian-bing Li; Bei-dou Xi; Hong-liang Liu (World Journal of Microbiology and Biotechnology, 2006)

Laccase activities of a soil fungus Penicillium simplicissimum in relation to lignin degradation - Guang Ming Zeng; Hong Yan Yu; Hong Li Huang; Dan Lian Huang; Yao Ning Chen; Guo He Huang; Jian Bing Li (World Journal of Microbiology and Biotechnology, 2006)

Testifying the rice bacterial blight resistance gene xa5 by genetic complementation and further analyzing xa5 (Xa5) in comparison with its homolog TFIIAγ1 - Guang-Huai Jiang; Zhi-Hui Xia; Yong-Li Zhou; Jia Wan; Da-Yong Li; Run-Sheng Chen; Wen-Xue Zhai; Li-Huang Zhu (Molecular Genetics and Genomics, 2006)

Cloning and characterization of an HDZip I gene GmHZ1 from soybean - Yong-Jun Wang; Yi-Dan Li; Guang-Zuo Luo; Ai-Guo Tian; Hui-Wen Wang; Jin-Song Zhang; Shou-Yi Chen (Planta, 2005)

Soybean DRE-binding transcription factors that are responsive to abiotic stresses - Xue-Ping Li; Ai-Guo Tian; Guang-Zuo Luo; Zhi-Zhong Gong; Jin-Song Zhang; Shou-Yi Chen (Theoretical and Applied Genetics, 2005)

Single-step recovery of ephedrine hydrochloride from raw materials using expanded bed adsorption - Wei-Dong Chen; Yan-Dong Wang; Li-hang Zha; Guang-Hui Ma; Zhi-Guo Su (Biotechnology Letters, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)

Alteration of N-acetylglucosaminyltransferases in pancreatic carcinoma - Bi-cheng Nan; Dong-min Shao; Hui-li Chen; Yong Huang; Jian-xin Gu; Yi-bin Zhang; Zhao-guang Wu (Glycoconjugate Journal, 1998)